Water-activated hydrogel-based medical patches, flexible substrates, and methods of making and using such patches
The limitations of existing hydrogels in surgical enclosure and healing applications are solved by dry hydrogel patches forming electrophilic and nucleophilic hydrogel precursor layers on porous hydrophilic substrates, achieving rapid crosslinking and Effective adhesion improves the flexibility and healing effect of the patch.
Patent Information
- Application Number
- CN202380038586.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-03
- Filing Date
- 2023-05-04
- Publication Date
- 2024-12-27
AI Technical Summary
Existing hydrogels have limitations in surgical closure, drug delivery and tissue healing applications, limiting their effective use.
Using a medical patch including a biocompatible substrate and a dry hydrogel precursor layer, the hydrogel precursor layer consists of an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor, which is porous hydrophilic through a dry atmosphere. A hydrogel precursor layer is formed on the substrate and spontaneously crosslinked in a physiological solution to adhere to the tissue.
Fast and predictable adhesion and crosslinking are achieved, which can effectively control bleeding, promote healing, and are suitable for difficult-to-reach locations, improving the flexibility and adhesion of the patch.
Smart Images

Figure CN119212741A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This PCT application claims priority to the following co-pending U.S. patent applications: U.S. patent application 17 / 738,847, filed by Bassett et al. on May 6, 2022, entitled "Water-activated hydrogel-based medical patches and methods of making and using such patches," and U.S. patent application 18 / 142,956, filed by Bassett et al. on May 3, 2023, entitled "Water-activated hydrogel-based medical patches, flexible substrates, and methods of making and using such patches," both of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to medical patches based on hydrogels, and more particularly to methods of using such patches as hemostatic patches to control bleeding, surgical closure, promote healing, and carry out local drug delivery. The invention further relates to methods of making patches, such as forming a melt blend, which is cast onto a suitable substrate. Flexible substrates allow delivery of folded patches to be placed in otherwise difficult to reach locations. Background Art
[0004] Hydrogels have found a range of uses in medical applications for surgical closures, drug delivery, tissue fillers, spacers, etc. In the case of wound healing, hydrogel materials can provide a hydrophilic environment to isolate tissue and promote healing. For hemostasis and other wound healing applications, existing products have limitations that restrict their effective use. Summary of the invention
[0005] In a first aspect, the present invention relates to a medical patch comprising a biocompatible substrate and a dry hydrogel precursor layer on the substrate, the dry hydrogel precursor layer comprising an electrophilic hydrogel precursor having a plurality of electrophilic functional groups and a nucleophilic hydrogel precursor having a plurality of protonated amine groups and no more than about 2% by weight of water. Typically, both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncrosslinked and are blended or in direct contact with each other.
[0006] In another aspect, the present invention relates to a medical patch, comprising a biocompatible substrate and a dried hydrogel precursor layer on the substrate, the dried hydrogel precursor layer comprising a PEG-electrophilic hydrogel precursor and a PEG-nucleophilic hydrogel precursor and no more than about 2% by weight of water, the PEG-electrophilic hydrogel precursor having a plurality of arms with terminal reactive electrophilic groups, the PEG-nucleophilic hydrogel precursor having a plurality of arms with terminal protonated amine groups. Typically, both the PEG-electrophilic hydrogel precursor and the PEG-nucleophilic hydrogel precursor are substantially uncrosslinked, and the dried hydrogel precursor layer forms a crosslinked hydrogel within no more than 5 minutes after hydration with a physiological solution.
[0007] In another aspect, the present invention relates to a method for forming a medical patch, the method comprising:
[0008] One or more layers of liquid are applied to a porous hydrophilic substrate in a dry atmosphere to form a hydrogel precursor layer on the porous hydrophilic substrate, wherein the hydrogel precursor layer comprises a blend of an electrophilic hydrogel precursor and a protected nucleophilic hydrogel precursor, or a stack of sublayers of each of an electrophilic hydrogel precursor and a protected nucleophilic hydrogel precursor, wherein adjacent sublayers are in direct contact with each other. The protected nucleophilic hydrogel precursor comprises an acidified amine, and the liquid comprises an electrophilic hydrogel precursor and / or a protected nucleophilic hydrogel precursor. The liquid comprises a melt or non-aqueous solution of an electrophilic hydrogel precursor and / or a protected nucleophilic hydrogel precursor.
[0009] In other aspects, the invention relates to a method for using a medical patch, the method comprising:
[0010] One or more medical patches are placed on or in a bleeding defect associated with an organ, wherein the medical patch comprises a biocompatible substrate and an initially dried, substantially non-crosslinked hydrogel precursor layer on the substrate, wherein the layer comprises an electrophilic hydrogel precursor and a nucleophilic precursor as a blend or in the form of multiple stacked sublayers in direct contact with each other.
[0011] In a further aspect, the invention relates to a particle composition comprising a blend of a porous hydrophilic material and a hydrogel precursor, the hydrogel precursor comprising an electrophilic hydrogel precursor having a plurality of electrophilic functional groups and a nucleophilic hydrogel precursor having a plurality of protonated amine groups and no more than about 2 wt % water. Typically, both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncrosslinked and are in the same particle, or in different particles, or a combination thereof. The particle composition can be placed in a hemorrhagic defect where it undergoes gelation.
[0012] In another aspect, the present invention relates to a medical patch, which includes a biocompatible substrate and a hydrogel precursor presenting a surface along one side of the biocompatible substrate, the hydrogel precursor including an electrophilic hydrogel precursor having multiple electrophilic functional groups and a nucleophilic hydrogel precursor having multiple nucleophilic functional groups, wherein the biocompatible substrate includes thermal cross-linked gelatin. The hydrogel precursor at least partially extends into the surface of the biocompatible substrate to form an adhesive hydrogel precursor structure. The adhesive hydrogel precursor structure includes a blended layer and / or a separate adjacent layer of an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor, and the medical patch presents a fractured surface of an adhesive hydrogel precursor.
[0013] In another aspect, the present invention relates to a method for forming a medical patch, the method comprising compressing a structure comprising a biocompatible substrate and one or more hydrogel precursor layers to form a medical patch, wherein the one or more hydrogel precursor layers are melt-coated onto the substrate and present a surface along one side of the biocompatible substrate, wherein the biocompatible substrate comprises foamed gelatin having a ruptured pore structure. The one or more hydrogel precursor layers at least partially extend into the ruptured pore structure of the biocompatible substrate to form a cohesive hydrogel precursor structure, wherein upon wetting with a physiological fluid or a physiological buffered saline, the cohesive hydrogel precursor structure cross-links to form a cohesive hydrogel structure.
[0014] In another aspect, the present invention relates to a method for using a flexible medical patch, the method comprising placing one or more flexible medical patches on or in a target bleeding site, wherein the flexible medical patch comprises a biocompatible substrate and a hydrogel precursor presenting a surface along one side of the biocompatible substrate. The hydrogel precursor comprises an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor as a blend and / or in the form of multiple stacked regions in direct contact with each other, and the biocompatible substrate has a ruptured pore structure. Typically, the hydrogel precursor is initially dried and substantially uncrosslinked, and at least partially extends into the ruptured pore structure of the biocompatible substrate to form an adhesive hydrogel precursor structure, wherein the medical patch is hemostatically adhered to the target bleeding site.
[0015] In another aspect, the present invention relates to a method for forming a medical patch, the method comprising applying a liquid hydrogel precursor to a porous hydrophilic substrate in a dry atmosphere, wherein the application is performed by compressing the substrate at a printing position using a print head to inject the liquid hydrogel precursor into the compressed substrate. The liquid hydrogel precursor comprises an electrophilic hydrogel precursor and a protected nucleophilic hydrogel precursor, wherein the protected nucleophilic hydrogel precursor comprises an acidified amine, wherein the liquid hydrogel precursor comprises a melt or non-aqueous solution of the electrophilic hydrogel precursor and / or the protected nucleophilic hydrogel precursor.
[0016] In another aspect, the present invention relates to a medical patch, which includes a biocompatible substrate and a hydrogel precursor, the hydrogel precursor including a solid blend and / or a separate solid layer of an electrophilic hydrogel precursor having a plurality of electrophilic functional groups and a nucleophilic hydrogel precursor having a plurality of nucleophilic functional groups, wherein both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncrosslinked. The biocompatible substrate includes thermally crosslinked gelatin having a ruptured pore structure, wherein the hydrogel precursor at least partially extends into the ruptured pore structure of the biocompatible substrate to form an adhesive hydrogel precursor structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1A is a perspective view of the structure of a hemostatic patch.
[0018] Figure 1B is a perspective view of the layered hemostatic patch structure.
[0019] Figure 1C is a perspective view of a hemostatic patch structure having a compressed substrate.
[0020] Figure 1D is a perspective view of a hemostatic patch structure having a compressed substrate and an adhesive hydrogel precursor network with a fractured surface.
[0021] Figure 2 is a perspective view of an apparatus for spraying a blended precursor composition onto a substrate to make a hemostatic patch.
[0022] Figure 3A is a side view of an apparatus for slot die coating a blended precursor composition onto a substrate to make a hemostatic patch.
[0023] Figure 3B is with Figure 3A Side view of an apparatus for slot die coating similar to the apparatus in , where the coating head is adjusted to press into the substrate during coating.
[0024] Figure 4A is a side view of an apparatus for continuous roll slot die coating of a blended precursor composition onto a substrate to make a hemostatic patch.
[0025] Figure 4B is a flow chart of a two-step compression process according to an embodiment of the present disclosure.
[0026] Figure 4C is a side view of a process flow for making a flexible hemostatic patch product from a gelatin sheet and a hydrogel precursor composition.
[0027] Figure 4D is a side view of the gap between the calender rolls.
[0028] Figure 5 is a schematic diagram of a hemostatic patch wrapped around a tubular organ.
[0029] Figure 6 is a schematic diagram of a hemostatic patch placed on a non-tubular organ.
[0030] Figure 7 is a schematic diagram of a hemostatic patch placed on the skin.
[0031] Fig. 8A is a cross-sectional view of a hemorrhagic defect in tissue.
[0032] Figure 8B is placed Fig. 8A Cross-sectional view of the hemostatic patch after application on the bleeding defect.
[0033] Figure 8C Adhesion to the bleeding defect Figure 8B Cross-sectional view of a hemostatic patch.
[0034] Fig.8D This is a cross-sectional view of the healing tissue after the hemostatic patch has been absorbed.
[0035] Fig. 9 is a schematic diagram of the Adam scale for defect bleeding scoring.
[0036] Fig. 10A is a photograph of the initial placement of the patch into the channel defect.
[0037] Fig. 10B yes Fig. 10A The photo is shown 1 minute after standing.
[0038] Fig.11 is a graph of force versus time for a representative patch sample evaluated using a commercial texture analyzer.
[0039] Fig. 12A is a schematic diagram of the tapered hemostatic patch being placed into the cervix using a tapered mandrel.
[0040] Fig. 12B is a schematic diagram of a tapered hemostatic patch placed in the cervix, wherein the left inset shows the tapered shaft pressing the patch into the cervix, and the right inset shows the tapered shaft having been removed and the tapered patch remaining in the cervix. In the left inset, only the tapered end of the shaft is shown, and the handle of the tapered shaft is not shown.
[0041] Fig.13A is a perspective view of a flexible hemostatic patch folded in an accordion shape.
[0042] Fig. 13B is a schematic diagram of using forceps to introduce an accordion-folded flexible hemostatic patch into a cannula.
[0043] Fig. 13C is a schematic diagram of a flexible hemostatic patch that is accordion-shaped and folded laterally.
[0044] Fig.13D Schematic diagram of using forceps to introduce an accordion-shaped and laterally folded flexible hemostatic patch into a cannula.
[0045] Fig.14 Schematic diagram of the use of forceps to introduce an accordion-folded flexible hemostatic patch into a laparoscopic surgical site.
[0046] Fig.15A is a SEM image of the cross-linked gelatin substrate.
[0047] Fig. 15B After calendering Fig.15A SEM image of the cross-linked gelatin substrate.
[0048] Fig. 15C is a SEM image of the cross-linked gelatin substrate.
[0049] Fig.15D After calendering Fig. 15C SEM image of the cross-linked gelatin substrate.
[0050] Fig.16A is a SEM image of the surface of the precursor-coated gelatin substrate.
[0051] Fig. 16B is a SEM image of the surface of a precursor coated gelatin substrate after compression with calendar rolls set at a gap of 5 mm.
[0052] Fig. 16C is a SEM image of the surface of a precursor coated gelatin substrate after compression with calendar rolls set at a 2 mm gap.
[0053] Fig.16D is a SEM image of the surface of a precursor coated gelatin substrate after a first compression with a calendar roll set at a 5 mm gap and a second compression with a calendar roll set at a 2 mm gap.
[0054] Fig.17A is a SEM image of a cross section of a precursor-coated gelatin substrate.
[0055] Fig. 17B After calendering Fig.17A SEM image of a cross-section of a precursor-coated gelatin substrate.
[0056] Fig.18A is the first photograph of a precursor coated substrate, where the substrate was not compressed prior to coating.
[0057] Fig.18Bis a second photograph of a precursor coated substrate where the substrate was not compressed prior to coating.
[0058] Fig.18C is a photograph of a precursor coated substrate where the substrate was calendered prior to coating.
[0059] Fig.19 is a graph of average fluid uptake versus time for uncompressed and compressed substrates. DETAILED DESCRIPTION
[0060] Medical patch is formed as the dry layer with hydrogel precursor on substrate, as blend or as the adjacent sublayer of direct contact, wherein causes spontaneous crosslinking to form the hydrogel that can adhere to tissue after hydration with biological fluid.Usually, hydrogel precursor does not need to react with blood or tissue, because any physiological fluid can activate crosslinking, and described crosslinking relates to the reaction of equal or near equal amount of nucleophilic functional group and electrophilic functional group.The processing forming hydrogel precursor layer is usually selected to avoid substantial crosslinking during processing by protecting nucleophilic group and avoiding moisture (even if reactive species is contacted).Processing can include the dehydration melt blend forming precursor, then it can be coated or cast to form described layer, or by coating the non-aqueous solution of blend and removing solvent.The substrate supporting dry hydrogel can be selected to have absorbency, so that substrate further assists the hemostatic function of patch. In addition, the processing of patch and the deposition of hydrogel precursor can be designed to obtain flexible patch, wherein hydrogel precursor material has good adhesion with substrate, and hydrogel precursor material has good cohesiveness (cohesiveness), which presents the surface for adhering to wound in the patch completed.By using flexible and biodegradable substrate, it is possible to realize that patch is placed on the wound of difficult-to-reach position and / or abnormal shape.Contact with tissue during cross-linking process can promote the formation of required adhesive bond, no matter whether any covalent bonding occurs with tissue, no matter whether blood is present.Adopt selected component, patch can be folded and will not fragment, so that they can be delivered and / or folded to insert wound rather than above wound by trocar in laparoscopic surgery.The increase of patch flexibility can be realized by appropriately selecting substrate, and ideal patch can include compressed gelatin sponge, together with the suitable integrated precursor layer that is permeated into compressed sponge.The surprisingly good adhesion of hydrogel precursor layer and surface provides the combination along patch edge, without directly contacting blood or wound. The results of these patches show that the material is also clearly useful as a filler for wounds and the like, which may be formed from a shredded patch (crushed patch) or an equivalently formed material in which the components are individually shredded, crushed or otherwise broken up.
[0061] Gelatin substrate can provide ideal fluid absorption and biodegradation within the appropriate time range.Especially, foamed gelatin satisfies these characteristics, although other porous gelatin forms can have similar characteristics, such as fusion fiber gelatin.However, it has been found that the flexibility of a higher degree of flexibility than the directly available flexibility of these materials is required.Before and / or after the deposition of the precursor material, the compression substrate (such as using calendering) can be ideal for giving a significantly higher degree of flexibility.When using a porous gelatin substrate, the precursor material, as a blend of precursors and / or as a separate precursor, is applied to the surface of the substrate to provide a blended layer and / or separate adjacent layers of an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor.With regard to the bonding strength of the blended layer and / or separate adjacent layers and the adhesion strength relative to the substrate, it is ideal that the coated substrate has both flexibility and mechanical strength, so that the precursor will not be delaminated or peeled off from the dry patch. It has been found that under slight compression, hydrogel precursor (as one or more melts or one or more non-aqueous solutions) is injected into substrate to cause the adhesion of hydrogel precursor and porous substrate to improve, while maintaining the good adhesion of hydrogel precursor. Although the elasticity of substrate can cause recovery of substrate thickness after hydrogel precursor deposition, hydrogel precursor is deposited into substrate with good permeability to provide the good adhesion of hydrogel precursor and substrate, while still presenting the surface of hydrogel precursor on most or all surfaces, to establish the adhesion of patch to tissue surface during use. After hydrogel precursor deposition, can compress structure (such as by calendering) to further improve the flexibility of patch, this can make the surface of precursor broken. The patch structure gained can have required flexibility, while maintaining the good adhesion and adhesion of hydrogel precursor, so that the delamination or peeling of hydrogel precursor can be avoided. Hydrogel precursor has some features of surface layer, but hydrogel precursor also at least partially penetrates into substrate, and therefore has some features of integrated structure. Adhesive hydrogel precursor structure can be adhered to substrate via the diffusion boundary between hydrogel precursor and substrate. Because substrate surface is not smooth in microscopic, the gelatin whisker from substrate can penetrate into the hydrogel precursor existing along substrate surface, and hydrogel precursor can penetrate into and embed in the part of substrate to form the diffusion boundary between hydrogel precursor and substrate in adhesive hydrogel precursor structure.In various cases, hydrogel precursor can be alternatively described as one or more layers, or coating, or presents the adhesive hydrogel precursor structure (or adhesive hydrogel precursor network) on hydrogel precursor surface.Although clear boundary may not separate substrate and hydrogel precursor, hydrogel precursor still presents the surface along substrate, so that when hydrogel precursor is hydrated, patch can adhere to wet tissue.
[0062] The dry layer of hydrogel precursor (such as blend) generally includes the first hydrogel precursor with multiple electrophilic functional groups and the second hydrogel precursor with multiple protonated amine groups (usually primary amine). In particular, nucleophilic amine can be protonated to form cationic ammonium groups, which protect amines from nucleophilic reactions until they are deprotonated. Halides (such as chlorides) or other strong acid conjugated anions can be counterions. Once blend hydration and ammonium groups are deprotonated due to the dilution of acid during hydration, electrophilic functional groups and nucleophilic functional groups can react to form covalent crosslinking. Therefore, in patch products, hydrogel precursors are substantially uncrosslinked, which is further described below. In some embodiments, patch or its part can be degradable. Precursor can be applied as different layers or as a premixed melt. If melt is selected, it is advantageous to use the melting point of the blended precursor so that it remains solid at room temperature, thereby providing maximum storage stability. Precursor blends can include components that are liquid at room temperature, but blends have a melting point higher than room temperature. In principle, precursor blends can be viscous liquids at room temperature, but the resulting patch may need refrigerated storage to ensure storage stability. Patch can be used for implantable applications or for exposed tissue or skin tissue healing. Substrate can be selected accordingly. Patch can be effectively used in hemostatic applications. For hemostatic applications, absorbent substrates are very desirable. Absorbent substrates can be formed by natural materials, such as collagen, gelatin, cellulose or other similar biopolymers, or formed by synthetic hydrogels, such as polymers including polyethylene glycol, polyvinyl alcohol or other water-soluble or water-swellable synthetic polymers or with a combination of biopolymers. Substrates with flexibility and good drapability are generally provided to provide ideal patch properties, or rapidly softened when encountering moisture and become drapable substrates can also provide ideal properties for many applications.
[0063] In some embodiments, the precursor layer does not have the buffer added, and the result clearly shows that the precursor layer gels quickly and well without any buffer. There may be some appropriately selected buffers without destroying the function of the precursor layer. In this case, inorganic buffers may be ideal because they can remain in a separate phase until activated by physiological fluids. Carbon dioxide from air or carbon dioxide present in the laparoscopic environment can be dissolved in water to form carbonic acid, which can provide a small amount of buffering capacity. Carbonic acid evaporates in the form of carbon dioxide, rather than concentrating with the removal of water. The buffer not appropriately selected may be undesirable because it causes the precursor to undergo undesirable premature crosslinking before use or causes crosslinking to be slowed down after being applied to the tissue. Although water is removed from the patch during processing, if there is a buffer of higher pH, a trace of water may still cause some crosslinking, and a more acidic buffer may slow down crosslinking when contacting with a physiological solution (usually with weakly alkaline pH). According to the experience of these polymer systems, usually, in the case of moderately slowing down gelation, phosphate buffers and perhaps other neutral to weakly acidic buffers may be used. There is evidence that patches without buffer can provide ideal performance together with suitable storage stability. Patches that do not significantly add buffer or have an acceptable level of buffer may be more easily described from the perspective of patch function, such as storage stability and gelation speed, which are described in detail below. If buffer is included, they can be placed on substrate, for example, as powder, with a hydrogel precursor layer above them, or if they are compatible with the non-aqueous form of the precursor layer, they are blended into the hydrogel precursor layer.
[0064] Various suitable substrates are described below. It has been found that sponge patches based on gelatin have particularly effective patch properties. If the sponge is compressed to break the cell structure of the sponge, improved flexibility can be obtained using these sponges as substrates. Although the compression of the gelatin cell structure reduces the mechanical strength of the substrate, the substrate becomes significantly more flexible accordingly, while maintaining sufficient mechanical stability, in order to apply the hydrogel precursor layer to the substrate and apply the patch. Although various processing schemes can be used effectively, the two-step compression process produces particularly desirable results. The hydrogel precursor layer can be added after the first compression and before the subsequent compression. The hydrogel precursor penetrates into the broken cell structure of the sponge to stabilize the patch, and the hydrogel precursor layer breaks during further compression, which not only improves the flexibility of the coated substrate, but also promotes and accelerates the hydration of the precursor layer to accelerate the adhesion effect.
[0065] As described in more detail below and clearly illustrated, patch has extraordinary adhesion to wet tissue.Effective manufacturing method is described.Hydrogel is designed to have roughly equal electrophilic functional groups and nucleophilic functional groups, so that complete crosslinking can occur, and it is expected that complete crosslinking occurs between hydrogel precursors, and any precursor does not need to be bonded with the functional group in blood or tissue.Based on the teaching of this area, the strong adhesion of patch in the case of lacking covalent bonds with blood or tissue is surprising result.This improved design provides excellent performance, including for example strong adhesion and rapid gelation, while maintaining a good shelf life.If it is desired to accelerate gelation time, buffer / accelerator solution (such as by backing) can be applied to patch soon after tissue, to further accelerate gelation process.Although buffer / accelerator solution can be added to patch immediately before being applied to tissue in principle, this method may cause gelation too fast, so that good adhesion cannot be obtained.
[0066] Patches are particularly suitable for sealing active leakage or bleeding. In the case of liquid precursors, only when delivered as a spray sealant, such sealing is usually impossible because the precursor is replaced by active fluid outflow. In the case of the sealant based on the patch as the subject of the present invention, manual compression, which is applied as a part of the patch application, can temporarily control the active fluid outflow, and activate the sealant and adhere to the tissue surface, thus forming an effective seal.
[0067] For some wounds, such as those wounds that may have cavities and bleeding is not too serious, inserting broken patch materials can effectively stabilize the wound, wherein the material is cross-linked in place. Medical staff can chop the patch for use by themselves, or can distribute the broken patch material in that form. In order to manufacture broken patch compositions, the patch does not need to be fully formed to produce similar materials. Substrate (such as gelatin substrate) can be chopped, and precursor blends can be formed and crushed / reduced to fine particles. For example, melt blend or solution spray drying / cooling can be directly formed into particle type materials, and if necessary, particle type materials can be further ground or sieved. Then the material of separate chopped / crushed can be mixed for distribution and use. Although the precursor blend formed for crushing may be ideal for rapid gelation / crosslinking, separate precursor powders can be blended as an alternative. The relative amount of component can follow the scope described for patch, although the amount slightly changed can be selected for the commercialization of these embodiments according to clinical experience.
[0068] The particle composition can be prepared by broken patches, which is a blend of porous hydrophilic material and hydrogel precursor, wherein the porous hydrophilic material is the substrate of the patch, and the hydrogel precursor is the dried layer of the hydrogel precursor on the substrate. The blend can be homogeneous or inhomogeneous. In some embodiments, the particle composition is a blend, wherein the porous hydrophilic material and the hydrogel precursor have a separate source. For example, the porous hydrophilic material can be a broken uncoated substrate, or a porous hydrophilic material provided in particle form, such as gelatin particles or gelatin powder. In some embodiments, the porous hydrophilic material can be foam, nonwoven tufted material or nonwoven felt material. Two or more porous hydrophilic materials can be used together. The example of different hydrophilic porous materials includes, for example, a substrate with the same material but with different porosities, pore sizes and / or particle sizes or a substrate with different compositions. Hydrogel precursor can be provided as a blend of electrophilic hydrogel precursor and nucleophilic hydrogel precursor in the same particle, or provided as different particles of electrophilic hydrogel precursor and different particles of nucleophilic hydrogel precursor, or provided as their combination.In some embodiments, the weight ratio of broken substrate / porous hydrophilic material in broken patch composition can be about 5 weight % (wt%) to about 75 weight %, about 7 weight % to about 50 weight % in some embodiments, and about 10 weight % to about 35 weight % in other embodiments.In other embodiments, the weight ratio of broken substrate can be less than 25%, less than 10%.In other embodiments, the particle composition of precursor can be used without any broken substrate, so that the broken patch weight ratio is 0 weight %.It will be appreciated by those of ordinary skill in the art that the other scope of porous hydrophilic material composition in the above-mentioned clear scope is also considered, and these scopes are within the scope of the present disclosure.
[0069] The particle composition can have particles consisting of any combination of porous hydrophilic materials and hydrogel precursors. The particles of different compositions can have average particle diameters different from each other. In one embodiment, the porous hydrophilic material and the hydrogel precursor form a composite material within the particle. In another embodiment, the porous hydrophilic material and the electrophilic hydrogel precursor form a composite material within the particle, and the nucleophilic hydrogel precursor is in separate / different particles. In another embodiment, the porous hydrophilic material and the nucleophilic hydrogel precursor form a composite material within the particle, and the electrophilic hydrogel precursor is in separate / different particles. In another embodiment, the porous hydrophilic material is in the particle, and the composite material of the hydrogel precursor is in separate / different particles. In another embodiment, the porous hydrophilic material, the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are in separate / different particles. The particle composition can be provided as particles of a porous hydrophilic material, the particles being coated with or at least partially coated with one or both of the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor. The coating of one or more precursors can be completed by spraying a melt or solution of one or more precursors. Multiple layers of coating may be applied, such as a layer of one precursor over a layer of a different precursor.
[0070] The particle composition can have a form ranging from powder to small particles to chunky particles, such as particles obtained by chopping substrate or patch. Small particles can have an average diameter of about 0.001mm to about 5mm or about 0.01mm to about 3.5mm. The particle may or may not be approximately spherical, and may be any reasonable shape. The particle composition may also include a developer and / or a therapeutic agent, as described for the patch. The particle composition may be placed on or in a bleeding defect, and pressure may be optionally applied. The bleeding defect may be partially filled or completely filled by the particle composition, or thinly coated with the particle composition. Those of ordinary skill in the art will recognize that the other ranges of the average diameter within the above-mentioned clear range are also considered, and these ranges are within the scope of the present disclosure. If the patch is chopped up for use by medical personnel, the resulting patch fragments may generally have considerable size and shape variations according to the expectations of the medical personnel.
[0071] Because the precursors can be thoroughly mixed, rapid gel formation is possible even if the amines are initially protected. Once the acid protecting groups are neutralized upon dilution with physiological fluid, crosslinking begins. Physiological fluids are generally weakly alkaline, with physiological pH (e.g., plasma) ranging from 7.32 to 7.42 pH units. For PEG-NH 2 Even at neutral water pH, -NH 3 +Part should also be deprotonated to form nucleophilic active form.Therefore, under suitable hydration, patch can gel in less than one minute, and embodiment proves rapid gelation.Due to the chemical property used, patch is usually adhered to any moist tissue surface with physiological solution, and does not need to directly contact blood and / or wound, although it can exist.Patch is designed for fast and predictable efficacy, which can significantly contribute to the implementation of effective medical procedures.
[0072] Can select every kind of precursor composition to form the heat flowable composition that does not decompose, it can be blended into liquid.The heat flowable composition or the blend of two or more kinds of heat flowable compositions can be respectively clean melt or clean melt blend, wherein "clean" refers to the liquid phase composition without adding solvent.Then the melt blend can be applied to substrate and cooled to form patch.Especially, the precursor with polyethylene glycol core forms flowable liquid at relatively low temperature usually.Slot coating, extrusion, screen printing or other suitable coating processes can be used to form coated substrate.In some embodiments, precursor can be dissolved in some organic solvents in which the precursor is suitably stable, such as aprotic polar solvent.The solution of mixed precursor can be applied to substrate (such as spraying), and dried to remove solvent.In alternative embodiments, non-aqueous solvent solution can be used to process precursor, wherein solvent is selected to avoid acidified amine group deprotonation.Precursor solution can be deposited using technology similar to precursor melt.
[0073] Medical patch can be used for wound (as part of surgery) in closed patient body or for wound healing or surgical closure or other various purposes along skin and has important value.Patch of the present invention provides the remarkable advantage of being activated by any physiological fluid, so that contact with blood or tissue is not clearly needed.Therefore, even if a part of patch directly contacts blood or tissue, whole patch can also form effective closure, even along the edge that may not directly contact blood or tissue.For example, absorbent substrate can absorb physiological fluid, and moisten the part of patch with physiological fluid along whole patch surface.And if there is suitable moisture, then any part of patch does not need to directly contact blood or tissue to adhere, therefore, for example, lymph fluid can be effectively activated patch by direct contact or from substrate transfer.Patch can be used for human or veterinary medical purposes.Prepared patch can be free of blood component and human body component.
[0074] The patch can generally have a substrate and a hydrogel precursor layer on the substrate, wherein the precursor layer can be a blend of precursors and / or the sublayer of the same and / or different composition. The substrate can be homogenous, or it can have the structure of a multilayer and / or structured layer. Generally, the substrate is dry when the patch is formed, and the substrate is formed by a biodegradable material, although for some applications, it may be desirable to use a non-degradable substrate. The substrate can be very imbibed, which can help manage blood and other fluids while the hydrogel closes the wound. The patch generally has enough thickness to provide the required mechanical integrity, but will not be too thick, and a patch with appropriate thickness can provide required crosslinking and hydration within the required time period, and degrade within the appropriate time and will not be too bulky.
[0075] Precursors can be selected to be capable of being thermally processed to form a flowable state at an appropriate temperature. For embodiments in which the precursors are blended in a flowable state during processing, the formation of the melt blend should be thermally stable for each precursor. Processing can be performed in a low humidity environment so that the hygroscopic material does not absorb unwanted moisture from the air. Typically, the flow characteristics of the heated precursor composition are strongly affected by the polymer core to which the functional groups are suspended. In particular, precursors based on polyethylene glycol have the advantages of relatively low flow temperatures and acceptance of approved implantable medical products, although other hydrophilic precursor cores can be used.
[0076] In some embodiments, if the precursor is soluble in an appropriate organic solvent that does not cause crosslinking, the precursor can be blended in an organic solution. Various solution coating techniques can be applicable to forming a precursor coating with a solution blend. After forming the coating, the organic solvent can be removed by evaporation to form a dry coating. After drying, similar to the patch formed by cooling the melt, the patch can be packaged in a waterproof bag, etc.
[0077] In order to obtain the required shelf life, suitable handling and processing characteristics and the setting during application, the amine precursor is provided in the form of acid salt / conjugate, and the blended precursor can be free of buffer, or only has a properly selected buffer that does not excessively slow down gelation or make the storage of the patch unstable. The presence of an alkaline pH buffer tends to amplify instability to crosslinking during processing by potentially removing protons from the amine. Although water is avoided during synthesis, it is impossible to obtain extremely low water content for all hydrophilic components. On the other hand, amines are selected to be easily deprotonated when in contact with physiological fluids, so that no buffer is needed to achieve rapid gelation.
[0078] Other hemostatic hydrogel patches are known. For example, fibrin-based patches are available on the market. It is a fibrin-based patch from Baxter. It is also possible to obtain similar powders and syringes based on fibrin that can deliver matrix or other components based on blood. Another method of patch relates to making the hydrogel part in the patch crosslinked to leave unreacted electrophilic groups. Partial crosslinking is provided for solution processing to make the hydrogel precursor layer of patch, and precursor therein intentionally has the functional group ratio (nucleophilic reagent deficiency) that produces a large amount of unreacted electrophilic groups. Unreacted electrophilic groups are intended to react with nucleophilic groups (such as naturally occurring amines) in the blood or tissue at the wound site. The shortcoming of this method is that the patch only adheres to tissue or blood, therefore away from the patch edge of direct wound interaction, and the position that may not occur to be in direct contact with blood or tissue, may cause part of the patch to adhere and / or bad patch adhesion. Polyoxazoline copolymers have been used to describe the hydrogel based on this method as the core of functionalized precursors. Referring to the disclosed U.S. Patent Application 2019 / 0231923 entitled "Cross-Linked Polymers and Implants Derived From Electrophilically Activated Polyoxazoline" of Hoogenboom et al., it is incorporated herein by reference. These cross-linked polymers based on polyoxazoline are described as adhesives, and are not explicitly described as hydrogels. In contrast, hydrogels described herein originate from the fact that all or substantially all of them are cross-linked after application, and are not dependent on the reaction of other nucleophiles provided with tissue or blood or patents to cross-link, although some reactions of the precursor of the present invention and blood or tissue may occur. Even if the hydrogel precursor of this patch only reacts effectively with itself, they still achieve excellent adhesion.
[0079] Polyethylene glycol-based (PEG-based) hemostatic patches are marketed under the trade name Veriset TM (Medtronic). It is believed that Veriset TM The invention relates to the technology described in published U.S. Patent Application 2010 / 0100123A (the '123 Application) to Bennett, entitled "Hemostatic Implant," which is incorporated herein by reference. These patches involve separate precursor components. In contrast, the methods herein involve blended or intimately contacted hydrogel precursor components that can rapidly form a highly cross-linked homogeneous hydrogel that contacts the patient. Due to the mixing or intimate contact of the uncross-linked precursors, the hydrogel can rapidly gel to form a homogeneous hydrogel with good mechanical stability, good adhesion, and predictable properties. Another hemostatic patch is marketed under the name HEMOPATCH with a PEG-based NHS hydrogel precursor.TM Sold by Baxter International, Inc. (IL, USA). The precursor coating in HEMOPATCH is designed to crosslink with amines in tissue and blood.
[0080] Generally, the patch of the applicant herein includes substrate and hydrogel precursor layer.The crosslinking of the hydrogel precursor layer after being placed on the tissue site plays the effect of adhering the patch to the position.The substrate is usually adhered to the precursor layer, and can be used to promote the hydration and stability of the patch in use, especially in the case of hemostasis.For this reason, the substrate usually has high absorbency and porosity, while maintaining mechanical integrity.In this way, the substrate can absorb fluid (such as blood), to help the position of the stabilizing patch, and help to make the hydrogel hydrate to drive crosslinking, while not too porous to make the substrate surface adhere to the blood through the substrate, such as adhering to gauze or surgeon's gloves.Substrate absorbability can be evaluated according to swelling, and the substrate can form a hydrogel, but the hydrogel does not show further crosslinking after hydration.The porosity of the substrate usually allows some penetrations of the hydrogel precursor to the adjacent substrate surface.
[0081] In the hydrogel precursor layer of the patch of the present invention, two kinds of precursors for cross-linking can be mixed in a dehydrated state or formed as a sublayer in the precursor layer. The amine group is in a protonated acidic state. The precursor layer can be effectively free of buffer, to support relatively more rapid cross-linking when hydrating with physiological fluids. The precursor layer is stable in a suitable time period under dry storage, for product distribution with a commercially suitable shelf life. Of course, the precursor can include trace amounts of anionic pollutants, but the appropriately pure precursor should eliminate any quality problems. One or more amine end group precursors can be used, and one or more reactive precursors to nucleophilic end groups can also be used to form a patch as described herein.
[0082] Cross-linking reaction involves nucleophilic amine and appropriate group reaction to carry out addition reaction.Addition reaction is usually carried out at a reasonable rate under higher pH value (usually pH 7 or higher).In the case of not using activation solution, the deprotonation of amine can occur relatively quickly after hydration with physiological solution, and then allow cross-linking reaction to occur in a short time (e.g. <3 minutes).The results in the embodiment confirm rapid gelation.Because the precursor is mixed or closely contacted in the dry patch, the reactive cross-linking group can be near, without the need to participate in a large amount of movement of cross-linked macromolecular precursor molecules.As described and illustrated below, the initial uncross-linked precursor can gel quickly to induce the adhesion of the patch.Usually, it is not necessary to use high pH buffer to induce gelation at an appropriate rate, and such high pH buffer (such as borate buffer) may promote shortening the storage time.Low pH buffer (such as phosphate-based buffer) usually prolongs gelation time, but these buffers of appropriate amount may not slow down gelation with unacceptable amount.Low pH buffer may not adversely change the storage time. If desired, to speed up reaction time, an additional external higher pH buffer may be applied to the patch after placement on the patient for a particular application, but this is not required.
[0083] The substrate for supporting the hydrogel precursor can be absorbent, which can provide several advantages. First, it can absorb fluid (such as blood, lymph, etc.), so that it can help medical professionals manage wounds when applying patches. In addition, the absorption of physiological fluids by absorbent substrates can help hydrogel precursor hydration. Therefore, absorbent substrates can accelerate gel time, which can be less than one minute. Substrate is generally biodegradable, although in some embodiments, substrate can be non-degradable within the relevant time range, such as in some applications related to external applications of patches. In the case of envisioning external use patches, backing substrates may not be biodegradable, and patches can be removed after healing is completed, or the hydrogel formed by the precursor in contact with the tissue may be absorbable, so that the patch substrate is released after a few days. In particular cases, it may be advantageous to deliver the hydrogel itself, and in such a case, a non-porous backing substrate may be used so that it can release the hydrogel on wet tissues, without adhering to the hydrogel itself. In such applications, the substrate made of a polymer substrate (such as polytetrafluoroethylene, polyethylene, polyurethane, etc.) showing low adhesion to the hydrogel precursor may be useful. Release layers of adhesive bandages and the like may be suitable for this purpose.
[0084] For most hemostatic applications of patch, it is desirable that substrate is biodegradable to nontoxic decomposition products within a reasonable time period, to be removed from the patient. Substrate can absorb body fluids ideally and engage with the infiltration precursor layer. Although various natural and artificial materials (usually polymers) can provide these characteristics, it has been found that gelatin sponge materials perform particularly well in patch structures. In order to achieve required flexibility levels, gelatin sponge can be compressed so that the gelatin cell structure is broken, and the precursor layer can be infiltrated into the broken cell structure to form a complete and stable structure with required absorption characteristics.
[0085] Gelatin is a hydrolyzate of collagen, a major component of the extracellular matrix of animals. Collagen is typically harvested from a variety of livestock. In its native form, collagen is an insoluble fibrous protein. Hydrolysis breaks down the protein polymer chains into smaller units, allowing the resulting gelatin to be processed. The exact properties of the gelatin can depend on the processing. But generally, gelatin is soluble in hot water and some other polar solvents. To return gelatin to being insoluble, gelatin can be cross-linked to control specific properties. To avoid the use of toxic chemicals for cross-linking, sufficient cross-linking can be achieved by heating. To form an absorbent substrate, gelatin is formed into a sponge with a cellular structure. The foamed gelatin cellular structure can be formed without cross-linking.
[0086] The formation of gelatin sponges is known, which are then typically stabilized by chemical crosslinking. See, for example, published U.S. patent application 2007 / 0077274 (the '274 application) to Ahlers, entitled "Method for Producing Shaped Bodies Based on Crosslinked Gelatin," which is incorporated herein by reference. The '274 patent relates to previous crosslinked gelatin products that were not sufficiently durable for certain applications. The crosslinked gelatin is formed using a pore former, such as air, to provide a sponge structure with pores. The product in the '274 patent is still biodegradable. Gelatin sponges are commercially available for use as hemostatic materials. For example, gelatin sponges are available from Gelita AG (Germany, applicant for the '274 patent) and Ethicon (USA). Uncrosslinked gelatin sponges can be obtained. Gelita and Ethicon sell gelatin sponges as hemostatic patches, i.e. (Ethicon) and (Gelita).
[0087] While chemical cross-linking may be desirable for longer persistence, chemical cross-linking may involve the use of toxic chemicals or other components that may be undesirable in terms of biodegradation of the material and may result in the material being too persistent. Chemical cross-linking may also change the mechanical properties of the substrate, making it more brittle. On the other hand, completely uncross-linked gelatin may decompose too quickly before hemostasis is achieved and thereby result in a loss of absorbency for body fluids. Thermal cross-linking may achieve the desired balance of properties without the introduction of chemicals that may complicate biocompatibility. As described in the '274 patent, thermal cross-linking of gelatin may result in dehydration, which may form cross-linked bonds. Thermal cross-linking is further described below.
[0088] Prior work has shown that compressing gelatin sponges can increase flexibility. The '274 application discusses "mechanical action," including by rollers, to increase the flexibility of cross-linked gelatin sponges. They suggest that the density increases by a factor of 2 to 10, but the mechanical properties of the material after mechanical action are not described, except that the reference indicates that dissolution over time is not affected without providing data. Published U.S. Patent Application 2021 / 0213157 (the '157 application) by DeAnglis et al., entitled "Flexible Gelatin Sealant Dressing With Reactive Components," describes the use of a compressed gelatin substrate with a hydrogel precursor, which is incorporated herein by reference. The '157 application talks about compressing the gelatin preferably after cross-linking. Accordingly, the '157 application mentions that the compressed gelatin sponge is stronger due to the higher cross-linking density (caused by the amine groups of the protein being physically closer), although the '157 application indicates that cross-linking is optional. The '157 application does not appear to indicate the possibility of thermal cross-linking.
[0089] The '157 application references a prior published U.S. patent application that teaches the association of a hydrogel precursor with an absorbent substrate, see U.S. Patent Application 2011 / 0045047 to Bennett et al., entitled "Hemostatic Implant" (incorporated herein by reference), which appears to be a follow-up to the '123 application referenced above. The '157 application points out the undesirable aspects of the earlier work and points to an alternative approach of using a powder of a dry precursor deposited on a porous substrate.
[0090] The '157 application exemplifies the use of commercial substrate materials, particularly Product codes 1974 and 1975 (which are said to be compressed), and Gelatin film. The '157 application does not describe the detailed properties of these substrates, and no specific further processing is performed before the hydrogel precursor is applied. As described above, the precursor is added as a fine dry powder, which is a blend of 4-arm PEG-SG (succinimidyl glutarate) (MW 4000Da), 4-arm PEG-amine (MW = 3,000Da) and sodium bicarbonate powder. The powder is applied as a suspension using an organic solvent, which is then allowed to evaporate. The powder precursor lacks the advantages of the solid precursor layer described herein.
[0091] It is believed that commercial gelatin sponges for hemostatic purposes are generally chemically cross-linked, for example, with aldehydes (such as formaldehyde or glutaraldehyde) to stabilize the structure so as to have a reasonable duration in contact with biological fluids. As mentioned above, the '157 application uses a commercial substrate from Ethicon, Inc., and there is no detailed information about the production or specific characteristics of the substrate except for the size. As described herein, processing involves a coating process to form a continuous precursor layer, which is designed to be stable and uncross-linked until activated by body fluids or water. Then, the precursor layer and the substrate exhibit a synergistic relationship, wherein the precursor layer can stabilize the substrate, and the hydrogel precursor penetrates into the substrate to stabilize the hydrogel precursor from delamination or peeling.
[0092] In the processing of the applicant, the compression of the patch structure is carried out after applying the hydrogel precursor layer. The compression step usually breaks or crushes the precursor layer formed, thereby forming microcracks and / or cracks across the surface. Microcracks and / or cracks are consistent with the increased flexibility of the resulting patch. Whether or not the part along the patch is in direct contact with the wound, the hydrated patch becomes adhered to the tissue. Gel sponge can include additives, such as plasticizers and possible other agents, and if the patch material is not too elastic, so that compression causes the thickness to be reduced more together with less rebound after compression, it is considered that the improvement of the mechanical properties of the patch is greater. Then the cell structure of the gel sponge breaks, which can further promote hydration and improve flexibility. Except for compressing after placing the precursor layer, the gelatin patch can also be compressed before applying the precursor layer. Initial compression can promote the precursor layer to penetrate into gelatin, while maintaining the surface of the precursor layer.
[0093] In order to improve the adhesion of hydrogel precursor to porous gelatin substrate, it has been found that hydrogel precursor can be deposited on the substrate of slightly compressed state.Printhead can be adjusted to provide required deposition configuration.Porous gelatin substrate can have certain elasticity, so the moderate compression during hydrogel precursor layer may not cause the continuous change of substrate thickness.However, being deposited on substrate under compression force seems to cause hydrogel precursor to be more penetrated into substrate.The obtained patch structure shows the adhesion and cohesiveness of hydrogel precursor of required degree, thereby reduces or eliminates any peeling or delamination of hydrogel precursor from dry patch.The obtained hydrogel precursor structure presents the surface for applying to wound, wherein the surface is completely or at least significantly covered by hydrogel precursor, even if it is broken.The hydrogel precursor structure can be referred to as one or more layers, or is expressed by the term of reflecting that it penetrates into substrate to form the cohesive hydrogel precursor or coating with more complex structure, such as cohesive hydrogel precursor structure, cohesive hydrogel precursor network or cohesive network, which are used interchangeably in this article.
[0094] In principle, the compression of gelatin sponge can be carried out in various ways, such as placing the patch between two plates and fastening it to the structure. A convenient way of applying compression is to pass the patch through a calendering roller. The spacing of the calendering roller can be set to achieve the required compression. From the perspective of process flow method and applying shear force to break the precursor layer, it is also convenient to use a roller to compress. Rollers can be applied repeatedly to gradually achieve the required compression. Relative to passing a roller later with a precursor layer, the first compression without a precursor layer can be carried out at a larger roller spacing.
[0095] For hydrogel precursor layer, protected nucleophilic precursor generally has acidified amine group.For example, amine can react with strong acid (such as hydrochloric acid), and chloride ion or other corresponding conjugate base can keep associating with precursor.Amine acidification stabilizes precursor layer by suppressing cross-linking reaction until amine can be deprotonated.By this precursor selection, the obtained patch can be stable for a long time in dry storage.Nucleophilic precursor generally has multiple functional groups, and three or more groups can allow more highly cross-linked structure.Nucleophilic precursor can have hydrophilic core, it can be highly branched and have side hanging amine group.Low pH buffer can not make acidified amine group unstable.
[0096] Electrophilic precursors have electrophilic groups that can react with amines to form covalent crosslinks. Electrophilic groups typically react only with amine groups and do not react with protonated amine groups or ammonium acid conjugates. Electrophilic precursors have multiple functional groups and can form highly crosslinked hydrogels with three or more functional groups. Electrophilic groups are typically suspended from a hydrophilic core (such as polyethylene glycol) that can be appropriately branched to form a desired degree of crosslinking.
[0097] Electrophilic precursors and protected nucleophilic precursors can be designed to have a flow temperature lower than the decomposition temperature of any precursor. Therefore, melt blends can be formed with two compounds. Melt blends can be formed into a good mixture. Then the melt blend can be processed to form a patch. If the precursor layer includes a sublayer, these sublayers can be applied to each other in sequence. The sublayer can include a blend of precursors or one of the precursors. Generally, processing can be performed under low humidity conditions to reduce any moisture absorption from the surrounding atmosphere. The melt blend can be directly formed into a coating for a patch, although the melt blend can be cured in principle for subsequent processing. For example, the melt blend can be slit coated on a substrate, although other processing techniques such as extrusion, screen printing, spraying, etc. can be used. Slit coating or other coating techniques can be performed on a substrate sheet for effective processing. After the coating is cured, the coated sheet can be cut into the desired patch size. Alternatively, a coating can be formed on a pre-cut patch substrate. Patches can be distributed using appropriate packaging to keep a dehydrated state.
[0098] In some embodiments, the precursor can be dissolved in an inert organic solvent. Suitable solvents can be aromatic liquids, such as toluene, xylene, dimethyl carbonate, etc., or aprotic solvents. Typically, as long as the fluid properties allow for appropriate processing, the solution can be highly concentrated to reduce solvent use. The coating method for solvent-based deposition can generally be the same as that for melt blends, and the concentration can be appropriately adjusted according to a specific deposition method.
[0099] The components of the patch tend to be hydrophilic and / or hygroscopic. Therefore, the components after synthesis or purchase can be dried / dehydrated before processing to form the patch. Some substrates can be lyophilized. In some embodiments, it is desirable to obtain a hydration level no more than 5% by weight or significantly lower. Processing can be carried out in a controlled atmosphere of dry air, nitrogen, etc., while applying heat and vacuum. Processing can include a purge technique, which uses a limited inert dry gas stream together with the heat under a partial vacuum to enhance drying. Conditions for reducing moisture can be provided. After forming the patch, it can be packaged in a moisture-proof package under dry air. The patch can be sterilized, for example, using ethylene oxide gas during packaging or using radiation after packaging. Sterilization can be carried out without causing a large amount of cross-linking.
[0100] Hydrogel patches described herein are particularly suitable for use as implantable hemostatic patches, which can be absorbed after a reasonable period of time in a few days to a month or longer. Hydrogel patches can be used to control bleeding or to seal the wounds of open surgery or laparoscopic surgery. Hydrogel patches can be used for any wound healing situation generally, including superficial placement, rather than implantation placement. Rapid closure, good adhesion and adjustable absorption time provide desirable features for a range of applications.
[0101] Patch structure and hydrogel precursor
[0102] Hydrogel precursor patch described herein generally includes a hydrogel precursor layer (as a blend or sublayer) on a substrate and a substrate surface, although generally with some penetrations into the substrate. The substrate suitable for the required patch application can be selected. Generally, the substrate is absorbent, and the substrate can be in situ absorbed within a reasonable time period of contact with the patient. The patch can be suitable for implantation in the patient, and for these embodiments, the substrate is generally absorbable. The precursor is generally substantially uncrosslinked and blended in the layer. The layer can be uniform on the substrate, or variable. Select the precursor to be relatively quickly crosslinked when exposed to physiological solutions or tissues. The patch can be suitable for use as a hemostatic patch, which helps to control and limit bleeding.
[0103] In the patch before use, the hydrogel precursor in the layer on substrate is not cross-linked substantially. Accurate quantification may be impractical, but the clear meaning of concept and the satisfaction of these conditions are very clear. First, chemical design makes it impossible to expect cross-linking, because the amine group is protected by the acid modification for blocking nucleophilic reaction. Significant cross-linking causes various precursor molecules to be connected into a network structure. Under a certain degree of cross-linking, the material no longer has an independent precursor molecule, and basically becomes a material bond connected together by a covalent bond. This process is evaluated in the case of gelation, and the bond can be referred to as the resulting gel, which is a hydrogel in this case. When the cross-linking degree of the hydrogel precursor increases over gelation and towards complete cross-linking along with other time, the gel becomes stronger and becomes stable. For example, as described below, gelation time (or gel time) can be measured. On the contrary, in the middle time before gelation, along with the occurrence of some cross-links, characteristics change, which changes the behavior of the composition. If the precursor is substantially uncrosslinked, the properties of the fully hydrated precursor do not change significantly, and the flow characteristics and rheology of the precursor composition do not change measurably relative to the formed uncrosslinked composition, although these properties may change rapidly once crosslinking is allowed to begin.
[0104] Figure 1AThe structure of an embodiment of a hemostatic patch is shown.Hemostatic patch 100 has substrate 102 and precursor layer 104.Substrate 102 can be a gelatin substrate or other suitable substrates as described below.For example, substrate 102 can be a gelatin substrate without adding blood components (such as fibrinogen or thrombin or platelet).In some embodiments, substrate 102 is porous and has absorbency.In other or alternative embodiments, substrate 102 is biodegradable.Usually, substrate is relatively thin, such as average thickness is no more than one centimeter, and the area of patch can be appropriately selected according to specific application.
[0105] Precursor layer 104 can be a blend of an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor. Alternatively or additionally, precursor layer 104 can be constructed as a sublayer of an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor, which may or may not include a blend, but generally has an interface of an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor along a sublayer. In some embodiments, a sublayer applied to a substrate in liquid form forms a single homogeneous layer on the substrate after cooling and / or drying. In other embodiments, the sublayer forms a continuous layer with a composition gradient. Figure 1B An alternative structure of a hemostatic patch is shown. Hemostatic patch 150 has substrate 152 and precursor layer 154. Precursor layer 154 is constructed as a stack of sublayers 160 and 164. Sublayers 160 and 164 are in direct contact with each other. In some embodiments, sublayer 160 is a sublayer of an electrophilic hydrogel precursor, and sublayer 164 is a sublayer of a nucleophilic hydrogel precursor. In other embodiments, the composition of the sublayer is opposite, and sublayer 160 is a sublayer of a nucleophilic hydrogel precursor, and sublayer 164 is a sublayer of an electrophilic hydrogel precursor. In some embodiments, precursor layer 154 is constructed as three or more alternating sublayers, such as sublayer 160 / sublayer 164 / sublayer 160, wherein adjacent sublayers are in direct contact with each other. As used throughout this article, direct contact between hydrogel precursors means accidental or unintentional contact of the substantial surface area of the corresponding components not only involving the layer extension dimension, and usually this will involve layer-by-layer interaction. The multiple sub-layers may have the same thickness or different thicknesses. In some embodiments, the precursor layer 104 / 154 has an imaging agent so that the precursor layer 104 / 154 is visually distinguishable from the substrate 102 / 152. In a preferred embodiment, the precursor layer 104 / 154 has a blue or green coloration due to the presence of a dye.
[0106] Figure 1CAnother structure of a hemostatic patch is shown. Hemostatic patch 170 has a compressed substrate 172 and a precursor layer 174. Typically, compressed substrate 172 is porous and absorbent. In some embodiments, precursor layer 174 penetrates into the porous structure of compressed substrate 172. Precursor layer 174 can be prepared by the same composition as described above for precursor layer 104 and / or precursor layer 154 or have the same sublayer structure. In some embodiments, precursor layer 174 has cracks, such as microcracks and / or cracks. Figure 1D Another structure of a hemostatic patch is shown.Hemostatic patch 180 has a compressed substrate 182 and an adhesive hydrogel precursor structure 184, which has a fragmentation surface 186. Typically, the adhesive hydrogel precursor structure 184 has a precursor material embedded in a substrate material, while presenting a surface located on one side of the compressed substrate 182. In some embodiments, the surface area of the compressed substrate 182 associated with the adhesive hydrogel precursor network 184 is completely coated with a hydrogel precursor blend. Typically, the compressed substrate 182 is porous and absorbent. Typically, the hydrogel precursor has good adhesion in the adhesive hydrogel precursor structure 184, so that even if the surface is broken, the fragmentation and loss of the precursor material are also resisted. Typically, the hydrogel precursor in the adhesive hydrogel precursor structure 184 has good adhesion to the compressed substrate 182. In some embodiments, the features of good adhesion and / or good adhesion can be that the adhesive hydrogel precursor structure 184 resists peeling during processing and / or further processing. The present invention relates to the present invention and the method for preparing the adhesive hydrogel precursor structure 184.Processing and / or further processing can include calendering, such as to cause the crushing of the surface 186 of adhesive hydrogel precursor structure 184, and the processing after forming the patch relates to, for example, bending, folding, packaging and / or transportation.Usually, the compressed substrate region 183 relative to the adhesive hydrogel precursor structure 184 does not contain hydrogel precursor.Adhesive hydrogel precursor structure 184 can be prepared in the following manner: the blend of electrophilic hydrogel precursor and nucleophilic hydrogel precursor is applied to porous hydrophilic substrate (such as cross-linked gelatin substrate), or a single precursor is applied as an adjacent layer, and the adjacent layer can be blended to a certain extent during application, but still adjacent along the patch region.In some embodiments, porous hydrophilic substrate has a ruptured pore structure.
[0107] In some embodiments, the application of the precursor material is performed using a porous hydrophilic substrate under compression, such as using a print head, to inject the hydrogel precursor into the substrate. In some embodiments, the adhesive hydrogel precursor structure 184 has a surface that conforms to one surface of the substrate 182. In other embodiments, the adhesive hydrogel precursor structure 184 has a surface that extends beyond the surface of the substrate 182 opposite the compressed substrate area 183. The hydrogel layer 174 ( Figure 1C) extends beyond the surface of substrate 172, and can be considered as an embodiment of adhesive hydrogel precursor structure 184. In some embodiments, porous substrate is prepared by calendering before printing. In some embodiments, adhesive hydrogel precursor structure 184 has cracks, such as microcracks and / or cracks. Compressed substrate 172 / 182 can be a cross-linked gelatin substrate. In some embodiments, compressed substrate 172 / 182 is a hole-shaped sponge substrate. In some embodiments, compressed substrate 172 / 182 is a compressed gelatin substrate, such as formed by compressing rigid and / or cross-linked gelatin substrates. In additional or alternative embodiments, compressed substrate 172 / 182 is biodegradable. Typically, hemostatic patch 170 / 180 is relatively thin, such as an average thickness of no more than one centimeter, and is relatively flexible. The thickness, width and length of the patch can be appropriately selected according to a specific application. Figure 1A , 1B , 1C and 1D are presented as separate diagrams and do not mean that features of the different diagrams cannot be appropriately combined or interchanged under the general discussion in this article.
[0108] The size of the hydrogel precursor patch can be selected to be suitable for appropriate applications. In addition, the total thickness is divided into substrate thickness and hydrogel precursor thickness. In this paragraph and the next paragraph, size refers to the size of the dry patch, and the swelling from hydration is further discussed below. The area of the patch is usually not particularly limited, and can be selected according to the desired position of the patch. For commercial applications, different sizes can be allocated for user selection. The actual limit is usually recommended to be no more than 20 centimeters (cm) × 20cm for the patch area of human patients, although larger patches can be used, and in these values, any smaller range can be selected, such as 5cm × 5cm, 10cm × 5cm, 2cm × 4cm, etc. Conventions may recommend specific sizes for specific applications. Different sizes can be sold for medical professionals to select the desired size. Usually, the patch can also be cut into a size suitable for a specific situation encountered using instruments available in an operating room environment.
[0109] The thickness of patch can depend on the ability and absorption time that balance makes patch bend to conform to the ability of application site and the fluid of absorption required amount.Thicker patch may be not too flexible, and may need longer time to hydrate and degrade, and thicker patch can absorb more blood and other fluids simultaneously.Similarly, thinner patch absorbs less usually, may be more flexible, and may degrade faster, thereby shortening the duration.The cross-linked hydrogel precursor layer provides all or most of the adhesion of patch usually during the initial application of patch.Substrate can be selected to provide a large amount of fluid absorption.In some embodiments, patch can have the dry average thickness of about 0.25mm to about 10mm, can have the dry average thickness of about 0.3mm to about 9mm in other embodiments, can have the dry average thickness of about 0.35mm to about 8mm in further embodiments, and can have the dry average thickness of about 0.4mm to about 6mm in other embodiments. Substrate 102 / 152 / 172 / 182 can have the average dry thickness of no more than about 10mm, can have the average dry thickness of about 0.2mm to about 8mm in some embodiments, can have the average dry thickness of about 0.25mm to about 7mm in further embodiments, and can have the average dry thickness of about 0.3mm to about 5.5mm in other embodiments. Precursor layer 104 / 154 / 174 can have the average thickness of about 25 microns to about 2mm, can have the average thickness of about 30 microns to about 1.75mm in further embodiments, and can have the average thickness of about 40 microns to about 1.5mm in other embodiments. Precursor layer can be partially penetrated into substrate. In some embodiments, a large part of precursor layer will be retained on the top of substrate, to present the dry precursor layer for patch application. In order to evaluate average precursor layer thickness, it can be measured by the precursor load (g / cm 2 ) divided by the former density (g / cm 3) to calculate the average thickness, or by applying the precursor layer on a non-porous substrate and measuring the dry average thickness (because the relative dense characteristics of the precursor layer should not be substantially changed by the substrate) and accurately estimated. Although the patch can generally have these ratios of substrate and hydrogel precursor coating thickness, it is desirable in some embodiments that the dry substrate is at least as thick as the dry hydrogel precursor layer, at least about 60% in further embodiments, 65% to 95% in some embodiments, and about 70% to about 90% of the dry patch thickness in other embodiments is the substrate thickness. For ease of measurement, the substrate thickness includes any hydrogel precursor that penetrates into the substrate. Those of ordinary skill in the art will recognize that the additional ranges of size and thickness in the above-mentioned clear range are also considered, and these ranges are within the scope of the present disclosure. Typically, a hydrogel precursor layer can be added without significantly damaging the porous, absorptive properties of the substrate material.
[0110] More generally, except gelatin-based substrates, in principle, the substrate suitable for patch can be formed by natural materials, synthetic materials or their combination. Synthetic materials for absorbent substrates include, for example, polyesters, polyurethanes, high molecular weight polyethylene oxide (PEO) or other reasonable synthetic polymers. Absorbable polyesters include, for example, polylactic acid, polyglycolic acid or its copolymers. High molecular weight PEO can be slowly dissolved in water. Natural materials are usually processed appropriately to be included in medical products, so they are usually modified to varying degrees by their natural forms. Nevertheless, natural materials can provide the desired characteristics suitable for substrates, including high absorption rates to aqueous solutions and degradation within a reasonable time period in in vivo applications. Suitable natural materials include, for example, polysaccharides and materials derived from extracellular matrix proteins. For example, polysaccharides as derivatives of cellulose, pectin, hyaluronic acid or chitosan can be used to manufacture absorbent sheets. Commonly used materials are cellulose forms including, for example, esters and ether derivatives (such as cellulose acetate or ethyl cellulose). Oxidized cellulose is a material that helps to stop bleeding, but this material is generally considered to be poorly absorbable and can cause postoperative complications, while hydroxycellulose, nitrocellulose or other forms are suitable.
[0111] Collagen is an extracellular matrix protein that in its native form can be found in three-chain fibrils. Purified collagen can take various forms, and gelatin is a partially hydrolyzed form of collagen. If desired, collagen can be derived by other means. Highly absorbent and resorbable collagen sponges have been developed, and these can be used alone as hemostatic elements. For example, commercial forms are marketed by Becton, Dickinson and Company under the trademark Avitene TM MCH and Avitene TMUltrasponge is sold. Gelita Medical GMBH sells gelatin (based on collagen) hemostatic materials that can provide a basis for patch substrates. Custom substrates can be formed as follows: use commercially available medical grade collagen or gelatin (e.g., from Gelita Medical or other suppliers), which are formed into sheets, optionally cross-linked (such as glutaraldehyde cross-linked), and dried (such as freeze-dried). Although cross-linking can stabilize collagen, strong chemical cross-linking can significantly increase the duration.
[0112] Gelatin can be cross-linked thermally and / or chemically, such as using formaldehyde or glutaraldehyde, to mechanically stabilize the material suitable for the substrate. Gelatin is a hydrolyzed form of collagen. The length of the thermal cross-linking affects the duration again. Although not wanting to be limited by theory, it is believed that thermal cross-linking can affect the cross-linking of adjacent suitable groups in the structure. In contrast, chemical cross-linking can form a more complex cross-linked structure, which can provide significant entropy stability. Sufficiently extended chemical cross-linking can produce essentially permanent / non-degradable materials. For decades, chemically cross-linked collagen has been used for prosthetic tissues, heart valves and other prostheses. Before thermal cross-linking, gelatin is placed in a desired shape and then heated, such as in an oven, etc. Typically, thermal cross-linking can be carried out at a temperature of about 100°C to about 200°C and at a temperature of about 120°C to about 180°C in a further embodiment, for a time of about 15 minutes to about 4 hours, and in a further embodiment, for about 25 minutes to about 3 hours. Those of ordinary skill in the art can adjust the time and temperature to achieve the desired characteristics, such as porosity and mechanical stability and the duration after implantation in vivo, which is further discussed below. Using heat cross-linked gelatin materials, the substrate can be a foam, a nonwoven tufted material, or a nonwoven felt material. One of ordinary skill in the art will recognize that additional ranges of temperature and time within the explicit ranges above are also contemplated and are within the scope of the present disclosure.
[0113] Commercial gelatin sponges are available, wherein gelatin is foamed, and may or may not be chemically cross-linked. The gelatin sponges illustrated in the embodiments are foamed and uncross-linked commercial materials. The use of uncross-linked gelatin avoids concerns about the release of potentially toxic chemicals for cross-linking. The resulting foamed gelatin material has a porous structure with a sponge-like cell structure. Density and pore size can be adjusted by processing parameters. Commercial materials can be designed to have appropriate absorbency to absorb fluid at the wound. Although it is found that compression of gelatin substrates significantly improves flexibility, it is found that absorbency does not change significantly. Absorbency can be evaluated as follows: the sponge is placed in a certain volume of saline, and the weight can be evaluated after the sponge is immersed and reaches a steady state (plateau phase) of liquid absorption. For denser substrates, the steady state of swelling may take a long time to reach, and for highly porous gelatin sponges, the steady state may be reached faster, usually reaching most of the swelling after about 10 minutes. Although it is possible to wait longer to measure after reaching a steady state of swelling, if necessary, measurements can be taken after 24 hours to easily capture swelling, but swelling measurements should be performed before the hydrogel significantly decomposes. For highly foamed gelatin sponges, a large part of swelling can occur in less than a minute, and denser substrates may not reach a plateau in a significantly longer time. Substrates typically absorb at least about 100% of their dry weight of liquid, at least about 150% in some embodiments, at least about 200% in further embodiments, at least about 250% in other embodiments, and at least about 350% in additional embodiments, and typically biocompatible substrates can absorb water in the range of 100% to 2500% by weight relative to the weight of the dry patch. Typically, the initial uncompressed volume provides a rough upper limit of the solvent swelling weight, and allows some swelling. In some embodiments, the compressed substrate (without the hydrogel precursor layer) can absorb at least about 80% of the liquid compared to the uncompressed substrate, and in further embodiments can absorb at least about 90% of the liquid compared to the uncompressed initial substrate, and in some embodiments at least about 92.5%, indicating that the possible swelling of the compressed substrate is close to its uncompressed value. In an embodiment, the compressed substrate absorbs more than 98% of the liquid relative to the uncompressed substrate material. Those of ordinary skill in the art will recognize that additional ranges within the above explicit ranges are also contemplated and are within the scope of the present disclosure.
[0114] Regarding the improved flexibility after compression, it can be evaluated relative to the corresponding substrate material that is not compressed. Although a thinner uncompressed material may be more flexible than a thicker version, its absorbency is reduced by the thickness change and the corresponding mass loss. Therefore, it is appropriate to compare versions with approximately the same absorbency. Since flexibility also depends on the initial thickness of the substrate and the material used to form the substrate, it may not be particularly meaningful to try to quantify the improved flexibility. The substrate flexibility can be qualitatively compared by winding the substrate on a mandrel, in which case a more flexible substrate can generally be wound on a narrower mandrel without breaking. Therefore, in some embodiments, the compressed substrate can be bent around a mandrel with parallel folded sides and a diameter of 5 mm. However, the compressed substrate may lose mechanical strength. For the force of bending the material, the force (bending strength) is reduced, so the material can be bent or folded more easily. The columnar strength is reduced, so squeezing the two opposite sides crushes the material with less force, which is reasonable because the bubbles have been broken. The hydrogel precursor layer provides mechanical stability for the compressed substrate without significantly reducing the flexibility along the axis parallel to the calendering roll due to cracks in the hydrogel precursor layer.
[0115] The compression of substrate can be carried out in one or more compression stages. In particularly interesting embodiments, at least the last compression is carried out after the precursor layer is added to the top of the substrate, and at least one compression step is carried out before the precursor layer is deposited to provide the greater permeability of the precursor layer while leaving the top surface of the precursor layer. Subsequent compression steps can be carried out in a manner that the compression thickness gradually decreases, although due to some responsiveness of the material, subsequent compression can be carried out with the same or possibly slightly wider compression thickness. The initial gelatin sponge thickness provides a basic parameter for the final assembly structure, as modified by processing, which jointly determines the characteristics. The spacing of the final compression is generally no more than about 85% of the initial substrate average thickness, no more than about 65% in some embodiments, no more than about 55% in some embodiments, and in further embodiments is about 20% to about 50% of the initial average substrate thickness. In some embodiments, the lower limit of the compression range can be 5%, 10%, 15%, 20%, 25% or 30% and the upper limit can be 85%, 75%, 65%, 60%, 55%, 50% or 45%, and the range can include any one of these lower limits and any one of these upper limits. Although the substrate material can have some rebound from compression, it is desirable that at least about 40% of the compression step is maintained (rebound does not exceed about 60%), so compression from 2mm to 1.5mm will involve rebounding to a final average thickness of no more than about 1.8mm, making the gelatin less elastic, although in some embodiments, the rebound can be 100%, without net compression. Typically, the rebound rate can be from about 0% to about 100%, from about 10% to about 90% in some embodiments, and from about 15% to about 80% in other embodiments, and from about 20% to about 70% in other embodiments. Those of ordinary skill in the art will recognize that other ranges of relative compression and rebound rates within the above-mentioned clear ranges are also considered, and these ranges are within the scope of the present disclosure.
[0116] Although in principle various methods are suitable for applying compression, the use of calendering rollers and the like provides shear in addition to compression, relative to, for example, the use of flat plates. The shearing along the edges passing through the rollers applies additional forces to break the cellular structure of the sponge. In particular, when the hydrogel precursor layer is on a substrate, the shearing tends to break the hydrogel precursor layer, which further contributes to flexibility and faster hydration when in contact with body fluids. The nature of the cracks generally depends on the amount of compression as well as the material properties, but the cracks or fissures may or may not run through the entire thickness of the hydrogel precursor layer. Although the precise characterization of the cracks is not particularly appropriate because the crack locations are random, in some embodiments, there are typically visible cracks within every square centimeter of the finished structure. Calendering rollers are also particularly ideal for continuous production process flows.
[0117] Calendering rollers and related conveying systems are well known in various industrial environments. Calendering rollers have been widely used in polymer processing and food processing, and some equipment can be shared between different industries. For convenience, pasta rollers are used in the embodiments. Typically, commercial calendering rollers have adjustable thickness. Multiple calendering rollers can be placed in series to perform sequential calendering steps, such as with reduced thickness, although other production configurations can use the same calendering rollers in sequence, where appropriate adjustments are made between runs. As mentioned above, a hydrogel precursor layer can be formed before a calendering step (such as the last calendering step). The formation of a hydrogel precursor layer is described in detail below. Although roll-to-roll processing can be performed in principle, foamed gelatin is usually formed into a block or other fixed shape, which can be cut into a desired size (including thickness). Therefore, a process system can be designed to process gelatin sponge sheets. In some embodiments, the sheet can be relatively large, for subsequent cutting into separate patches for packaging. If the sheet is cut into separate sheets, this allows the edge portion of the larger sheet to be discarded, and the edge portion may have less uniformity according to process considerations.
[0118] Because the component of patch tends to be hydrophilic and / or hygroscopic, therefore can be processed to form patch before described component drying / dehydration.Suitable drying technology can comprise for example vacuum drying, heat drying, desiccant drying, lyophilization etc. or its combination.It is desirable to make hydration level be no more than the water of 5 % by weight, in further embodiment be no more than the water of about 3 % by weight, in further embodiment be no more than the water of about 2 % by weight, or significantly lower in some embodiments.Water-content can be determined by coulometric titration (Karl Fischer) or loss on drying method.It will be appreciated by those of ordinary skill in the art that other scope in the above-mentioned clear and definite scope of water-content is also considered, and these scopes are within the scope of the present disclosure.
[0119] The hydrogel precursor can be selected to provide the required absorption and cross-linking when in contact with physiological fluids, while remaining stable as a coating during storage under dry (usually refrigerated) conditions to have an appropriate shelf life, such as at least two months and in some embodiments at least about six months. The nucleophilic group can be a protonated amine, wherein the protonated form of the acidic amine is protected from cross-linking reactions. Suitable electrophilic groups cross-link when the unprotonated amines are in contact in the same phase, whether eutectic in a mixture or dissolved in a solvent, which typically has a pH of at least about 7.1, which deprotonates the initially protonated amines.
[0120] With respect to buffers, regardless of whether the hydrogel precursor changes pH and could in principle provide some buffering functionality, it is not considered a buffer. The amine precursor is provided in an acidified form, where the acidic proton acts as a protecting group that blocks cross-linking. Upon contact with body fluids at physiological pH, the acidified amine can be deprotonated, allowing it to cross-link with the electrophilic precursor. The layer of uncross-linked precursor may not include any significant added buffer, and ideal patch performance is found without added buffer. The buffer can be considered any Bronsted base, which will generally be an anion (B) corresponding to a weak acid (HB). - ). Anions corresponding to strong acids, such as halide anions, do not act as aqueous buffers, and the amine precursor is typically provided as an HCl salt or similar strong acid analog.
[0121] Generally, pH is used to control the cross-linking reaction, and amine is provided in an acidified form, which inhibits cross-linking. Therefore, avoiding high pH buffer in the precursor layer avoids any premature cross-linking reaction by activating via a buffer. When physiological fluids penetrate into the patch during use, the pH changes caused by the physiological fluids rapidly deprotonate amines and induce cross-linking. Because the precursors are mixed or directly contacted in the dry patch, the precursors can be rapidly cross-linked and have a relatively high initial cross-linking density, to provide good adhesion, without waiting for a longer time to achieve more complete cross-linking. Gel time is further described below.
[0122] In hydrogel systems, it is advantageous to use functional groups suitable for crosslinking monomers to form adhesive patches in situ, including monomers, typically macromonomers as indicated below, which contain electrophilic groups that show activity to amine functional groups. Therefore, multi-component hydrogel systems can be spontaneously crosslinked when components are activated by contacting with physiological fluids, but two or more components are appropriately stable in a reasonable process time before being activated by physiological fluids. Such systems include monomers (usually but not necessarily macromonomers) of amines with difunctional or multifunctional numbers in one component, and macromonomers with electrophilic groups with difunctional or multifunctional numbers in another component, such as parts containing N-hydroxysuccinimide esters. N-hydroxysuccinimide ester functional groups promote the formation of amide bonds in the reaction with amines, and have been used in other medical hydrogels, although other suitable electrophilic precursors are described below. N-hydroxysuccinimide esters are usually suspended on the hydrophilic core.
[0123] The hydrogel precursor may have crosslinking activated by the physiological fluid contacted by the precursor after delivery. The hydrogel precursor described herein may be designed to hydrate relatively quickly. The hydrogel and precursor solution properties are further described below. The parameters affecting the properties include: functional group chemical properties, crosslink density / molecular weight of the monomer, monomer composition, substrate composition and patch structure.
[0124] The cross-linking density of the obtained biocompatible cross-linked polymer is controlled by the total molecular weight of macromonomer and the available functional group quantity of each molecule.Compared with higher molecular weight (such as 10,000Da), the lower molecular weight (such as 600Da) between cross-linking gives higher cross-linking density.The higher molecular weight macromonomer with significant branching provides ideal gelation time, and in some embodiments exceeds 2500Da, thus obtains elastic gel.In specific embodiments, the molecular weight of parent nucleic acid conjugated polymer (with amine) is not significantly less than electrophilic polymer.In some embodiments, it has identical size (size) or larger size.
[0125] Cross-linking density can also be controlled by the ratio of nucleophilic group and electrophilic group in mixed precursor material.For dry solid precursor layer, gel time depends significantly on hydration time, because cross-linking reaction can occur in water, and because amine deprotonation can be used for nucleophilic substitution.Rapid hydration substrate can help dry hydrogel precursor hydration, and the size of hydrophilic core in precursor molecule can affect hydration time.Although do not want to be limited by theory, it is believed that longer gel time can be diffused into the patch of original position placement slowly with physiological fluid and / or acid conjugate species diffused out slowly from the patch of original position placement.Another method of controlling cross-linking density is by adjusting the stoichiometry of nucleophilic functional group and electrophilic functional group.The 1:1 ratio of electrophilic group and amine group should provide the highest cross-linking density, although the electrophilic group in precursor can react with amine in principle in the protein in physiological solution and in tissue.In an embodiment, the functional group ratio of 1:1 is used to obtain desirable performance.
[0126] monomer
[0127] Monomers that can be cross-linked to form biocompatible structures (e.g., implants) can be used. As described above, monomers can be macromonomers, which can or may not be polymers. As used herein, the term "polymer" means a molecule formed by at least three repeating groups, which molecule can then have a reactive functional group suspended on the polymer. Typically, the term "reactive precursor material" means a polymer, functional polymer, macromolecule or small molecule that can participate in the reaction to form a cross-linked molecular network (e.g., hydrogel). As described above, for the formation of a rapidly cross-linked hydrogel precursor system, monomers are typically (but not necessarily) macromonomers, as indicated below, because macromonomers typically allow more rapid hydration and more rapid deprotonation of amines.
[0128] Monomers may include, for example, biodegradable water-soluble macromonomers described in U.S. Pat. No. 7,332,566 (hereinafter referred to as the '566 patent) to Pathak et al., entitled "Biocompatible Crosslinked Polymers With Visualization Agents," which is incorporated herein by reference. These monomers are characterized by having at least two polymerizable groups and may or may not be separated by at least one degradable region. After crosslinking, the product polymer forms a cohesive hydrogel that persists indefinitely or until eliminated by degradation, which may involve, for example, enzymatic reactions or hydrolysis. Typically, the macromonomer forms a core of a water-soluble and biocompatible polymer, such as a polyoxyalkylene, such as polyethylene glycol, which may be flanked by a hydroxycarboxylic acid, such as lactic acid, to form a degradable ester or a non-degradable amide. In addition to being biocompatible and nontoxic, suitable monomers may also have at least some elasticity after crosslinking or curing. For electrophilic compounds or compounds with amine groups, the core of the compound can have multiple arms or branches, each arm or branch having a functional group suitable for cross-linking. PEG-based polymers with three or more arms are typically star polymers with a branched core and extended PEG polymer arms. As described above, monomers based on polyethylene glycol (PEG) are established medical hydrogel precursors, and precursor compounds with various arm numbers, molecular weights, and functional groups are commercially available.
[0129] Nucleophilic functional groups are usually amine groups. Amine groups can be protonated in the form of protecting groups or gates to control crosslinking. The nucleophilic amine groups of the precursor can be designed to be significantly deprotonated at physiological pH values (such as about 7.1 to about 7.6 pH units), although blood and tissues are generally in a narrow pH range in healthy individuals. Although macromolecular monomers are exemplified and provide the required properties, trilysine has been used as a polyamine monomer in medical hydrogels, and similar compounds can be used. Electrophilic functional groups can be selected to react with amines to form crosslinks. N-hydroxysuccinimide esters are ideal electrophilic groups, although other suitable groups are described below. One or both of the functional groups can be suspended on the hydrophilic core, which can help provide the required liquid swelling when hydrated. In some embodiments, the polymer can have a part or bond (connection) that can be biodegraded by hydrolysis, such as esters, carbonates or other suitable bonds, although enzymatic degradable bonds can be present additionally or alternatively. Several such bonds are well known in the art and are derived from alpha-hydroxy acids, their cyclic dimers (anhydrides) or other chemicals used to synthesize biodegradable moieties, such as glycolide, dl-lactide, l-lactide, caprolactone, dioxanone, trimethylene carbonate or copolymers thereof. In particular, electrophilic monomers can conveniently provide degradable bonds.
[0130] Typically, the monomers providing electrophilic functional groups and the monomers providing amine groups are macromonomers to provide more rapid hydration of the dried precursor layer. The macromonomers typically have a biologically inert and water-soluble core with pendant reactive functional groups for crosslinking. When the core is a water-soluble polymer region, the polymer that can be used can be a natural polymer or a synthetic polymer. Suitable polymers for the core can include polyethers, such as polyoxyalkylenes, such as polyethylene glycol ("PEG"), polyethylene oxide ("PEO"), polyethylene oxide-co-polypropylene oxide ("PPO"), co-polyethylene oxide block or random copolymers; poloxamers, such as F-127; and polyoxazoline, polyvinyl alcohol ("PVA"); poly(vinyl pyrrolidone) ("PVP"); and polysaccharides such as hyaluronic acid, chitosan, dextran or digested cellulose, and their derivatives. Based on extensive experience with existing medical products, star-branched polyethers and more specifically polyethylene glycol (also known as poly(oxyalkylene) or poly(ethylene oxide)) are particularly suitable. Acidified amines or electrophilic groups can be located at the end of the arms of each branch or a portion thereof. For PEG precursors, in the field of medical hydrogels, a common notation involves the number of arms and the molecular weight and the functional groups on the arms, such as 4A15K NH 2-HCl for a 4-arm PEG with a molecular weight of 15,000 Daltons and an acidified amine with a chloride ion, or 8A20K NHS ester for an 8-arm PEG with a molecular weight of 20,000 Daltons and an N-hydroxysuccinimide ester functional group.
[0131] PEG-based hydrogels have been widely used in medical products. Therefore, they are widely accepted and PEG monomers with various functionalities are commercially available in medical grade forms. Polyoxazolines have attracted attention as potential ideal substitutes for PEG-based products. Poly(2-oxazoline) has the structure -(CH 2 CH 2 N(COR))-, where the R group can be H, an alkyl group, or other functional group. Amine terminated poly(2-ethyl-2-oxazoline) is available from Sigma-Aldrich. Terminal functional monomers do not allow crosslinking, but multifunctional electrophilic monomers with three or more functional groups can achieve crosslinking. The synthesis of poly(2-R-2-oxazoline) having 25% side chains with N-hydroxysuccinimide (NHS)-ethyl groups is described in published U.S. patent application 2019 / 0125922 to Bender et al., entitled "Tissue-Adhesive Porous Hemostatic Product," which is incorporated herein by reference.
[0132] It has been determined that the hydrogel formed by the macromers with longer distances between the cross-linking points is generally softer, more compliant, and more elastic. Therefore, in the polymer of the '566 patent, increasing the length of the water-soluble segment (such as polyethylene glycol) tends to enhance elasticity. As used herein, the molecular weight of the hydrophilic macromer (such as the macromer with the polyethylene glycol macromer core) is generally at least about 2,000Da, about 2500Da to about 500,000Da in some embodiments, about 5,000Da to about 250,000Da in other embodiments, about 7500Da to about 100,000Da in further embodiments, about 10,000Da to about 50,000Da in other embodiments, and about 15,000Da to about 40,000Da in other embodiments. The PEG precursors located in the lower part of these molecular weight ranges may be liquids. As used herein, molecular weight (mass) employs conventional units, which may be equivalently Daltons or molar mass-grams / mole (assuming the presence of natural isotopes in either case), and for polymers, if there is any molecular weight distribution, the molecular weight is usually reported as an average value. One of ordinary skill in the art will recognize that additional ranges within the above explicit ranges are also contemplated, and these ranges are within the scope of the present disclosure.
[0133] The hydrogel precursor in the hydrogel precursor solution has a certain ratio of electrophilic functional groups and amine functional groups. The ratio of functional groups can change the crosslinking density and properties of the resulting hydrogel. Generally, if the number ratio of electrophilic functional groups to amines is one to one, the hydrogel can be completely crosslinked in sufficient time and without restrictions. In some embodiments, the ratio of nucleophilic functional groups to electrophilic functional groups is not less than 1. Generally, the ratio of electrophilic functional groups to nucleophilic functional groups can be about 0.8 to 1.2, and in further embodiments, about 0.9 to about 1.1, in further embodiments, about 0.95 to about 1.05, in other embodiments, about 0.98 to about 1.02, in other embodiments, about 0.99 to about 1.01, and in some embodiments, about 0.995 to about 1.005, although the ratio can be about 1: 1. Those of ordinary skill in the art will recognize that other ranges of ratios within the above-mentioned clear ranges are also considered, and these ranges are within the scope of the present disclosure.
[0134] In order to achieve the desired functional group ratio, the functional groups can be distributed in various ways. The side hanging functional groups extending from the core can be referred to as being associated with the arms of the precursor. The precursor generally has 2, 3, 4, 5, 6, 7, 8, 9, 10 or more arms. At least one precursor generally has at least 3 arms to obtain crosslinking, and 4-arm, 6-arm or 8-arm precursors can be conveniently used to obtain the desired hydrogel properties. In order to obtain a one-to-one functional group ratio, if they have the same number of arms, equimolar amounts of precursors can be used, or if there are different numbers of arms on each precursor, the molar ratio can be adjusted accordingly. Therefore, two times the molar amount of 4-arm precursors can be combined with 8-arm precursors to obtain a 1:1 functional group ratio. For weight ratio, the molar ratio can be adjusted accordingly based on relative weight, and for 8-arm 10K MW (10,000 molecular weight) precursors, it will be combined with twice the mass of 8-arm 20K MW precursors to obtain a 1:1 functional group ratio. Those of ordinary skill in the art can adjust these calculations to obtain functional groups with different number ratios.
[0135] Functional groups and cross-linking reactions
[0136] Cross-linking reaction is usually designed to occur when hydrating with aqueous fluid, which is essentially a physiological fluid in the body surrounded by physiological conditions, although medical procedures may involve some local dilution or changes of physiological fluids, such as using disinfectants or other program emergency means, which start from its pure natural state without changing the basic processing of hydrogel precursors. In order to help hydration, the substrate can be wetted before the patch is applied to the tissue, as further explained below. Unless otherwise clearly stated, the reference to physiological fluids herein may involve slight changes to natural fluids due to medical procedures. Therefore, cross-linking reaction "in situ" occurs, meaning that they occur in local locations, such as organs or tissues in living animals or human bodies. Due to the in situ nature of the reaction, cross-linking reaction can be designed not to release the polymerization heat of undesirable amounts. The gelation time of the desired procedure is described above, and complete cross-linking can be completed usually after 2 minutes to 10 hours, although other times outside this range may also be acceptable. Longer complete cross-linking time may begin to compete with degradation time.
[0137] Certain functional groups (such as alcohols or carboxylic acids) do not usually react with other functional groups (such as amines) at physiologically acceptable pH. However, by using activating groups, such as N-hydroxysuccinimide or its derivatives, these functional groups can be made more reactive. Generally, several methods for activating these functional groups are known in the art. Suitable activating groups include, for example, carbonyl diimidazole, sulfonyl chloride, chlorocarbonate, aryl halide, sulfosuccinimide ester, N-hydroxysuccinimide ester (NHS), succinimide ester, succinimide amide, epoxide, aldehyde, maleimide, imidoester, etc. N-hydroxysuccinimide ester or N-hydroxysulfosuccinimide group is an ideal group for cross-linking amine functionalized polymers (such as amino-terminated polyethylene glycol ("APEG")), because they have been recognized in medical implants and have been used for a long time in approved products. A further extensive discussion of medical hydrogels in general is disclosed in US Pat. No. 7,332,566 to Pathak et al., entitled "Biocompatible Crosslinked Polymer With Visualization Agents," which is incorporated herein by reference.
[0138] Suitable nucleophilic functional groups are polymers with primary amines conjugated to acids. Therefore, another functional group for cross-linking is generally an amine. Amines are weak bases. In some embodiments, the acid conjugate is HCl, and an amine (such as PEG amine) HCl salt is formed. Acid conjugates can be selected to match the approximate molar concentration of amines. The advantage of the NHS-amine reaction is that the reaction kinetics lead to rapid gelation, usually within about 10 minutes, more usually within about 1 minute, and most usually less than 30 seconds. The gelation time may be limited by the hydration time of the dry hydrogel precursor. Protonated amines are generally not suitable for nucleophilic substitution. Therefore, the precursor blend can be prepared at a suitable pH to maintain substantially protonated amines before delivery to contact with physiological solutions.
[0139] The cross-linking density of the resulting biocompatible cross-linked hydrogel is controlled by the total molecular weight of the monomer and the number of functional groups available for each molecule. Compared with a higher molecular weight (such as 100,000Da), a lower molecular weight (such as 2000Da) between cross-links will give a higher cross-linking density. A higher molecular weight monomer can be used to obtain a more elastic hydrogel, while a correspondingly lower molecular weight monomer can be used to obtain a less elastic hydrogel. Different applications may mean that the hydrogel has different characteristics.
[0140] Another method of controlling cross-link density is by adjusting the stoichiometry of nucleophilic functional groups and electrophilic functional groups. A one-to-one ratio can result in the highest cross-link density. Typically, over time, the hydrogel completes solidification so that the available cross-linking sites form cross-linked bonds. If electrophilic and nucleophilic groups are provided in equal equivalent amounts, it can be expected that almost all functional groups form cross-linked bonds after complete solidification. Two types of reagents of equal quantity (or reaction equivalent) generally provide the highest cross-link density. If different functional group ratios are used, the properties of the cured hydrogel may be correspondingly different. The cross-link density can depend on the number of functional groups on the precursor molecule and the ratio of the precursor molecule. If desired, the non-stoichiometric ratio of electrophilic and nucleophilic groups can be used to change the cross-link density. The ratio of functional groups is further described above.
[0141] Degradable or non-degradable bonds
[0142] Generally, it is desirable that patch is degradable, and in some embodiments is relatively rapidly degradable. Therefore, if the patch is implanted, they will not continue indefinitely. In order to degrade the patch, both the substrate and the hydrogel formed in situ are degraded. According to application, it may be desirable or undesirable that the hydrogel is degradable, such as by hydrolysis or biodegradation due to enzymatic activity, although for hemostatic patches, patches are usually designed to be rapidly degraded, so they will not last for a long time after stable coagulation. If it is desired that the biocompatible cross-linked hydrogel polymer is degradable or absorbable, one or more precursors having degradable bonds between functional groups can be used. As used in the art, if absorbable polymers are absorbed under physiological conditions, then whether they are degraded by biological action (such as enzymatic cleavage), they can be referred to as biodegradable. Degradable bonds can also be optionally used as a part of the water-soluble core of one or more precursors. Alternatively or additionally, the functional group of the precursor can be selected so that the reaction product between them produces degradable bonds. For each method, degradable bonds can be selected so that the resulting degradable biocompatible cross-linked hydrogel polymer degrades or is absorbed within a desired time period. In other embodiments, functional groups and bonds (links) with functional groups can be selected to resist degradation under physiological conditions, thereby significantly reducing or eliminating the absorption of the patch.
[0143] Typically, degradable bonds are selected so that the hydrogel is degraded into non-toxic products under physiological conditions for removal from the patient by natural means. Exemplary enzymatically hydrolyzable biodegradable bonds include peptide bonds that can be cleaved by metalloproteinases or collagenases. Other exemplary biodegradable bonds can be functional groups on core polymers and copolymers, such as hydroxycarboxylic acids, orthocarbonates, anhydrides, lactones, amino acids, carbonates, phosphonates, or combinations thereof. In an exemplary embodiment, the degradable bond is an ester formed by a hydroxycarboxylic acid moiety adjacent to an electrophilic group for crosslinking. Esters can be gradually degraded by hydrolysis under physiological conditions, wherein the duration depends on the specific structure. In order to obtain non-degradable hydrogels, esters formed by hydroxycarboxylic acid moieties can be replaced by amide groups that are generally not hydrolyzed under physiological conditions. Monomers with PEG cores are commercially available, having N-hydroxysuccinimide electrophilic groups attached with amide bonds or alternatively ester bonds, for example from Jenkem Technology, TX, USA. PEG-amines can also be obtained from Jenkem, with various arm numbers and molecular weights. Desirable degradable electrophilic groups include, for example, N-hydroxysuccinimidyl succinate (SS), N-hydroxysulfosuccinimidyl succinate, N-hydroxysulfosuccinimidyl glutarate, succinimidyl glutarate (SG), succinimidyl adipate (SAP), succinimidyl azelaic acid ester (SAZ) or mixtures thereof. Examples of rapidly degradable patches with SS linking groups are described below. Mixtures of degradable bonds and non-degradable bonds (such as the above-mentioned amides) can be used to adjust the duration, for example to form oligomeric species to be cleared by the body.
[0144] Hydrogel and patch properties
[0145] The evaluation of patch properties can be carried out in vitro under specific conditions, so that properties are independent of biological conditions. Such evaluation helps to describe patch characteristics, which is very important for actual in vivo use. In this article, we have described the measurement of gel time, swelling, substrate porosity, burst strength and duration, and have carried out corresponding measurements in the example. However, for the patch performance evaluation in the actual program, scheme can be used to provide the appropriate restriction of patch behavior under the test conditions of simulated hemorrhagic tissue, thereby providing repeatable background for patch evaluation. The following example shows the result of in vitro test, which is wherein compared with the actual use of animal model. For dry patch, the density of patch (substrate and precursor layer) can be about 0.075g / cm 3 To about 0.5g / cm 3 For a single precursor layer, the density may be about 0.050 g / cm 3 About 0.450g / cm 3One of ordinary skill in the art will recognize that additional ranges of density within the explicit ranges above are also contemplated and are within the scope of the present disclosure.
[0146] The gel time of the sample patch can be evaluated in a laboratory environment, which provides an appropriate estimate for in vivo performance. The embodiment has been measured for a specific sample. A commercial texture analyzer is used to evaluate the gel time. Texture analyzers are available from Texture Technologies Corp. / Stable Microsystems, Ltd. (such as model TA-XT Plus) and Brookfield Technologies (such as model CTX texture analyzer). These systems are designed to analyze food and soft medical materials. First, the instrument is calibrated according to the standard procedure of the instrument using a standard test block. The TA-005 probe (Texture Technologies) with a 1 / 4 inch diameter and a flat surface (alternatively hemispherical) can be used with a 5kg load cell. The sample holder is heated to 37°C to track the standard body temperature. The sample holder is a non-porous polymer foam block with a 1.5mm hole cut in the middle. The 8mm diameter stamped sample from the patch is placed on it with the sample holder hole as the center, with the precursor layer facing down. To begin the test run, the tester is started and 67 microliters (μl) of 37°C buffer solution (pH 8.0) is added to the 8 mm punch sample to the center of the test sample. The texture analyzer can be programmed accordingly to meet these parameters. The force required to deform the patch by 0.4 mm is determined as a function of time.
[0147] The graph as a function of time yields a characteristic curve. The patch is in a dehydrated state at the beginning and is hard, so the initial force is relatively high. Over the course of a few seconds, the patch will hydrate and the force reaches a minimum. It can be expected that crosslinking begins during hydration and early processing is performed. As crosslinking continues, the force begins to increase, indicating that crosslinking has reached a level that makes the material strong. The time when the force begins to increase is considered to be the gel time, which marks the gelation point at which the gel begins to become strong. In these systems, the use of the patch involves hydration, during which the solid precursor is hydrated and begins to crosslink. Therefore, the dissolution of the precursor is offset by crosslinking. As hydration begins, the solid softens until crosslinking is fully carried out, starting to make the hydrogel strong. The gelation process has different characteristics from a solution-based hydrogel system that begins with a dissolved precursor. After gelation begins, as crosslinking continues, the force continues to increase. Three equivalent stampings from the same patch were measured three times, and the results were averaged. For the patches described herein, the gel time is generally no more than about 5 minutes, in further embodiments from about 3 seconds to about 3 minutes, in some embodiments from about 4 seconds to about 2 minutes, and in other embodiments from about 5 seconds to about 1 minute. One of ordinary skill in the art will recognize that additional ranges of gel times within the above explicit ranges are also contemplated, and these ranges are within the scope of the present disclosure.
[0148] The bursting pressure of patch samples can also be tested, and these values are ideal for ensuring that samples have the desired performance in actual use. The bursting pressure measurement is intended to provide standard test conditions related to patch adhesion to bleeding tissue. As mentioned above, some patches can be formed with compressed gelatin substrates, and the substrate ideally provides a more flexible structure and / or a more uniform substrate surface, while maintaining sufficient rigidity to resist the warping / deformation of the substrate during coating. The results presented in the following embodiments show that the patch with compressed gelatin substrate exhibits approximately the same bursting pressure. Experience so far shows that the patch with compressed gelatin substrate exhibits more uniform performance. As described after the bursting test description, the same sample can then be used to evaluate swelling. The bursting test can be evaluated on a device designed to simulate bleeding tissue, and the device is suitable for measuring according to ASTM F2392-04 (2015). The ASTM scheme provides information related to the test fixture surface, which is then adjusted to be used with the porous plate of the test device. It is believed that there is no commercial version of such a test instrument, but for the patch test used clinically, the corresponding test will be very ideal. Therefore, taking into account and complying with the above ASTM protocol, a similar test device with regulatory implications was built into the design, as further described in the Examples below.
[0149] For test, use calibrated syringe pump, wherein 60ml syringe tube is filled with saline and pump is set to 2ml / min.Use burst fixture, its cavity is connected to syringe pump, wherein cavity top has circular opening.Pressure sensor (such as digital pressure gauge) is also connected to cavity, to measure the pressure in cavity.In order to start test, syringe pump is used to fill cavity, until cavity is almost full.The test block with the patch sample in gel test is placed on the hole on fixture top, wherein patch stamping sample is upward.Similarly, also can similarly use the hydration patch pressed on test block, but use the patch after gel test to provide uniformly prepared patch to carry out burst test.In this configuration, the hole in sample holder is located at the center of burst fixture cavity.Then the upper half of fixture is fastened on test block, to fix sample holder, wherein hole is connected with cavity, cavity extends through the upper half of fixture, exposes sample from top.Once top fixture fixes test block, the pressure measured on expected pressure gauge increases.
[0150] After fixture and top are fixed in place, start pump so that water is pumped into cavity to continuously increase the pressure in cavity.Pump runs until 1) liquid appears on patch sample surface, 2) popping sound is heard, or 3) maximum pressure recorded on pressure gauge does not change in 30 seconds.Once condition has been reached, pump stops, and the maximum pressure value obtained is recorded as bursting pressure, recorded in units of millimeters of mercury (mmHg).For patch sample as described herein, bursting pressure can be at least about 10mmHg, at least about 15mmHg in a further embodiment, at least about 50mmHg in a further embodiment, and about 20mmHg to about 1500mmHg in other embodiments.It will be appreciated by those of ordinary skill in the art that the other scope of bursting pressure in the above-mentioned clear and definite scope is also considered, and these scopes are within the scope of the present disclosure.
[0151] After hydration, both substrate and precursor layer swell. Although swelling can be evaluated in principle in several reasonable ways, swelling is evaluated in this article by the weight produced by water retention. For embodiments based on compressed substrates, swelling based on weight may not change significantly, so the evaluation of overall swelling may be roughly unchanged relative to similar patches assembled on uncompressed substrates. The dry weight of the patch before testing can be used as an initial reference point. Finally, swelling can be evaluated based on incubation with aqueous fluids, but over a long period of time, the patch material may degrade. In essence, swelling described herein is evaluated in a sufficiently long period of time, so that swelling reaches a stable state after incubation in 37°C of phosphate buffered saline, for denser substrates, this can be after about 24 hours, or for highly foamed gelatin sponges, this can be about ten minutes. The sample for evaluation can be the same sample for other characteristic measurements, and this uses the unsubmerged weight of hydration as a reference point to provide a consistent swelling valuation. If swelling is assessed directly from a dry sample, air can be squeezed out of the sample in the early stages of swelling to achieve proper measurement without significant delay. In some embodiments, the sample at the end of the burst test can be used to further evaluate swelling. After the burst test is completed, the sample can be carefully removed from the sample holder. The sample is then weighed to obtain the initial weight. The weighed sample is then placed in a 50ml tube containing approximately 45ml phosphate buffered saline (PBS) and sealed. PBS is a standard buffer for medical and other biological applications and typically contains sodium chloride, some potassium chloride and phosphate. PBS is available from standard suppliers (FisherScientific, Sigma-Aldrich, etc.) and is classified in PubChem (https: / / pubchem.ncbi.nlm.nih.gov / compound / Phosphate-Buffered-Saline). The sealed tube is placed in a 37°C water bath. After 24±2 hours, the tube is removed from the water bath. Then, the incubation sample is taken out, patted dry and weighed. The value of the swelling percentage is determined by the following formula:
[0152] % swelling = 100 x (output weight - input weight) / input weight.
[0153] The value of "input weight" can be dry weight or weight corresponding to an alternative reference point, such as weight after burst test. For the patches described herein, swelling (from after burst test to incubation in PBS for 22-26 hours) can be at least about 100%, in further embodiments about 135% to about 350%, and in other embodiments about 150% to about 300%. Those of ordinary skill in the art will recognize that additional ranges of swelling within the above specific ranges are also contemplated, and these ranges are within the scope of the present disclosure.
[0154] Although the substrate has a high swelling weight, it is initially porous, so the volume swelling may be weak. If the substrate is initially compressed relative to its initially formed dimensions due to cell rupture, swelling may restore some or most of the original dimensions of the structure. The hydrogel precursor is initially dense, so upon crosslinking and swelling, the volume change of the crosslinked hydrogel is generally more significant. Therefore, after hydration and swelling, the volume increase of the hydrogel layer may be more significant than the substrate volume change.
[0155] Another important characterization is the persistence (persistence) of the patch. In vitro measurements can be performed to obtain consistent measurement results to simulate in vivo behavior. The persistence of substrates and related cross-linked hydrogel layers can be different from each other. The persistence behavior of substrates can be evaluated by continuing the swelling test. Specifically, the sample loaded into the tube containing PBS can be kept in a 37°C hot bath until the substrate of the patch sample is no longer visible. The time when the sample substrate disappears is considered to be the end of the substrate duration. Usually, the substrate disappears in no more than 96 hours, disappears in no more than about 84 hours in a further embodiment, and disappears in about 15 minutes to about 72 hours in another embodiment. In some embodiments, it is ideal for the substrate to disappear in no more than about 48 hours. Those of ordinary skill in the art will recognize that the other scopes of the degradation time within the clear range are also considered, and these scopes are within the scope of the present disclosure. Usually, the hydrogel formed in situ lasts longer than the substrate.
[0156] Imaging agent
[0157] In the case of convenience, biocompatible cross-linked hydrogel polymers can contain developer to improve its visibility during medical procedures, and provide rapid confirmation of the orientation of the patch relative to the surface to be placed against the wound. In principle, in addition to the hydrogel precursor layer (same or different), or as a substitute for the hydrogel precursor layer, the substrate can have a developer. The patch in the example has a blue developer only in the hydrogel precursor layer. As used in this article, developer can refer to optical visualization (with color), or use the visualization of imaging methods (such as x-rays or ultrasound). Developer is particularly useful when used in minimally invasive surgery (MIS, such as laparoscopy) procedures, and one of the reasons is that they have improved visibility on a color monitor. It is sometimes available to provide color by adding a colored developer to the precursor melt before the hydrogel layer is cast on the substrate.
[0158] The imaging agent (optical) can be selected from any of a variety of non-toxic colored substances suitable for medical implantable medical devices, such as FD&C blue dyes 1, 2, 3 and 6, indocyanine green or colored dyes commonly found in synthetic surgical sutures. In some embodiments, green or blue are ideal because they have better visibility in the presence of blood or on a pink or white tissue background. The dye can be added to the melt blend in trace amounts as a dehydrated compound to form a dried hydrogel layer.
[0159] The selected colored substance may or may not be chemically bound to the hydrogel. Other imaging agents may be used, such as fluorescent (e.g., green or yellow fluorescence under visible light) compounds (e.g., fluorescein or eosin), X-ray contrast agents (e.g., iodinated compounds), ultrasound contrast agents (e.g., microbubbles) or MRI contrast agents (e.g., gadolinium compounds) visible under X-ray imaging equipment. Biocompatible imaging agents FD&C BLUE #1 and fluorescein-NHS may be particularly desirable in some applications. The developer may also be a bioactive agent suspended or dissolved in a hydrogel matrix, or a material for encapsulating a bioactive agent (if present).
[0160] As mentioned above, visually observable developer can be advantageously used in some embodiments. Wavelength is about 400 to 750nm light can be observed by human color (RKHobbie, Intermediate Physics for Medicineand Biology, the 2nd edition, pp. 371-373). When eyes receive light with a main wavelength of about 450 to 500nm, blue is perceived, and when eyes receive light with a main wavelength of about 500 to 570nm, green is perceived. In addition, because eyes detect red or green or blue, the combination of these colors can be used to simulate any other color only by making eyes receive the ratio of red, green and blue perceived as the desired color by the human eye. As used herein, blue means the color perceived by the normal human eye at a wavelength of about 450 to 500nm, and green means the color perceived by the normal human eye at a wavelength of about 500 to 570nm as used herein.
[0161] One or more imaging agents may be present in the final electrophilic-nucleophilic precursor layer at a concentration suitable for visualization, such as about 0.0001 mg / cm2 (g / cm 2 ) to about 0.5g / cm 2, although higher concentrations may be used, up to the solubility limit of the imaging agent. In some applications, these concentration ranges have been found to impart the desired color to the hydrogel without interfering with the crosslinking time (as measured by the time for the reactive precursor material to gel). The imaging agent is generally not covalently linked to the hydrogel. One of ordinary skill in the art will recognize that additional ranges of imaging agent concentrations within the explicit ranges above are also contemplated and are within the scope of the present disclosure.
[0162] Developer can be used to help visualize the interface of patch and following tissue. In some embodiments, dye is conjugated with electrophilic or nucleophilic end group, so that it is incorporated in the patch, in order to visualize together with persistence directly related. In some cases, dye is fluorescent, so that only under special illumination conditions, visualization is realized, and single system gel is invisible under normal visual conditions.
[0163] The user can use the developer to view the hydrogel with the human eye or by an imaging device (e.g., camera) that detects a visually observable developer. A visually observable developer is a reagent with a color that can be detected by the human eye. The characteristic of providing imaging for an X-ray or MRI machine is not a characteristic sufficient to establish the function of a visually observable developer. An alternative embodiment is such a developer that is usually not visible to the human eye, but when used in combination with a suitable imaging device (e.g., camera), can be detected at different wavelengths (e.g., infrared or ultraviolet). Similarly, a sound-permeable agent (e.g., bubble) can provide improved imaging by ultrasound. A hydrogel with an imaging agent for X-ray and / or ultrasound visualization is further described in U.S. Pat. No. 8,383,161, entitled "Radiopaque Covalently Crosslinked Hydrogel Particle Implants" by Campbell et al., which is incorporated herein by reference.
[0164] The radiopaque portion can be introduced by a radiopaque precursor molecule, or covalently linked to a hydrogel functional group. For example, triiodobenzoate can be combined with an arm of the precursor at the ester group. The total number of arms can be selected to achieve the desired cross-linking and radiopacity. The CT number (also referred to as the Hounsfield unit or Hounsfield number) is a measure of visibility under indirect imaging techniques. A CT number of at least about 50 can be used, and in some embodiments, the CT number can be from about 70 to about 2000.
[0165] Methods for patch formation and storage
[0166] The method for preparing the patch includes obtaining a substrate, applying a precursor layer and packaging in a waterproof package, and an optional drying step one or more times in the whole process. If the substrate is not a commercial product, the method may also include preparing the substrate. If the substrate is derived from a commercial product, processing may include cutting a substrate of appropriate size from a larger material block or material sheet. Some suppliers may provide a gelatin substrate sheet with a desired initial thickness. For commercial production, processing may produce a patch material sheet with a hydrogel precursor layer, which may then be cut into appropriate sizes. The size may generally include a set of commercial sizes for the discretion of medical professionals, and it should be noted that the patch may be cut into size as required when used, as described above. The application of the precursor layer may include delivering a melt blend or solution coating with a non-aqueous precursor solution, and layer deposition may optionally include forming a sublayer. The water content may be reduced to below the target amount of packaging, and because the material is generally hygroscopic, processing is generally performed in a closed environment with a low water vapor level. The packaged patch is labeled with a use label and date to reflect appropriate shelf life and appropriate distribution.
[0167] Substrate can be purchased in a form to be used, or can be processed from appropriate starting materials. For gelatin substrates, these can be obtained as foaming sheets, which are subsequently calendered, coated and further processed in other ways. The material purchased can be purchased according to product specifications, and the ideal patch characteristics are as described above, and substrate is selected accordingly to meet these characteristics. Whether or not to purchase or further process to prepare the material formed for the patch, the substrate can be further dried before adding the precursor layer. Drying can be carried out by a variety of methods, such as being placed in a drying oven, contacting with dry gas, isolating with a desiccant, their combination, etc. Suitable drying ovens can be selected based on the size of the substrate material, and continuous heating can be performed until relative humidity drops below the target value. Heat treatment can be carried out under suitable mild conditions, so the characteristic of the material will not change in an undesirable manner. Suitable desiccant is commercially available, such as zeolite, calcium chloride, calcium sulfate, etc.
[0168] In some embodiments based on gelatin sponge material as substrate, the starting material can be purchased or produced. In either case, if appropriate, the material can be cut into a specified thickness for further processing. Typically, a specific patch size may not be cut to size before the hydrogel precursor layer is applied and compressed, although some final processing may be performed after cutting to size. Commercial suppliers of gelatin sponge materials include, for example, Ethicon (USA), Gelita (Germany), Pfizer (Pfizer), and others.
[0169] In some embodiments, the precursor layer can be formed using a solvent coating method. The solution of the precursor should be non-aqueous to avoid the introduction of water that will need to be removed and to avoid deprotonation of the amine. However, the precursor should be soluble in a solvent. Suitable solvents may include, for example, aromatic liquids such as toluene, xylene, chlorobenzene, ethylbenzene, etc.; alkanes such as hexane; or aprotic solvents such as tetrahydrofuran, ethyl acetate, acetone, acetonitrile, dimethyl sulfoxide; blends of any two or more of these liquids, etc. In general, the concentration should be selected to be as compatible as possible with process conditions (such as viscosity) so that a uniform coating can be applied with a smaller amount of solvent. A person of ordinary skill in the art can select a concentration based on the selected coating technique and the selected solvent. The solution may contain a developer and possible other additives such as a biological agent / therapeutic agent. Suitable coating techniques include, for example, spraying, jet printing, slit coating, screen printing, extrusion, etc. As is well known in the art, extrusion will generally mean a different range of viscosity and solid concentration compared to spraying.
[0170] The advantage of using solvent-free process is to avoid using solvent and relevant waste cleaning. The flow temperature of the precursor based on polyethylene glycol (PEG) is quite low, usually below 100 ℃, and relatively weakly depends on molecular size. Some precursors based on low molecular weight PEG can be liquid at room temperature, which can be blended with the precursor that is solid at room temperature to form solid blends. Polyoxazoline usually has a moderately higher flow temperature, and according to side chain and molecular weight, the flow temperature can be about 150 ℃ to 250 ℃. Therefore, the blend based on the precursor of PEG can be formed at a relatively low temperature, and any reasonable technology is used to be appropriately coated on the substrate. The precursor layer can include developer and possible other additives, such as biological agents / therapeutic agents. Although other coating techniques can be used to carry out melt deposition, slot die coating can be a convenient technology, because suitable commercial equipment can maintain material at a suitable temperature, while setting adjustable coating thickness. Equipment that matches the required substrate size can be selected, and the substrate can be easily supplied in sheet or coil form. Suitable commercial slot coating equipment include, for example, FOM Technologies (Denmark), Yasui Seiki (Miriwek Film, Ink, IN, USA), and Coating Tech Slot Dies, Corp. (WI, USA).
[0171] Figure 2 -4 shows various devices for forming an occlusive patch 100, which can be used as a hemostatic patch. Figure 2, spraying device 200 has precursor blend 202 in container 204, which can be a melt blend or an organic solvent blend.Precursor blend 202 can be a clean mixture of molten precursors.Alternatively, precursor blend 202 can be a melt blend with one or more additional components to reduce viscosity.Other components can include, for example, solvents, such as anhydrous organic solvents.Container 204 can mix and / or heat precursor blend 202 before being delivered by nozzle 205.Precursor blend spray 206 is deposited on substrate 208 to form a sealant patch composition, which has a coating of mixed unreacted precursors on substrate 208.In some embodiments, the sealant patch composition formed is dried to remove solvent and / or residual water.In some embodiments, the sealant patch composition formed is cut into separate patches and stored in a moisture-controlled package or container.
[0172] Reference Figure 3A , the slot die coating device 300 has a melt blend 302 in a container 304. The melt blend 302 can be a neat mixture of precursors. Alternatively, the melt blend 302 can have one or more additional components to change the viscosity, such as an organic solvent. The container 304 can mix and / or heat the melt blend 302 before delivering the melt blend 302 through the slot die 306 to form a film 308 on the substrate 310. The device 300 can use additional equipment such as filters, pumps, pulsation dampers, degassing units and / or flow regulators between the container 304 and the slot die 306. Typically, the film 308 is a continuous liquid film. Suitable slot coaters are commercially available, and the use of a commercial slot coater is described in the embodiments. The slot die 306 can have various head sizes, viscosity grades, and stripe pattern options. The width of the film 308 can be selected according to the selection of the slot die 306. The width of the film and the slot die can be selected to match the width of the desired product, or it can be wider than the width and cut into size after coating, such as a width that is several times the width of the product and cut to form a plurality of products of the coated substrate of each length. The slot die 306 can be used to control the deposition rate of the melt blend 302 on the substrate 310, which is related to the thickness of the precursor on the substrate. In order to use the slot die to coat the deposition, the die and the substrate move relative to each other, which can include substrate movement, slot coater and die movement or both movements. Device 300 can be similarly used for coating solvent blends.
[0173] As described above, it may be desirable to deposit a liquid hydrogel precursor material (melt or non-aqueous solution) onto and / or within a porous substrate under some compression. Figure 3BAs shown, the slot die 356 can be used to control the deposition rate of the melt blend 302 and inject the melt blend 302 into the substrate 310. In order to inject the melt blend 302, the slot die 356 and the substrate 310 are moved relative to each other, wherein the slot die 356 compresses the substrate 310 at the injection position. The force applied to the substrate 310 by the slot die 356, the depth of the slot die 356 compressed into the substrate 310, and / or the deposition rate can be adjusted to customize the formed adhesive hydrogel precursor structure. In some embodiments, the compression depth is about 0.02mm to 2mm, in further embodiments, about 0.05mm to about 1mm, and in other embodiments, about 0.2mm to about 0.8mm. In other embodiments, the compression depth is about 5% to about 30% or about 5% to about 15% of the thickness of the substrate before coating. Those of ordinary skill in the art will recognize that other ranges of compression for coating within the above-mentioned explicit ranges are also considered, and these ranges are within the scope of the present disclosure. The porous substrate 310 may have some elasticity. Thus, under relatively mild compression during coating, the substrate may rebound to approximately the original substrate thickness, such as Figure 3B Although a properly modified slot die printhead can effectively apply moderate compression, auxiliary structures can be used to provide moderate compression in the vicinity of the printhead, and calendar rolls and the like can be used to achieve such a purpose.
[0174] In some embodiments, reference Figure 3A , during the deposition of the melt blend 302, the substrate 310 moves as indicated by the directional arrow 312, and the slot die 306 can remain in place. The rate at which the substrate is translated along the directional arrow 312 and the parameters of the slot die 306 can be adjusted to vary the thickness of the film 308. If multiple layers are desired, the substrate can be translated back in the opposite direction to form a second layer, or translated back without coating and translated forward along the directional arrow 312 to further apply subsequent coatings. Figure 3B The embodiments in the above are similarly multiple coated. The substrate can be supplied as a single unit that is coated and then cooled and / or dried for packaging. In other embodiments, the substrate can be provided as a larger sheet that is cut to size after coating, and the larger sheet may or may not be provided in roll form. Dry gelatin substrates are typically provided as relatively hard sheets.
[0175] In other embodiments, during deposition of the melt blend 302, the substrate 310 is not moved, but rather the slot die 306 ( Figure 3A ) or slot die 356 ( Figure 3B) moves along directional arrow 314. In further embodiments, substrate 310 does not move, and slot die 306 or 356 moves in the direction indicated by directional arrow 314 for a period of time or until a selected travel distance is reached, and then moves in the opposite direction indicated by directional arrow 316 for a period of time or until a selected travel distance is reached. Film 308 can be formed by a single deposition layer of melt blend 302 or multiple deposition layers of melt blend 302. In some embodiments, film 308 is formed by alternately depositing melt blend 302 while moving slot die 306 or 356 along directional arrow 314 to form a first deposition layer, and then depositing melt blend 302 while moving slot die 306 or 356 along directional arrow 316 to form an additional deposition layer on the first deposition layer. Alternating deposition can be repeated a selected number of times to achieve the desired thickness of film 308.
[0176] In some embodiments, the film 308 is cooled to form a coating 309 as a solid on the substrate. For many applications, the coating 309 can be a continuous solid hydrogel precursor network that is bonded to the substrate 310 and at least partially integrated into the substrate 310. In some embodiments, the film 308 and / or the coating 309 are dried to remove solvents and / or residual water. The device 300 can be used to form a hydrogel precursor patch composition comprising the coating 309 on the substrate 310. In some embodiments, the structure formed with the hydrogel precursor patch composition on the substrate is cut into individual patches and stored in a moisture-controlled package.
[0177] Figure 4AIt is an embodiment of a roller slot die coating device 400, which has a substrate roller 402, and a substrate 404 is moved from the substrate roller 402 to the bottom of the slot die 405 by a belt 401 moving at a selected speed. The belt 401 can be any convenient conveying system and can be replaced by a series of rollers, etc. The container 406 contains a precursor blend 408, which can be a melt blend or an inert organic solvent solution. The precursor blend 408 can be a neat mixture of precursors. Alternatively, the precursor blend 408 can have one or more additional components to change the viscosity, such as a solvent. The container 406 can mix and / or heat the precursor blend 408 before delivering the precursor blend 408 through the slot die 405 to form a film 410 on the substrate 404. The coating device 400 can use additional equipment between the container 406 and the slot die 405, such as a filter, a pump, a pulsation damper, a degassing unit, and a flow regulator. In some embodiments, the film 410 can be a deposited continuous liquid film. The slot die 405 can have a variety of head sizes and viscosity grades as well as stripe pattern options. The width of the film 410 can be varied depending on the selection of the slot die 405. In some embodiments, the film 410 has a width of 1 cm to 10 cm. The slot die 405 can be used to control the deposition rate of the precursor blend 408 on the substrate 404, which affects the thickness of the film 410. In some embodiments, the slot die 405 can be used to control the deposition rate of the precursor blend 408 and inject the precursor blend 408 into the substrate 404. In order to perform the injection of the precursor blend 408, the substrate 404 is moved below the slot die 405, where the slot die 405 compresses the substrate 404 at the injection location, such as Figure 3B As shown. The force applied to the substrate 404 by the slot die 405, the depth of the slot die 405 compressed into the substrate 404 and / or the deposition rate can be adjusted to customize the cohesive hydrogel precursor network formed. In some embodiments, the compression depth is about 0.02mm to 2mm, about 0.05mm to about 1mm in further embodiments, about 0.1mm to about 0.8mm in some embodiments, and about 0.2mm to about 0.75mm in other embodiments. In other embodiments, the compression depth is about 5% to about 30% or about 5% to about 15% of the thickness of the substrate before coating. Those of ordinary skill in the art will recognize that other ranges of substrate compression within the above-defined ranges are also considered, and these ranges are within the scope of the present disclosure. The translation rate of the belt 401 can also be adjusted to affect the thickness of the film 410. The film 410 can be formed by a single deposition layer of the precursor blend 408 or multiple deposition layers of the precursor blend 408.
[0178] In some embodiments, the film 410 is cooled to form a coating 412. Typically, the coating 412 is a cohesive solid coating, although if desired, portions of the substrate may remain uncoated and the coating may have cracks. The film 410 and / or the coating 412 may be dried to remove solvent and / or residual water. The coating device 400 forms a hydrogel precursor patch sheet including a coating 412 on a substrate 404. In some embodiments, a cutting unit 414 is used to cut the hemostatic patch sheet into patches 416. The patches 416 may then be placed in a waterproof package 418.
[0179] Figure 4B 4 is an overview of a process 430 for improving the properties of a medical patch using a two-step compression process. In process 430, calendaring a substrate 434 is the first compression step. After the step of applying the precursor as a melt 438 to the substrate, a second compression step is performed to calendar the coated substrate 442. Of course, other process steps may be around Figure 4B The product can be assembled in clear steps, such as additional calendering steps, cutting steps, drying, sterilization, packaging and other appropriate process steps.
[0180] The methods and structures described herein improve the properties of medical patches by helping to prepare a substrate for receiving a precursor composition. Step calendering substrate 434 can help to more consistently apply the precursor to the substrate in the form of a melt 438, and is also generally used for non-aqueous solution coating while maintaining a relatively hard substrate for coating. Typically, step calendering substrate 434 can reduce the thickness variation of the substrate, and can also introduce a slight rupture of the cell structure of the substrate. Slight rupture can improve the penetration of the precursor into the substrate while maintaining the appropriate hardness of the substrate, for example, to avoid bending or warping the substrate during and / or after the step of applying the precursor to the substrate in the form of a melt 438. In some embodiments, step calendering substrate 434 can reduce the thickness of the substrate by up to 65%. In other embodiments, calendering substrate 434 can reduce the thickness of the substrate by 5% to 65%, 10% to 50%, 15% to 40% or 20% to 40%. In some embodiments, the substrate compression caused by calendering substrate 434 is at least partially reversible. In some embodiments, after calendering the substrate 434, the thickness of the substrate partially recovers from the fully compressed thickness. In some embodiments, the substrate thickness recovery can ultimately result in a final thickness reduction that is 75%, 60%, 50%, 40%, or 25% of the initial thickness reduction. After step calendering the substrate 434, the precursor is applied to the substrate in the form of a melt 438, wherein Figure 4AAn embodiment of this step is shown. As described above, compression during hydrogel precursor deposition can be relatively mild, and after forming the hydrogel precursor coating, the substrate thickness can be almost not reduced or reduced very little. The second compression step (forming a calendered coated substrate 442) is performed after the precursor coating is applied to the substrate and cured. The curing of the precursor layer can occur relatively quickly by exposure to the environment or optionally by a cooling step. The calendered coated substrate 442 can impart improved flexibility and hemostatic properties to the coated substrate, for example, by introducing appropriately induced cracks into the precursor coating and by introducing additional cracks into the substrate. Typically, the calendered coated substrate 442 can also introduce relatively slight to relatively obvious cracks in the precursor coating. In some embodiments, the cracks include microscale cracks with a series of widths, lengths, and densities on the surface, which can be referred to as broken to reflect changes in the entire surface. Some cracks can be surface cracks, and other cracks can have a depth similar to the depth of the precursor penetrating into the substrate. The calendered coated substrate 442 can reduce the thickness of the coated substrate by up to 65%. In other embodiments, calendaring the coated substrate 442 can reduce the thickness of the coated substrate by 5% to 65%, 10% to 50%, 15% to 40%, or 20% to 40%. One of ordinary skill in the art will recognize that additional ranges of dimensional changes within the above explicit ranges are also contemplated and are within the scope of the present disclosure.
[0181] Steps of calendering substrate 434 and / or calendering coated substrate 442 can change the size, shape and structure of the cells / pores in the substrate. Typically, process 430 collapses the pores and breaks the support around the pores. Although not wanting to be limited by theory, it is believed that the change in porosity of the substrate when compressed is related to the improved performance of the flexible medical patch. In some embodiments, process 430 imparts considerable flexibility and other performance improvements to the coated substrate.
[0182] Figure 4C It is a diagram of the process flow 450 that substrate is manufactured patch 487 by gelatin sheet 451 through process unit. The process unit may or may not be configured as continuous processing, wherein introduces substrate sheet at one end and exits patch at the other end. In order to provide cooling step, curing step etc., the assembly of process unit can be configured accordingly to allow these steps, and these steps may spend more time than active processing step. For convenience, some process components can be configured as the process steps of a subset that are continuously performed. Of course, the process rate of stable state can be realized generally, thereby allowing to use process instrument efficiently.
[0183] In some embodiments, the gelatin sheet 451 has a thickness of about 0.5 mm to about 1.5 cm. In the process flow 450, the gelatin sheet 451 receives thermal crosslinking 452 in an oven 453 or other suitable heating device, and the thermal processing unit may also optionally include a control component. The oven 453 can be any convenient oven or similar device that accommodates one or more gelatin sheets 451. Typically, the gelatin sheet 451 can have any convenient width and length. Thermal crosslinking 452 can be performed at a constant temperature for a selected period of time, or can be performed using a selected heating curve. The oven 453 can optionally be integrated with a heater conveyor system (not shown), which can move the gelatin sheet 451 at a selected rate to achieve a target heating time or other target heating curve, and the heater conveyor system may or may not be directly interfaced with other process equipment.
[0184] Reference Figure 4C , after thermal crosslinking 452, crosslinked substrate 454 may undergo substrate compression 455. In some embodiments, crosslinked substrate 454 is at room temperature before substrate compression 455. In some embodiments, crosslinked substrate 454 has a thickness of about 0.5 mm to about 1.5 cm. Substrate compression 455 is performed using calendaring rollers 456 and 457. Calendaring rollers 456 and 457 are at a selected distance from each other to form a gap 458. Typically, gap 458 is less than the thickness of crosslinked substrate 454. In some embodiments, gap 458 is no more than 65% of the thickness of crosslinked substrate 454. In other embodiments, gap 458 is 5% to 65%, 10% to 50%, 15% to 40%, or 20% to 40% of the thickness of crosslinked substrate 454. Calendaring rollers 456 and / or 457 may or may not be heated. Compared to crosslinked substrate 454, compressed substrate 459 has a ruptured cell structure instead of a complete cell structure. Typically, the compressed substrate 459 is thinner and has a more consistent thickness than the cross-linked substrate 454. In some embodiments, the compressed substrate 459 has a thickness of about 0.25 mm to about 1 cm, about 0.5 mm to about 7 mm, about 3 mm to about 6 mm. In some embodiments, the substrate compression 455 is integrated with a conveyor system 460 having a belt 461. The conveyor system 460 can be any convenient conveyor system, and the belt 461 can be replaced with a series of rollers, etc. In some embodiments, the calendering roller 457 can be part of the conveyor system 460. Those of ordinary skill in the art will recognize that additional ranges of thicknesses and percentages within the above explicit ranges are also contemplated and are within the scope of the present disclosure.
[0185] Next, refer to Figure 4C , the compressed substrate 459 is coated 462 using a coating device 491. The coating device 491 is similar to Figure 4AThe roller slot die coating device 400 is different in that it is not configured for roller-based substrates. The container 463 holds a precursor blend 464, which can be a melt blend or an inert organic solvent solution. The precursor blend 464 can be a neat mixture of molten precursors. Alternatively, the precursor blend 464 can have one or more additional components to change the viscosity, such as a non-aqueous solvent. The container 463 can mix and / or heat the precursor blend 464 before delivering the precursor blend 464 through the slot die 465 to form a film 466 on a compressed substrate 467. Coating 462 can use additional equipment between the container 463 and the slot die 465, such as a filter, a pump, a pulsation damper, a degassing unit, and a flow regulator. In some embodiments, the film 466 can be a continuous liquid film deposited. The slot die 465 can have various head sizes and viscosity grades and stripe pattern options. Suitable slot die coaters are commercially available. The width of film 466 can be changed by selecting slot die 465, and generally the width can be any reasonable value. In some embodiments, film 466 has a width of 1 cm to 100 cm, or in some embodiments has a width of about 2 cm to about 20 cm. Slot die 465 can be used to control the deposition rate of precursor blend 464 on compressed substrate 467, which affects the thickness of film 466. The translation rate of belt 461 can also be adjusted to affect the thickness of film 466. Film 466 can be formed by a single deposition layer of precursor blend 464 or multiple deposition layers of precursor blend 464. In some embodiments, film 466 is formed as a cohesive hydrogel precursor network. In some embodiments, film 466 is formed in the following manner: precursor blend 464 is injected into compressed substrate 467, while compressed substrate 467 is further compressed at the injection position. In some embodiments, film 466 is cooled to form coating 468. Typically, coating 468 is a continuous solid coating, although if desired, portions of the substrate may remain uncoated. Film 466 and / or coating 468 may be dried to remove solvent and / or residual water. In some embodiments, coating 468 has a thickness within the range described above, which may penetrate into the compressed substrate. In some embodiments, coating 468 is a portion of an adhesive hydrogel precursor structure that at least partially penetrates into the compressed substrate 467. In some embodiments, coating 468 is a portion of an adhesive hydrogel precursor structure having a surface that matches a surface of the compressed substrate 467. In some embodiments, cutting unit 469 is used to remove front segment 470. Removing front segment 470 may provide a more consistent coating on patch 487.
[0186] Next, coated substrate 471 having coating 472 and compressed substrate 473 is subjected to coated substrate compression 476 to form compressed coated substrate 477. Coated substrate compression 476 may be performed using calendaring rollers 478 and 480. Calendaring rollers 478 and 480 are at a selected distance from each other to form gap 481, such as Figure 4D As shown. Typically, gap 481 is less than the thickness of coated substrate 471. In some embodiments, gap 481 may not exceed 75% of the thickness of coated substrate 471. In other embodiments, gap 481 is 15% to 70%, 20% to 65%, 22% to 62% or 30% to 60% of the thickness of coated substrate 471. In some embodiments, compression coated substrate 477 has a thickness of about 0.3mm to about 1cm and has a thickness of about 0.5mm to about 5mm in other embodiments. Calendering rollers 478 and / or 480 may or may not be heated. Compression coated substrate 477 has cracked coating 482 and compression substrate 483. Typically, compression coated substrate 477 is thinner and more flexible than coated substrate 471. In some embodiments, cracked coating 482 has microcracks of various widths, lengths and depths that substantially span the surface to present a fractured surface. In some embodiments, cracked coating 482 has a relatively consistent ratio of fractured surface area to total surface area over most surface areas. In some embodiments, the edges of the cracked coating 482 are different from other areas of the cracked coating 482. In some embodiments, the cracked coating 482 has a thickness of about 0.1 mm to about 8 mm, about 0.15 mm to about 7 mm, about 0.2 mm to about 5.5 mm, about 0.25 to about 5 mm, about 0.35 mm to about 4.5 mm, and in some embodiments has a thickness of about 0.5 mm to about 4 mm. In some embodiments, the compressed substrate 483 has a thickness of about 0.1 mm to about 9 mm, about 0.15 to about 8 mm, about 0.25 mm to about 6 mm, about 0.5 mm to about 5.5 mm, about 0.75 mm to about 5 mm, and about 1 mm to about 4 mm. In some embodiments, the coated substrate compression 476 is integrated with a conveyor system 460 having a belt 461, which also conveys the substrate through the substrate compression 455. In some embodiments, the calender roller 480 can be part of the conveyor system 460.
[0187] Next, the flexible hemostatic patch sheet 486 can be cut 484. During cutting 484, a cutting unit 485 is used to cut the flexible hemostatic patch sheet 486 into patches 487, which can involve cutting in length and / or width. During optional packaging 488, the patches 487 are placed in a waterproof package 490.
[0188] Processing can be carried out in a controlled atmosphere, such as under dry nitrogen, other inert gases, etc. After the patch is formed, it can be packaged in a moisture-proof package, such as a polymer and / or foil bag, etc., under a dry inert gas. The patch can be heated, such as from 40°C to 90°C, to further dry. A packet of desiccant can be included in the package to help maintain dryness. The patch can be sterilized, for example, using radiation after packaging. Sterilization can be carried out under conditions that do not cause a large amount of cross-linking. The packaging is appropriately labeled according to regulatory guidelines for medical use and indicates an expiration date.
[0189] The storage of the patch is usually carried out in moisture-proof packaging. In some embodiments, the patch is heat-sealed in a foil bag. In order to increase the storage time, it may be desirable to store the patch under refrigerated conditions. Usually, the patch can be stored at a temperature not exceeding about 5 ° C, or stored at a standard refrigerator temperature, which may be in the range of 1 ° C to 7 ° C, but lower temperatures may also be used as required. For short-term storage, the patch can be stored at room temperature. At refrigerated temperature, the patch can be stored for at least 2 months, in further embodiments for at least one year, in other embodiments for three months to 3 years, and in some embodiments for 6 months to 2.5 years. Those of ordinary skill in the art will recognize that the other scopes of the storage temperature and time within the above-mentioned clear range are also considered, and these scopes are within the scope of the present disclosure. The patch that exceeds its shelf life can be identified by insufficient adhesion caused by premature cross-linking or premature hydrolysis to remove the electrophilic group for cross-linking.
[0190] Biologics and drugs
[0191] In addition to the optional developer, the patch can also include a biological agent. Optional biological agents or medicines can be, for example, agents that promote blood coagulation and / or healing. Although good hemostasis has been obtained without the need to add blood products to the complication in the patch composition, thrombin can be added to the patch. Because the patch material absorbs rapidly, the patch can degrade before any major problems related to adhesion formation or microbial contamination occur. However, if necessary, an antimicrobial can be added. In a further embodiment, therapeutic agents can include analgesics, anesthetics, steroids, antibiotics, steroids, anti-infective agents, anti-inflammatory drugs, non-steroidal anti-inflammatory drugs, antiproliferative agents or their combinations. These modes can be effectively used for local drug delivery, because the patch provides local adhesion and the reservoir of the medicine or bioactive agent added.
[0192] Uses and medical indications of the patch
[0193] Medical patch as herein described is particularly helpful for use as hemostatic patch.Hemostatic patch is applied to few, slight or moderate bleeding sites with compression force, and target is to stop bleeding.Patch may include or may not include therapeutic agent, such as the compound that promotes blood coagulation, and embodiment has shown effective hemostasis under the situation of any bioactive agent.Patch can be used for contacting with exposed tissue more generally, and need not attempt to control heavy bleeding, such as for surgical closure application.The cross-linking activation of patch is induced when contacting with any biological fluid.Adopt suitable substrate and thickness, patch can also be relatively flexible and conformable even when dry, and this characteristic can be used for some application.
[0194] Typically, the patch can be delivered directly to the wound site, such as in open surgery. In alternative embodiments, the patch can be used for laparoscopic surgery because the patch has enough flexibility to be delivered by a trocar. Although the patch can be easily applied to the wound (wherein the hydrogel precursor layer is directed toward the wound), alternatively, the patch can be folded, such as by turning the hydrogel precursor side outward, and inserting it into the wound so that the patch fills the wound.
[0195] To provide further patch delivery options, Fig.13A Patch 750 is shown having been folded into a loose accordion-like shape. Fig. 13B Process 800 is shown in which an accordion-folded patch 801 is introduced into a cannula 803 via forceps 805. Process 800 can be used to guide an accordion-folded patch 801 to a treatment site. Fig. 13C An embodiment is shown in which patch 806 has been folded accordion-like and then folded laterally. Fig.13D Process 810 is shown, wherein an accordion-shaped folded and laterally folded patch 812 is introduced into a sleeve 814 by forceps 816. Process 810 can be used to guide an accordion-shaped folded and laterally folded patch 812 to a treatment site. In some embodiments, process 800 / 810 can be used to preload sleeves 803 / 814 for future use. In some embodiments, process 800 / 810 can be used to preload sleeves 803 / 814 for packaging as a "preloaded" patch. In some embodiments, process 800 / 810 can be used with a tubular applicator to replace sleeves 803 / 814. Patch 750 and patch 806 each provide a more compact shape than a flat patch, which can be convenient for certain applications such as laparoscopic surgery applications.
[0196] Fig.14820 is a schematic diagram of a patch delivery for laparoscopic surgery 820, wherein an accordion-folded patch 824 has been introduced into a laparoscopic site 831 through a cannula 826 using forceps 828. Forceps 830 have been introduced into a laparoscopic site 831 through a cannula 834. Forceps 830 can help guide the accordion-folded patch 824 to a treatment site 838. In some embodiments, the treatment site 838 can be a wound site or a surgical site to be closed. In some embodiments, the accordion-folded patch 824 can be used in laparoscopic surgery 820 to provide hemostasis. In some embodiments, the coating of the accordion-folded patch 824 can be broken at the fold line. In some embodiments, the cracks in the coating of the accordion-folded patch 824 can extend to the substrate surface. Typically, the accordion-folded patch 824 can self-heal cracks due to swelling when hydrated by fluid at the treatment site.
[0197] The hemostatic patch can also be ground or chopped as needed to be used as a filler, which is used alone or in combination with another patch or a portion of a patch. The above-mentioned chopped patch preparation or similar particle composition can be distributed by a cannula attached to a bellows-type device. Such a preparation can be used to seal or control the bleeding of a large area of oozing surface of tissue.
[0198] In some embodiments, before the patch is applied to the tissue, shortly, the patch can be moistened with a sterile aqueous solution (such as saline or water for injection) to start hydration. Typically, the patch is applied to the tissue, wherein a sterile gauze pad or the like is placed on the patch surface to promote the application process, and as used herein, a gauze pad refers to the pad of any non-adhesive absorbent material. Gauze pads can be used to apply roughly uniform pressure to the patch in a period of time to allow adhesion. The time selected is generally at least about 5 seconds, at least about 8 seconds in a further embodiment, about 10 seconds to about 4 minutes in some embodiments, and about 12 seconds to about 2 minutes in other embodiments. Those of ordinary skill in the art will recognize that the other scope of the time in the above-mentioned clear and definite scope is also considered, and these scopes are within the scope of the present disclosure. The placement of the patch can include using a single patch or placing a plurality of medical patches on the bleeding defect. Other medical patches can overlap with at least a portion of the first medical patch.
[0199] For wounds, in a process known as hemostasis, bleeding can be stopped by using a patch. Hemostasis involves coagulation, which stops bleeding and can be considered the first stage of wound healing. After hemostasis, the wound no longer bleeds. Using a patch as described herein, hemostasis can usually be achieved in about 5 minutes, and in some embodiments, hemostasis is achieved in no more than 3 minutes. Those of ordinary skill in the art will recognize that other ranges of hemostasis time within the above-mentioned clear range are also considered, and these ranges are within the scope of the present disclosure.
[0200] The specific use of interest includes applying the patch to a wound on or in an organ or to a wound on a blood vessel. In a broad sense, hemostasis can relate to any wound repair, although the bleeding degree may be significantly different. Patch described herein can be used for the situation of any degree of bleeding, but as shown in the examples, they can be effective in the case of heavy bleeding. In the case of surgery, the patch can be used for being placed on and relate to blood vessels, liver, intestinal tract, uterus, pancreas, other organs, orthopedic applications (such as bones and connective tissue) or general any surgical wound and the operation of the wound produced by injury. In some embodiments, the patch can be placed along the skin, in order to close the wound on the patient's surface or in order to end surgical intervention.
[0201] Although usually any tissue wound can be effectively covered with patch as described herein, patch is particularly effective for covering the wound in the organ that is easy to bleed heavily. Suitable organs include, for example, bones, glands, digestive organs, lung organs, urinary organs, reproductive organs, blood vessels, interfaces with natural or synthetic implants or their combinations. In some embodiments, the organ is an artery or vein, and the organ can be natural, transplanted or their combination generally. In particular, the patch can be applied to the bleeding defect. The bleeding defect can be, for example, sutures, puncture wounds, gunshot wounds, cavities, abrasions, biopsy puncture holes, transplant interfaces or their combinations. The placement of one or more patches can include placing one or more medical patches on the bleeding defect with non-flat geometry, which is generally determined by the shape of the organ. The placement of a patch can include wrapping one or more medical patches around the organ. The degree of organ bleeding can be evaluated according to spot grade bleeding scores or other verified bleeding scales.
[0202] In some embodiments, the patch itself may be packaged in a pre-folded form, such as Fig.13A and 13C As shown, or wrapped in "preload" form, so as to allow the use of axle handle or plunger-like mechanism to be deployed from a tubular applicator to squeeze the patch near the treatment site. The preload of patch is used for laparoscopic application, which involves inserting through a narrow tubular entrance, and the patch can be further moved to the hemostasis site after being introduced by a laparoscopic manipulator, and the laparoscopic manipulator can also apply pressure to place the patch against the wound. In other embodiments, the preload configuration stores the patch or cylindrical patch of the package, and these patches can be delivered to the defect (such as a bullet wound or a puncture wound) wherein the hemostasis is not ideal by a flat substrate geometry. In more embodiments, the preformed patch-axle handle relationship can provide for delivering a geometry that is not ideal for using a flat patch to stop bleeding, and wherein the axle handle surface has a desired shape for making the patch conform to the wound.
[0203] One application envisioned is to use a tapered preformed patch in conjunction with a tapered mandrel for use in hemostasis following a loop electrosurgical excision procedure (LEEP) of cervical tissue. In this case, the shape of the mandrel and preformed patch serves to fill the irregular tapered depression left by the LEEP procedure, and the mandrel can be removed after the patch adheres and hemostasis is achieved. Fig. 12A and 12B One embodiment of the above application is shown. Fig. 12A The tapered hemostatic patch 700 is shown being placed into the cervix 704 using the tapered mandrel 702 . Fig. 12B A hemostatic patch 710 is shown positioned within the cervix 704. The left inset shows the tapered mandrel 702 providing pressure to the tapered hemostatic patch within the cervix 704. The right inset shows the tapered mandrel 702 removed and the positioned hemostatic patch 710 adhered to the irregular tapered depression of the cervical tissue. For this and similarly shaped embodiments, the patch can be heated to soften the precursor layer for forming into the mandrel or simply otherwise molded into the desired shape. If cooled on the mandrel, the shape can be substantially maintained for deployment.
[0204] In more embodiments, the patch becomes soft and conformable by processing or pre-wetting, and can be applied to other gynecological applications. Some embodiments use conformable patches to stop the bleeding of hysterectomy after cesarean section. In other applications, softening patches can be applied through the cervix to stop postpartum hemorrhage. Postpartum hemorrhage may be a very worrying condition, which causes the mother to lose blood rapidly, thereby causing hypotension and shock, and may cause death. In some cases, after therapeutic treatment and manual compression hemostasis failure, softening patches can be delivered vaginally / through the cervix and conformable to irregular intrauterine surfaces, which eliminates the more extreme results of surgical intervention, hysterectomy or death. Ideally, the patch stops bleeding quickly in 1-2 minutes, and will be absorbed rapidly subsequently, to reduce interference with any other future medical diagnosis. Multiple patches can be used until hemostasis is achieved.
[0205] Although the patch is wetted shortly before being delivered to the application site in some embodiments, one or more patches can be placed without pre-wetting one or more medical patches. In some embodiments, placing one or more patches includes wetting one or more medical patches with non-buffered water or non-buffered saline before and / or after placement. Regardless of whether the patch is pre-wetted, the patch is hydrated relatively quickly. Along with the precursor cross-linking to form a hydrogel, the precursor layer becomes adhered to the application site. Typically, the precursor layer is hydrated and adhered to an organ or other tissue in no more than about 2 minutes.
[0206] Ocular application can relate to a patch with a substrate, which is used to prevent the reactive precursor from adhering to an applicator or user during application to the moistened ocular surface. In certain embodiments, the substrate dissolves rapidly, or is removable, so that the time it exists is only enough to prevent adhesion during application. In other embodiments, the substrate is non-resorbable, continues to provide structural support for the blended melt precursor, and is removed after the precursor is applied. It is conceivable that the ocular application of a premixed precursor melt containing a therapeutic agent for treating ocular surface conditions (such as controlling postoperative pain) and / or treating the anterior chamber of the eye. In such an embodiment, a releasable backing can be used to apply the molten precursor plus the therapeutic agent to the fornix of the eye, and then removed after cross-linking begins. In some cases, the melt blend of the precursor may be less compatible with the substrate, to reduce adhesion to the substrate during application. In other cases, the melt precursor is preformed, cut into an insert shape, and then or only before application, a substrate backing is added. In cases where the substrate is added after the unreacted blend is created, an adhesive (such as a low Mw PEG liquid) can be used to enhance the adhesion of the melt blended precursor to the substrate during storage or shortly before application. One embodiment can include a melt precursor wafer attached to a disposable applicator substrate that can be applied to the fornix by the patient and then discarded (substrate).
[0207] From this embodiment, in the case of self-administration by the patient, various therapeutic agents can be delivered in a sufficiently large amount within a possibly short period of time. Larger therapeutic agent loads enable the use of more types of lower efficacy drug substances. High potency candidates are a limitation of ocular implants, which are limited to small volume applications, such as punctal plugs, anterior, posterior and suprachoroidal injections. An example is the use of NSAIDs or bupivacaine for local fornix delivery, rather than the use of high-efficiency corticosteroids, which may have off-target problems, such as long-term use leading to increased intraocular pressure. In these embodiments, only high-efficiency therapeutic agents are no longer needed, opening the way for ocular applications in the front of the eye, such as treating painful inflammation, dry eye, infection, etc.
[0208] In the case of surgery, the patch usually provides the required burst strength, but if necessary, sutures, such as dissolving sutures, can also be applied. For degradable patches, the patch of application can be sealed in the patient's body, and its safe degradation is achieved at the appropriate time of hemostasis stability. Usually, there is no need to further intervene in the patch, but in rare cases, supplementary care can be applied to the wound. For in vivo use, the patch is usually absorbed into the body by degradation for removal, usually by the kidney, completed within 28 days, in further embodiments within 21 days, and in other embodiments, 7 days to 14 days. Those of ordinary skill in the art will recognize that the other scope of the time in the above-mentioned clear and definite scope is also considered, and these scopes are within the scope of the present disclosure. In alternative embodiments, the patch can be designed to be substantially non-absorbable for hydrogels so that it can continue the extended time period.
[0209] Figure 5 5 is a schematic diagram of a hemostatic patch 501 wrapped around a tubular organ 504. In some embodiments, the tubular organ 504 is an artery or a vein. The wrapped hemostatic patch 501 may have a tail 506 formed by connecting the two ends of the hemostatic patch 501. The hemostatic patch 501 may be dry or pre-moistened before wrapping. Examples 5 and 6 illustrate wrapping a suture on a femoral artery with a hemostatic patch 501. Example 6 illustrates wrapping of a hemostatic patch 501 using a double layer of wet gauze and a hemostatic patch 501. As illustrated in Example 5, the hemostatic patch can be placed on a tubular organ and / or a tubular graft without wrapping. Example 6 illustrates a non-wrapping process for establishing hemostasis in a cavity-type bone defect using a disc-shaped hemostatic patch.
[0210] Figure 6 is a schematic diagram of a hemostatic patch 512 placed on a non-tubular organ 514. Examples 3 and 4 illustrate placement of a hemostatic patch 512 on a liver defect including both concave and convex defect surfaces. Figure 7 is a schematic diagram of a hemostatic patch 518 placed on skin 520.
[0211] Figures 8A-8D The method of action of the hemostatic patch is shown. Fig. 8A A bleeding defect 600 of tissue 604 is shown with blood 606 flowing out of it. Figure 8B A hemostatic patch 607 is shown placed on tissue 604. The hemostatic patch 607 is placed with the substrate 608 facing away from the bleeding defect 600 and the melt blend layer 610 facing the bleeding defect 600. Blood 612 from the bleeding defect 600 is absorbed into the hemostatic patch 607, causing the precursors in the melt blend layer 610 to dissolve and interact to form a cross-linked hydrogel layer 616 ( Figure 8C). In some embodiments, after the hemostatic patch 607 is placed on the bleeding defect 600, the melt blend layer 610 reacts to form the cross-linked hydrogel layer 616 within 30 seconds. Figure 8C Also shown is substrate 618 conforming to allow hemostatic patch 620 to adhere to tissue 622 and close bleeding defect 600 to yield hemostatic defect 624 . Fig.8D Healed tissue 626 is shown wherein the hemostatic patch 620 has been absorbed.
[0212] Example
[0213] Examples 1-8 relate to the general formation of hydrogel precursor layers and demonstration of hemostatic efficacy in several model systems. Example 9 relates to the evaluation of the properties of the compressed substrate and the formation of the patch and the properties of the resulting patch.
[0214] Example 1: Preparation of hemostatic patch samples
[0215] This example describes the preparation of a hemostatic patch sample.
[0216] Hemostatic patch samples were prepared by melt coating the dry blend of two hydrogel precursors onto a porcine gelatin substrate. Various gelatin / collagen substrates as shown in Table 1 were prepared. Each substrate was cross-linked, wherein light cross-linking refers to less than about 20% cross-linking, and high cross-linking refers to greater than about 20% cross-linking. Substrates A, B, and D are characterized by having small pores (micrometers or less) and a porosity greater than 80%, as measured by mercury intrusion porosimetry. Each substrate prepared for coating was dried in an oven at a temperature of 35°C under ambient air for 18 hours or until the relative humidity of the oven was less than 5%. The thickness of the gelatin substrate after drying was approximately the same as that before drying. For each patch sample, the first hydrogel precursor was an eight-armed polyethylene glycol-based precursor having a molecular weight of 15,000Da and a succinimidyl glutarate (SG) functional end group (8A15k PEG SG, Jenkemusa). The second hydrogel precursor was an eight-arm polyethylene glycol-based precursor with a molecular weight of 20,000 Da and HCl salt amine functional end groups (8A20k PEG amine-HCl, Jenkemusa). The first and second precursors were measured in powder form and then melt blended with trace amounts of FD&C Blue #1 in a glove box on a heated roller system at a temperature above 45°C. The molten precursor blend was delivered to a liquid dispensing system (Vulcan TMJet Dispenser, Nordson). Under inert gas conditions, a single layer of the coating of the melt blend is applied to a dry gelatin substrate with a width of 0.5 mm per pass and a line speed of 50 mm / second until the total width of the coating is about 20 cm. The thickness of the coating is about 0.25 mm. The mixed precursor coated substrate is cured at room temperature under inert gas conditions. The thickness of the coated substrate measured is about 1.25 mm. The coated substrate is cut into individual hemostatic patches of about 2 × 4 cm in size and packaged in foil containers or disposable bags, both of which are designed to keep the initial relative humidity of the inert gas in the container below about 20 ppm. Suitable commercial medical packaging includes Amcor PerfecFlex 35772-E or Paxxus Symphony 26-1010. The patch is sterilized after packaging. The mixed precursor coated side ("active side") of each patch is identified by its blue coloring, while the substrate backing on the other side of each patch does not have blue coloring.
[0217] Table 1
[0218]
[0219] Example 2: In vitro testing of hemostatic patch samples and substrates
[0220] This example evaluates the gel time, burst pressure, swelling and persistence of a set of hemostatic patches prepared according to Example 1. This example also evaluates the swelling and persistence of the substrate.
[0221] Part A. Test Specimens and Test Procedures. A hemostatic test patch prepared using substrate type A according to Example 1 ("Test Patch A") was used in this study. Separately, (uncoated) samples of substrate A and substrate D with low and high crosslinking, respectively, were also tested. Individual samples for testing were cut from a single piece of test patch A or a single piece of substrate A or substrate D. The test methods used in this example are described in the "Hydrogel and Patch Properties" section above.
[0222] Part B. Substrate Testing.
[0223] The swelling of the samples of substrate A was evaluated. The samples of substrate A were weighed and then immersed in a phosphate buffered saline (PBS) solution maintained at 37°C for a selected period of time. Tables 2-4 show the swelling of the samples at 30 seconds, 1 minute, and 2 minutes, respectively. The swelling of the samples at 30 seconds, 1 minute, and 2 minutes was an average of 814 weight %, 973 weight %, and 1053 weight %, respectively. The results show that biocompatible substrates can be prepared to have high swelling rates and high swelling degrees at 30 seconds.
[0224] Table 2
[0225]
[0226]
[0227] Table 3
[0228] sample Mass, g Swelling at 1 minute 1 0.0071 887% 2 0.007 1017% 3 0.0073 892% 4 0.0073 1049% 5 0.0066 1018% average value 0.07568 973%
[0229] Table 4
[0230] sample Mass, g Swelling at 2 minutes 1 0.0068 1103% 2 0.0069 1077% 3 0.0068 1000% 4 0.0072 993% 5 0.0074 1092% average value 0.08094 1053%
[0231] The persistence of samples of substrates A and D in PBS solution was evaluated. The samples were immersed in a PBS solution maintained at 37°C. Visual evaluation of the samples was performed after 67 hours (2.8 days), 96 hours (4.0 days) and 114 hours (4.8 days). As shown in Table 5, each substrate A sample (samples 1-10) was observed to be partially persistent after 67 hours. Samples 1-10 were not visible at 96 hours, indicating that the persistence window of substrate A was about 2.8 to about 4 days. Each substrate B sample (samples 11-15) was observed to be persistent after 114 hours.
[0232] The results show that substrate persistence in simulated in vivo environments can be well controlled through substrate processing. The results also show that biocompatible absorbable substrates with high water absorption and total water absorption have been prepared and that these highly absorbent substrates can be designed to persist within a controlled time window.
[0233] Table 5
[0234]
[0235] Part C. Patch Testing.
[0236] Using an 8 mm biopsy punch, patch samples were cut from a single 2 x 4 cm piece of Test Patch A into 8 mm disks.
[0237] The gel time of the patch samples was evaluated using a commercial texture analyzer as described above in the “Hydrogel and Patch Properties” section. Fig.11 Shown are typical force versus time curves for patch samples evaluated immediately after activation with pH 8 buffer solution. Fig.11 The arrow in the graph indicates the time corresponding to the lowest force on the curve. The gel time for this sample was measured to be 25 seconds.
[0238] After the gel time test, the burst pressure of the test patch sample was tested. Table 6 shows the burst pressure results. The burst pressure of record sample 1 is 0, which shows that the sample does not adhere to the test block after the gel test. Samples 2-5 have a burst pressure of 10mm Hg to 65mmHg. Samples 6-10 have a burst pressure greater than 140mm Hg, and wherein sample 9 has a burst pressure of 188.2mm Hg. Table 6 also shows the quality of the patch sample before and after the burst test. The swelling of the patch sample during the burst test is in the range of about 340% to about 510%.
[0239] Table 6
[0240]
[0241] After the burst test, the persistence of the patch samples and the swelling from the hydrated state after the burst test were evaluated. The results are summarized in Table 7. Samples 1-5 were immersed in a PBS solution maintained at 37°C. These samples swelled an average of 203% by weight in 24 hours. Due to this expansion after hydration at the end of the burst test, it was determined that the cumulative swelling of patch samples 1-5 from a dry state after about 24 hours was 1412% to 1903%. Samples 1-5 were not visible after 114 hours (4.8 days). Samples 6-10 were immersed in a PBS solution maintained at 50°C. In this accelerated aging study, each sample almost disappeared at 24 hours.
[0242] Table 7
[0243]
[0244]
[0245] "x" means the sample has almost disappeared
[0246] The result shows that the absorbable patch of biocompatibility has been prepared, and its gel time is less than 30 seconds and burst pressure exceeds 140mmHg. These patches have also been demonstrated to have relatively high swelling rate and overall swelling degree, but persistence is relatively short (less than about 5 days). The result shows that, compared with the substrate (substrate A) separated, the test patch has similar persistence. The result shows that the precursor layer and substrate can be customized so that the persistence of the gained hydrogel layer and the substrate is similar. Alternatively, the precursor layer and / or substrate can be customized so that the gained hydrogel layer or substrate have a shorter duration.
[0247] Example 3: Liver defect study 1 (with comparative example)
[0248] This example evaluates the hemostatic effect of the hemostatic patch prepared according to Example 1 in a pig liver defect model and compares it with a commercially available fibrin sealant patch.
[0249] Part A. Test and Control Patches. This study used three hemostatic test patches prepared according to Example 1 using substrate type A ("test patch A"), substrate type B ("test patch B"), and substrate C ("test patch C"). A comparative fibrin sealant patch ("control patch A") from Baxter was purchased ( Fibrin sealant patch, 0.5 cm x 4.8 cm, product code 1144922). Each patch was trimmed to approximately 2 x 2 cm size for application. The active side of the test patch was blue, and the active side of the control patch was yellow.
[0250] Part B. Animal defect model preparation. An acute (Yorkshire) pig was incised along the anterior (ventral) midline and the liver was isolated. The animal had the following characteristics: weight (48.2 kg); sex (M); anticoagulation (ACT: 242). The ACT was recorded before the first placement. Defects were created in both the left and right inner lobes of the liver. An 8 mm biopsy puncture was used to penetrate the liver to a depth of approximately 4 mm. Metzenbaum scissors were then used to remove the embolism created by the puncture. At this time, bleeding was assessed using the Adam scale, which is described in Adams et al., Journal of Thrombosis and Thrombolysis (2009) 28: 1-5 (DOI 10.1007 / s11239-008-2049-3), which is incorporated herein by reference. According to the Adam scale, the target bleeding score > 3 is ideal. (See Fig. 9 ). If the target score is not reached, the liver is penetrated again using the biopsy puncture device until the target score is reached. The defect bleeding score generated by each test is recorded as the initial score, as shown in Tables 8 and 9. The bleeding defects of the test patch A are severe (tests 2-1 and 2-2), moderate (test 2-3) and slight (test 2-4). The bleeding defects of the control patch A are severe (tests 2-1C and 2-2C), moderate (test 2-3C) and slight / moderate (test 2-4C). Before placing the patch, clean dry gauze is used to treat bleeding at the defect site.
[0251] Table 8
[0252] Test Patch A Test Initial Rating Rating at 1 minute Rating at 3 minutes 2-1 4 0 0 2-2 4 0 0 2-3 3 0 0 2-4 2 0 0 average value: 3.25 0 0
[0253] Table 9
[0254] Control patch A test Initial Rating Rating at 1 minute Rating at 3 minutes 2-1C 4 4 3 2-2C 4 3 4 2-3C 2 0 2 2-4C 2.5 0 0* average value: 3.2 1.8 2.3
[0255] *Swelling under the patch.
[0256] Section C. Patch Evaluation Procedures and Results 。Use clean sterile saline to moisten clean gauze。Test patch A sample is placed back down on moistened gauze, so that the active side of the patch is facing away from the gauze, although in general use, the patch can be placed without gauze to facilitate correct placement, and then the gauze can be used to maintain a certain pressure while the patch adheres。The gauze used to process bleeding in the defect site is removed from the defect site。Immediately place the patch on the defect site, so that the active side of the patch contacts the defect and is located at the center of the defect as much as possible。Use open hands, apply powerful and uniform pressure on the back side of the patch with wet gauze, and keep 1 minute (first interval).Then, slowly reduce pressure, and carefully remove gauze from the back surface of the patch applied。If there is any adhesion of gauze to the patch, clean surgical instruments are gently applied to the edge of the patch, or gauze is separated from the patch using gentle flushing, while minimizing interference。After 30 seconds of evaluation period, 1 minute bleeding score is recorded according to the Adam scale, as shown in Table 8。 The patch back side is then used again with wet gauze to apply powerful and uniform pressure, and continues for another 2 minutes. Slowly reduce pressure again, and carefully remove gauze from the back surface of the patch applied. After 30 seconds of evaluation period, 3 minutes of bleeding scores were recorded according to the Adam scale, as shown in Table 8. Then, a pair of tweezers are used to gently pick up the edge of the patch to test adhesion. Repeat this procedure with test patch A to other three defects, totaling four tests. All test patch samples are well adhered to the target site, and are not affected by the removal of wet gauze. In addition, when pulling / picking with tweezers, the edge of the test patch sample cannot be pulled up. Leakage by any test patch sample is not observed. The result shows that all tests using test patch A are placed in 1 minute after achieving hemostasis.
[0257] The above procedure was repeated for Control Patch A with some modifications. For Control Patch A Trials 2-3 and 2-4, the target bleeding score was changed from 4.3 to 1.5 due to poor performance of the control sample in Trials 2-1C and 2-2C. > 3 down to > 2. The results are shown in Table 9. For control patch A test 2-4C, 3 minutes after placement, the bleeding score was recorded as 0, but there was swelling under the patch. When pressed, blood flowed out from below the patch and continued bleeding. This test is considered to be non-hemostatic. The results show that although the target bleeding score of the latter two tests is reduced, the test using control patch A did not achieve hemostasis 3 minutes after placement. In addition, it is observed that the control patch A sample does not adhere to the target site and it easily falls off. During the removal of the wet gauze, it is necessary to be extremely careful not to disturb the patch from the placement site.
[0258] On the liver defects produced by the control patch A tests 2-2C and 2-3C, after these control patch samples continued to have severe or mild bleeding at 3 minutes, respectively, test patch B and test patch C were evaluated. Both test patch samples were able to restore hemostasis within 1 to 3 minutes, as shown in Table 10. The initial placement of test patch B was not located in the center of the defect. One minute after the initial placement, a second test patch B was placed at the defect. Hemostasis was achieved 3 minutes after the initial placement (corresponding to 2 minutes after the second placement).
[0259] Table 10
[0260] sample Initial Rating Rating at 1 minute Rating at 3 minutes Test patch B 4 4* 0 Test Patch C 2 0 0
[0261] *Initial placement was not in the center of the wound and the second test patch B was placed at 1 minute.
[0262] Part D. Additional patch evaluations. In addition, test patch A was additionally evaluated by non-flat placement into a defect created on the liver surface using a scalpel. The channel-type defect was approximately 3 mm deep and approximately 5 mm long. Test patch A was cut into 2×4 cm dimensions, moistened with saline, folded in half lengthwise, and then placed into the defect. Fig. 10A 1 shows the test patch A after initial placement. Pressure was applied to the test patch sample using a moistened gauze pad. Hemostasis was achieved at 1 minute at the location where the test patch contacted the defect, as shown in FIG. Fig. 10B shown. Fig. 10B It was also shown that areas of the defect that were not in contact with the test patch continued to bleed.
[0263] This example shows that the hemostatic patch prepared according to Example 1 significantly outperformed a commercially available fibrin sealant patch, achieving hemostasis at 1 minute and 3 minutes after placement in a porcine liver defect. The reactive precursor in the hemostatic patch allows for both flat and non-flat placement, and allows for a short period of manual compression after placement, resulting in a fast, adaptable, and easy-to-use patch for mild to severe bleeding defects in the liver.
[0264] Example 4: Liver defect study 2 (with comparative example)
[0265] This example evaluates the hemostatic effect of the hemostatic patch prepared according to Example 1 in a pig liver defect model and compares it with a commercially available fibrin sealant patch.
[0266] Part A. Test and Control Patches. A set of hemostatic test patches prepared according to Example 1 using substrate type A ("test patch A") were used in this study. Comparative sealant patches embedded with human fibrinogen and human thrombin ("control patch B") were purchased from Johnson and Johnson ( Fibrin sealant patch, 5.1 cm x 10.2 cm, product code EVT5024). Each patch was trimmed to approximately 2 x 2 cm size for application. The active side of the test patch was blue, and the active side of the control patch was yellow.
[0267] Part B. Animal defect model preparation. An acute (Yorkshire) pig was incised along the anterior (ventral) midline and the liver was isolated. The animals had the following characteristics: weight (57.4 kg); sex (F); anticoagulation (ACT: 294). The ACT was recorded before the first placement. Defects were created in both the left and right inner lobes of the liver. An 8 mm biopsy puncture was used to penetrate the liver to a depth of approximately 4 mm. Metzenbaum scissors were then used to remove the embolus created by the puncture. At this point, bleeding was assessed. Targets were 40% to 100% based on the Adam scale. > 3 is ideal. (See Fig. 9 ). If the target score is not reached, the liver is punctured again using the biopsy puncture device until the target score is reached. The defect bleeding score generated by each test is recorded as the initial score, as shown in Table 11 and Table 12. All test patch A bleeding defects are severe. Control patch B bleeding defects are moderate (test 3-1C) or severe (test 3-2C, 3-3C and 3-4C). Use clean dry gauze to handle bleeding at the defect site.
[0268] Table 11
[0269]
[0270] Table 12
[0271]
[0272]
[0273] *During the hemostasis check, the patch came off along with the gauze.
[0274] **The patch subsequently fell off and the wound required re-treatment.
[0275] Section C. Patch Evaluation Procedures and Results 。This embodiment follows the procedure described in Part C of Example 2, wherein the modification is to perform the first scoring after 30 seconds. All test patch A samples adhere well to the target site and are not affected by the removal of wet gauze. In addition, when pulled / picked with tweezers, the edge of the test patch A sample cannot be pulled up. No leakage through any test patch A sample was observed. As shown in Table 11, all tests using test patch A achieved hemostasis within 30 seconds after placement.
[0276] The result of control patch B is shown in Table 12.Only one control patch B sample (control patch B test 3-4C) realizes hemostasis after 3 minutes.But, in the research later period, patch comes off, and bleeding restarts.The patch that comes off is located at thoracic cavity later.Other three control patch B tests show oozing out (control patch B test 3-1C and 3-2C) or appropriate bleeding (control patch B test 3-3C) when 3 minutes.During removing wet gauze, need to be extremely careful not to disturb control patch.When evaluating at 3 minutes, observe that control patch B only adheres to wound in the position of active bleeding.The control patch region beyond wound does not adhere to tissue, and remains as the skin flap of loose / protuberance.
[0277] Part D. Additional patch evaluations. In addition, test patch A was additionally evaluated using multiple non-flat (convex) placements on partially excised liver lobes. Placements were pre-moistened 2×4 cm patches, 2×4 cm dry patches, and 2×2 cm dry patches. It was observed that applying pressure to the dry patches was less difficult than with the pre-moistened patches because there was less slippage. After placement of all three patches, hemostasis of the entire defect was achieved. Each placement achieved hemostasis of the area in contact with the corresponding patch.
[0278] This embodiment shows that the hemostatic patch prepared according to Example 1 is significantly better than the commercially available fibrin / thrombin sealant patch, and is positioned at the pig liver defect after 30 seconds, 1 minute and 3 minutes to achieve the hemostasis of appropriateness to severe bleeding. Although the fibrin / thrombin sealant patch has reactive substances (thrombin), the patch is not actually closed wound like the hemostatic patch. The peeling test at the hemostatic patch edge shows no stratification, and the fibrin / thrombin patch is only attached to the wound site. In four tests twice, the control patch came off.
[0279] Example 5: Cardiovascular Defect Study
[0280] This example evaluates the hemostatic effect of the hemostatic patch prepared according to Example 1 after various placements in a porcine cardiovascular defect model.
[0281] Part A. Testing patches. A set of hemostatic patches prepared using substrate type A according to Example 1 ("Test Patch A") were used in this study. All placements were performed with the patches dry. After placement, the patches were made flexible by either hydrating the patches directly with saline or by applying pressure with pre-moistened gauze.
[0282] Part B. Preliminary preparation of animal defect model.A 60 kg acute (Yorkshire) sow was used in this study. An incision was made in the skin on the ventral midline of the neck to expose the carotid artery. Blunt dissection was performed through the underlying subcutaneous tissue and muscle. The muscle was retracted and the fascia surrounding the target vessel was dissected from the vessel surface. The side branches of the vessel were ligated with silk suture material and clips. After obtaining proximal and distal control of the artery using a vascular ring and a vascular clamp, the vessel was temporarily occluded. An arteriotomy was performed and the graft material (Gore Acuseal) was anastomosed in an end-to-end manner using non-absorbable sutures. After the anastomosis was completed, blood flow was reestablished by removing the vascular ring and vascular clamp.
[0283] An inguinal incision was made to expose each femoral artery. Blunt dissection was performed through the underlying subcutaneous tissue and muscle. The muscle was retracted, and the fascia surrounding the target vessel was dissected from the vessel surface. The side branches of the vessel were ligated with silk suture material and clips. After obtaining proximal and distal control of the artery using a vessel loop and vascular clamp, the vessel was temporarily occluded.
[0284] Part C. Defect creation, patching procedure, and outcomes.
[0285] Procedure 1: Femoral artery placement. Blood flow was stopped in a 3-5cm section of the left femoral artery using a clamp and a vascular ring. Four vascular punctures were performed using a 25-gauge needle to simulate the sutures of a vascular repair procedure. The artery was loosened to ensure that a bleeding defect had been created, and the bleeding was graded using the Adam scale. Pulsatile bleeding was determined to be severe (Adams scale rating of 4). The artery was re-clamped to stop blood flow, and the blood pooling in the area was cleared. Test patch A was cut into approximately 1×1.7cm. The dry test patch was placed on top of the defect site in a manner covering the defect, with the blue side bleeding toward the target. Manual pressure was applied to the test patch using a pre-moistened gauze sheet for 30 seconds. Blood flow in the area was then restored by removing the vascular ring and clamp. After 30 seconds of manual pressure, the gauze was removed. The hemostasis and adhesion of the patch were evaluated. Arterial blood flow was confirmed by checking the pulse on both sides of the placed patch. It was observed that the site was hemostatic 30 seconds after the patch was placed, and good adhesion to the surrounding tissue was achieved. Approximately 1 hour after placement, the hind leg was "mobilized" to simulate movement. During and after this movement, the patch remained adhered to the defect and surrounding tissue. Pulses were found on both sides of the placed patch (distal and proximal).
[0286] Procedure 2: Femoral artery placement during pulsatile flow. Perform the operation at the same site described in procedure 1, using a 25-gauge needle to perform a puncture on the blood vessel proximal to the defect in procedure 1. Pulsatile puncture bleeding was determined to be severe (Adams scale rating of 4). The puncture was immediately covered with manual pressure until the patch was about to be placed. Remove the manual pressure, and immediately place a dry patch of approximately 1.5×2cm size on top of the active bleeding site. Use a pre-moistened gauze piece to apply manual pressure to the patch for 30 seconds. After 30 seconds of manual pressure, remove the gauze. Evaluate the hemostasis and adhesion of the patch. Arterial blood flow is confirmed by checking the pulse on both sides of the placed patch. It was observed that the site stopped bleeding 30 seconds after the patch was placed, and good adhesion to the surrounding tissue was achieved. About 1 hour after placement, the hind legs were "activated" to simulate movement. During and after this movement, the patch remained adhered to the defect and surrounding tissue. Pulses were found on both sides (distal and proximal) of the placed patch.
[0287] Procedure 3: Femoral artery wrap placement. Use clamps and vascular rings to stop blood flow in a 3-5cm section of the right femoral artery. Use a scalpel to create a small longitudinal defect along the artery. Use 2-3 sutures to suture the defect. Confirm the bleeding defect by removing the proximal clamp and rate it as severe pulsatile bleeding. Reapply the clamp to stop blood flow and remove the blood in the area. Place a dry patch under the defect site with the blue side facing up. The patch is then moistened with saline and wrapped around the defect site so that the blue side is in contact with the target bleeding. Apply manual pressure on the patch using a pre-moistened gauze piece for 30 seconds. After 30 seconds of manual pressure, remove the gauze. Evaluate the hemostasis and adhesion of the patch. Arterial blood flow is confirmed by checking the pulse on both sides of the placed patch. It was observed that the site stopped bleeding 30 seconds after the patch was placed, and good adhesion to the surrounding tissue was achieved. About 15 minutes after placement, the hind legs were "activated" to simulate movement. During and after this movement, the patch remained adhered to the defect and surrounding tissue. Pulses were found on both sides (distal and proximal) of the placed patch.
[0288] Procedure 4: Placed on bleeding sutures. Heparin was administered to the animals, and the procedure was completed with anticoagulated blood. The right carotid artery was isolated, and the graft material (Gore Acuseal, ECH060020A) was anastomosed in an end-to-end manner. As active blood flowed through the artery and the graft material, a bleeding area was created by manipulating / removing the suture at the distal anastomosis. Bleeding was assessed as 3 (moderate) using the Adam scale. Two (2×2 cm) test patches A were placed along the suture patch to cover the defect, with the blue side bleeding toward the target. Manual compression was performed using a pre-moistened gauze sheet, and the manual compression was maintained for 30 seconds. After 30 seconds of manual compression, the gauze was removed and the hemostasis and adhesion of the patch were evaluated. After 30 seconds, hemostasis was achieved. The patch adhered to the suture, but had little adhesion to the graft material. It was observed that the closure of the suture after anticoagulation was as good as before anticoagulation.
[0289] Procedure 5: Placement on graft defect. This procedure is done with anticoagulated blood. Perform the procedure at the same site as described in Procedure 4, using a No. 14 needle to puncture the graft material. The puncture is evaluated to ensure a steady, moderate flow of blood from the defect (Adams score of 3). Test patch A is placed on the graft defect. Manual pressure is applied to the patch using a pre-moistened gauze pad for 30 seconds. After 30 seconds of manual pressure, the gauze is removed. The patch is evaluated for hemostasis and adhesion. After 30 seconds, it was observed that the target bleeding began to close. It was observed that the patch had little adhesion to the graft material. The patch was able to be pulled up from the bleeding site with tweezers.
[0290] The study showed that placement of test patch A successfully closed common defects in cardiovascular surgery, including pulsatile femoral artery perforation and end-to-end anastomosis between the carotid artery and the graft material. All applications of test patch A achieved hemostasis (or closure) 30 seconds after placement or before. After hind limb flexion, the patch remained stable and adhered to the tissue at the placement site. The patch successfully controlled bleeding from the graft material. In addition, after heparin was administered to the animals, the patch closure performance remained consistent.
[0291] Example 6: Orthopedic and Cardiovascular Defect Studies
[0292] This example evaluates the hemostatic efficacy of the hemostatic patch prepared according to Example 1 after various placements in an acute, non-GLP porcine orthopedic and cardiovascular defect model.
[0293] Part A. Testing patches. A set of hemostatic patches prepared using substrate type A according to Example 1 ("Test Patch A") was used in this study. All placements were performed with the patch dry and pressure applied by wet gauze. Both 2×2 cm and 2×4 cm patches were used. After placement, the patch was made flexible by applying pressure with pre-moistened gauze.
[0294] Part B. Initial preparation of the animal defect model. A 27kg acute (Yorkshire) boar was used in this study. An incision was made in the skin to expose the tibial diaphysis. Blunt dissection was then performed through the underlying subcutaneous tissue and muscle. The muscle was retracted and the fascia surrounding the target site was dissected from the bone surface. A dental drill with an approximately 2-3mm ball drill bit was used to create a target cortical hemorrhagic defect. The defect was irrigated with saline to remove debris and avoid tissue heating during creation.
[0295] An incision is then made in the skin to expose the femoral condyle. Blunt dissection is then performed through the underlying subcutaneous tissue and muscle. The muscle is retracted and the fascia surrounding the target site is dissected from the bone surface. A dental drill with an approximately 2-3 mm ball drill bit is used to create a target cortical hemorrhagic defect. The defect is irrigated with saline to remove debris and avoid tissue heating during creation.
[0296] Finally, an inguinal incision is made to expose each femoral artery. Blunt dissection is performed through the underlying subcutaneous tissue and muscle. The muscle is retracted, and the fascia surrounding the target vessel is dissected from the vessel surface. The side branches of the vessel are ligated with silk suture material and clips. After obtaining proximal and distal control of the artery using a vessel loop and vascular clamp, the vessel is temporarily occluded.
[0297] All bleeding assessments were performed using the Adams scale.
[0298] Part C. Defect creation, patching procedure, and outcomes.
[0299] Procedure 1: Tibial diaphyseal defect. A defect of about 3 mm in diameter and about 4 mm in depth was created on the tibial diaphyseal using a dental drill and a ball drill bit. Bleeding was confirmed and assessed to be very mild (Adams score of 1). The patch was cut into approximately 1×2 cm sheets. The patch was placed in a manner covering the defect with the blue side facing the target bleeding. Manual pressure was applied to the patch using a pre-moistened gauze pad for 30 seconds. After 30 seconds of manual pressure, the gauze was removed. The patch was evaluated for hemostasis and adhesion. It was observed that the site was closed 30 seconds after the patch was placed. The site was observed over time, and there was evidence that bleeding continued under the patch, but the site remained closed and the patch remained well adhered.
[0300] Procedure 2: Large defect of tibial diaphysis. Operate at the same site described in procedure 1, using a dental drill and a ball drill bit to produce a large defect of about 6mm in diameter and about 9mm in depth on the tibial diaphysis. Confirm bleeding and assess it to be very mild (Adams score of 1). Use a 6mm biopsy puncture to cut a 2×2cm patch into discs that match the size of the defect. Use forceps to place two of these discs in the defect, with the blue side of the first patch toward the target bleeding at the bottom of the defect. Each subsequent patch is stacked on top of the previous patch, with the blue side against the previous patch. Place these patches to address wall bleeding from the defect produced. Use a pre-moistened gauze sheet to apply manual pressure to the top patch for 30 seconds. After 30 seconds of pressurization, remove the gauze. Evaluate hemostasis and patch adhesion at this site. It was observed that hemostasis was achieved 30 seconds after the patch was placed.
[0301] Procedure 3: Femoral condyle defect. A defect with a diameter of about 6 mm and a depth of about 3 mm was created on the femoral condyle using a dental drill and a ball drill. Bleeding was confirmed and assessed to be very mild (Adams score of 1). A 2×2 cm test patch A piece was cut into a disc matching the defect size using a 6 mm biopsy puncture. The disc was placed in the defect using tweezers, with the blue side of the patch bleeding toward the target. Using the plunger from a 1 ml syringe, pressure was applied to the patch with a pre-moistened gauze piece for 30 seconds. After 30 seconds of pressurization, the gauze was removed. Hemostasis and patch adhesion at the site were assessed. Hemostasis was achieved 30 seconds after the patch was placed.
[0302] Procedure 4: Deeper defect of femoral condyle. A defect with a diameter of about 6 mm and a depth of about 9 mm was produced on the femoral condyle using a dental drill and a ball drill. Bleeding was confirmed and assessed as mild (Adams score of 2). A 2×2 cm test patch A sheet was cut into discs using a 6 mm biopsy puncture. Four of these discs were placed in a matching manner within the defect, with the blue side of the first patch toward the target bleeding at the bottom of the defect. Each subsequent patch was stacked on top of the previous patch, with the blue side against the previous patch. These patches were placed to address wall bleeding from the defect produced. Using the plunger from a 1 ml syringe, pressure was applied to the patch with a pre-moistened gauze sheet for 30 seconds. After 30 seconds of pressurization, the gauze was removed. Hemostasis and patch adhesion at the site were assessed. Hemostasis was achieved 30 seconds after the patch was placed.
[0303] Procedure 5: Femoral artery suture defect. Use clamps and vascular rings to stop blood flow in a 3-5cm section of the femoral artery. Use a 25-gauge needle to perform two vascular punctures to simulate the sutures of a vascular repair procedure. Loosen the artery to ensure that a bleeding defect has been created, and the bleeding is graded using the Adams scale. Pulsatile bleeding is assessed as severe (Adams score of 4). Re-clamp the artery to stop blood flow, and remove the accumulated blood in the area. Cut a piece of gauze and moisten it with clean saline. Place a 2×4cm patch on top of the wet gauze with the blue side facing away from the gauze. Then slide the patch / gauze pair under the artery with the blue side of the patch bleeding toward the target. The user holds both ends of the gauze and lifts them toward each other until both ends of the gauze touch. Then, apply pressure to the area where the patch-patch contacts ("tail") so that the central area of the patch is wrapped around the blood vessel and the tails of the patch adhere to each other. Note to ensure that the channel formed by the two tails is not directly on the bleeding site. Then apply manual pressure to the patch by gauze, continue 30 seconds.After manual pressurization for 30 seconds, remove gauze.Then restore the blood flow in the area by removing the vascular ring and clamp.Confirm arterial blood flow by checking the pulse on both sides of the patch placed.Then assess the hemostasis and adhesion of the patch.Trimming the tail of the patch with Mei Zengbao (Metzenbaum) scissors makes the length of the patch part along the artery leave about 2-3mm tail.Observe that the application site stops bleeding in 30 seconds, realizes good adhesion with the artery, and pulse is found on both sides of the far end and proximal end of the patch.
[0304] Procedure 6: Contralateral Femoral Artery Defect. The procedure described in Procedure 5 was applied to the contralateral femoral artery. The resulting pulsatile bleeding defect was assessed as severe (Adams score of 4). Again, hemostasis was observed at the application site at 30 seconds, good adhesion to the artery was achieved, and pulses were found on both the distal and proximal sides of the patch.
[0305] Another study evaluated Test Patch A in chronic ovine carotid artery occlusion using a patch closure model. After 7 days of implantation in the model, Test Patch A resulted in stable vascular repair without any signs of bleeding on angiographic assessment.
[0306] The study showed that placement of Test Patch A successfully closed condylar and diaphyseal bone defects (where bleeding was very mild to mild) as well as bilateral pulsatile femoral artery defects (where bleeding was severe). In each case, hemostasis (or closure) was achieved at or before 30 hours after placement of the dry patch. Pressure was successfully applied to the patch placed in the deeper bone defect using a syringe plunger. An alternative wrap placement method was successfully used to treat pulsatile femoral artery perforations.
[0307] Example 7: Combined study of soft organs and orthopedic defects
[0308] This example illustrates the use of a soft organ and orthopedic patch in a patient.
[0309] Part A. Test patches and control products. This study used three types of hemostatic patches prepared according to Example 1 using substrate type A ("test patch A"), substrate type B ("test patch B"), and substrate C ("test patch C"). The control product was a 2 mm thick water-insoluble porcine gelatin sponge ( Absorbable gelatin sponge, Johnson and Johnson, product code 1975), to which recombinant thrombin (Baxter, ) ("Control Patch C"). Dry placement and pre-moistened placement were attempted for each sample.
[0310] Part B. Animal defect model preparation. In a training laboratory setting, surgeons were provided with the patches described in Part A. An acute (Yorkshire) pig was incised along the anterior (ventral) midline and the liver was isolated. The animals had the following characteristics: weight (48.2 kg); sex (M); anticoagulated (ACT: 242). The ACT was recorded prior to the first placement. Defects were created in the spleen and in both the left and right inner lobes of the liver. An 8 mm biopsy puncture was used to penetrate each organ, initially to a target depth of approximately 7 mm. Subsequently, a target depth of approximately 2 mm was used. Metzenbaum scissors were then used to remove the embolus created by the puncture. At this point, bleeding was assessed. Target depth was 40 mm based on the spot grade SBSS. > 3 is ideal. If the target bleeding score is not achieved, the organ is penetrated again with the biopsy needle until the target score is achieved. Bleeding defects are moderate to severe. Before placing the product, use clean dry gauze to treat bleeding from the defect site.
[0311] Section C. Patch Evaluation Procedures and Results . Use clean sterile saline to moisten clean gauze. Place the test patch sample back to the wet gauze so that the blue surface of the patch is back to the gauze. Remove the gauze for handling bleeding from the defect site. Immediately place the patch on the defect site so that the blue side of the patch contacts the defect and is located in the center of the defect as much as possible. Use an open hand to apply strong and uniform pressure to the back side of the patch with wet gauze, and hold for 30 seconds. Then, carefully reduce the pressure, and carefully remove the gauze from the back surface of the applied patch. If there is any adhesion of gauze to the patch, a clean surgical instrument is gently applied to the edge of the patch, or the gauze is separated from the patch using gentle rinsing while minimizing interference. After the 30-second evaluation period, the 30-second bleeding score is recorded according to the spot grade SBSS. Then, use a pair of tweezers to gently pick up the edge of the patch to test adhesion. Repeat the procedure for each patch sample. Use an improved procedure for each patch sample, in which the patch is placed without pre-moistening with gauze.
[0312] Part D. Observation.
[0313] Test patch A causes hemostasis at each application. When pressure is applied to hollow defect and when patch is pre-moistened (rather than dry application on hollow organ defect), the closure of defect is more effective. Application of pre-moistened patch causes patch not to bulge / protuberance, and blood red core is not formed on the patch on hollow defect. Test patch B provides a result similar to test patch A, and causes hemostasis at each application. The application of test patches A and B successfully improves the surgeon's experience of the length of time after patch and patch placement. Tried multiple test patch C samples, but in each case the patch adheres to gauze during placement. Removing gauze causes substrate tearing, which causes bleeding again. Control patch C is successfully used to produce hemostasis in both liver and spleen. However, control patch C is poor in adhesion to tissue, and there is a surgeon's worry about the high risk of product coming off. Test patch and control patch are all swollen due to the blood under the patch / product at the defect site and show "dome effect". By applying pressure to the applied patch / product, the dome effect is generally avoided.
[0314] The results show that test patch A and test patch B provide good adhesion to tissue and rapid hemostasis in relatively easy-to-use patches. Test patch C cannot achieve sustained hemostasis through the process of use. The substrate porosity of test patch C is too high and is considered to be related to excessive blood flowing through the active surface from the defect and entering the substrate because the hydrogel can migrate through the highly porous substrate. This study shows that the active surface composition used with a suitable substrate contributes to the performance and usability of the patch. Control patch C fails to achieve good adhesion to tissue.
[0315] Example 8: Simulated cervical defect study
[0316] This example illustrates the use of a tapered mandrel to create hemostasis in a simulated cervical defect.
[0317] Part A. Testing patches. A set of conical hemostatic patches were prepared using substrate type A according to the general procedure of Example 1. The patches were further shaped into a cone by the following series of manufacturing steps: The patches were cut along one side to near the center of the patch. Then they were slightly heated and shaped into a roughly conical shape. The overlapping cut portions were then fixed together to stabilize the shape until the PEG cooled.
[0318] Part B. Animal defect model preparation.An acute (Yorkshire) pig was opened to isolate the pig abdominal wall. Prior to the first placement, the anticoagulation ACT was over 300. An 8 mm biopsy puncture was used to penetrate the lateral abdominal wall to a target depth of approximately 7 mm. Metzenbaum scissors were then used to remove the embolism produced by the puncture. At this point, bleeding was assessed. A bleeding of 3 according to the spot grade SBSS was achieved. Before placing the product, bleeding from the defect site was treated with clean dry gauze.
[0319] Section C. Patch Evaluation Procedures and Results . Place the test patch sample on the defect so that the blue surface of the tapered patch faces the defect. Hold the handle of the mandrel and press the tapered portion of the mandrel with the tapered patch into the defect. Apply gentle but constant pressure to the patch through the mandrel for 30 seconds. Then, carefully reduce the pressure and carefully remove the mandrel from the convex (dorsal) surface of the applied patch. Some adhesion of the patch to the mandrel was observed, and the mandrel was separated from the patch using a clean surgical instrument while minimizing interference. After the 30-second evaluation period, hemostasis was evaluated. An improved procedure was used in the second application, in which a wet gauze piece was placed between the tapered patch and the mandrel before the patch was pressed into the defect with the mandrel. During the removal of the mandrel and gauze from the applied patch, no adhesion of the patch to the mandrel or gauze was observed. After the 30-second evaluation period, hemostasis was evaluated.
[0320] Part D. Observation.
[0321] Hemostasis and good adhesion of the patch to the defect were achieved at 30 seconds using both applications. Although adhesion of the patch to the handle in the first application resulted in loss of hemostasis when the handle was removed, the improved placement procedure used in the second application resulted in maintenance of hemostasis after the handle was removed. The results indicate that shaped handles can be used to place preformed patches in locations that are not easily accessible by direct manual application ("remote locations"). The results also indicate that preformed patches and corresponding shaped handles can be advantageously used to help align, place, and apply preformed patches to remote locations and non-remote locations. The shaped handles allow more consistent pressure to be applied to the entire surface of the preformed patch in contact with the defect. Applying consistent pressure promotes rapid hemostasis by reducing the likelihood of bleeding beneath the patch. Based on the findings, it is expected that the tapered patch with the corresponding tapered handle will be suitable for achieving hemostasis of cervical bleeding defects, such as Fig. 12A and 12B shown.
[0322] Example 9: Preparation of a flexible hemostatic patch with a compressed substrate
[0323] This example describes a compression method for preparing a flexible hemostatic patch.
[0324] Part A. Substrate Compression Test.
[0325] Two types of substrates were used in this study, as shown in Table 13. Both substrate E and substrate F were foamed gelatin / collagen substrates obtained from different commercial suppliers. The commercial foamed gelatin substrates were heat crosslinked in an oven for several hours according to the above time and temperature ranges. The substrate samples were approximately 10 cm wide, 20 cm long, and 7 mm thick.
[0326] Table 13
[0327] Substrate Type characteristic Initial thickness E Foamed Gelatin / Collagen 7mm F Foamed Gelatin / Collagen 7mm
[0328] Calendering rollers were used to compress substrates E and F. For convenience, compression was performed using pasta rollers, which were set to correspond to a distance (ie, gap) between the near surfaces of the calendering rollers of about 5 mm. Fig.15A and 15B SEM images of the surface of a sample of substrate E before and after compression, respectively. Fig. 15C and 15D are SEM images of the surface of a sample of substrate F before and after compression, respectively. Figures 15A-15D was captured by backscattering using 25× magnification. The difference between the pore structures of substrate E and substrate F before compression can be seen in Fig.15A and 15C Although Fig.15A and 15C A range of apertures are shown, but generally, Fig.15A Macropore ratio Fig. 15C In addition, the material support around the macropores in the matrix E ( Fig.15A ) than the material support around the pores in the matrix F ( Fig. 15C ) is significantly thinner. Fig. 15B , after compression, the pore structure of substrate E appears to collapse and rupture, and generally lacks Fig.15A Thin stent material shown. Fig.15D , after compression, the pore structure of substrate F appears to be that of the uncompressed sample ( Fig. 15C ) is a similar but more dense version of the . Table 14 shows the Figures 15A-15D The average pore area fraction and average pore size of the SEM images. The measurement of the average pore area fraction is semi-quantitative because both the pores at the image surface and some pores below the image surface are captured. The data in Table 14 show that the average pore area fractions are similar for the uncompressed and compressed samples. The results show that there are significant differences in the foam / scaffold structure between Substrate E and Substrate F.
[0329] Table 14
[0330]
[0331] The fluid absorption, flexural strength, shear force, compression force and conformability of a group of substrate E samples before and after compression were further evaluated. For each measurement, the results of ten replicates were recorded, as shown in Table 15. Fluid absorption was tested by weighing each of ten uncompressed samples when dry (initial dry weight) and after soaking in saline for 15 seconds (final weight). The fluid absorption of each sample was calculated as (final weight-initial dry weight) / initial dry weight 100%. The average fluid absorption of uncompressed substrate E was recorded as the average value of the fluid absorption of 10 uncompressed samples. Ten dry uncompressed samples of substrate E were subjected to 3-point bending tests respectively by using a texture analyzer machine (model TA-XT Plus C) equipped with a 3-point bending device, and flexural strength was measured according to ASTM D790-17 (incorporated herein by reference). Each test sample was approximately 2.5 cm wide and 6.5 cm long. The maximum shear force was measured by loading the dry uncompressed test sample as a cantilever and applying force. The maximum shear force was recorded as the force when ruptured. Each test sample was approximately 2.5 cm wide and 6.5 cm long, with 1 cm held by the test grip. The column strength (or maximum compressive force) was measured by uniaxial compression of ten dry, uncompressed samples of substrate E using a texture analyzer machine (model TA-XT Plus C). Each test sample was a 2.5 cm wide, 7.5 cm long dog bone test sample. The column strength was recorded as the force at break. Conformity was tested by wrapping the dry sample around a 1 / 2 inch mandrel. The absence of cracking or breaking of the sample during the test indicated that conformity was positive, and the results were recorded as the ratio of the number of positive samples in every 10 test samples. The average thickness of each sample was measured with a caliper.
[0332] The above test was repeated using a group of 10 compressed substrate samples for each test. The results are shown in Table 15. The average measured values of the uncompressed substrate samples were compared with the average measured values of the compressed substrate samples, indicating that there was basically no change in fluid absorption (360% relative to 356%), but the mechanical properties of the samples showed changes. The average flexural strength, shear strength and column strength of the compressed samples were low, but all compressed samples (10 / 10) were conformable to a 1 / 2 inch diameter mandrel. Only 3 of the 10 uncompressed samples were conformable to the same 1 / 2 inch mandrel test. The results show that the compression of the substrate imparts flexibility / conformity to the substrate without changing the fluid absorption. In addition, the results show that the compressed samples retain a greater percentage of the original compression and tensile strength compared to the shear strength (maximum shear force), as shown in the column strength and flexural strength measurements. The shear strength of the compressed sample is about 10% of the shear strength of the uncompressed sample. This result shows that the compression of the calendered substrate E causes significant shear-induced rupture, but is still gentle enough to allow the substrate to remain relatively hard. The results show that compression (especially by calendaring) can impart flexibility to the cross-linked gelatin substrate through pore structure collapse without measurable fluid absorption loss and without significant stiffness loss. The results also show that the thickness variability of the compressed substrate samples is lower than the thickness variability of the uncompressed substrate samples.
[0333] Table 15
[0334]
[0335] Additional fluid uptake data was collected over time for both the uncompressed and compressed samples. Fig.19 The average fluid uptake for substrate samples immersed for 15 seconds, 1 minute, 5 minutes, or 10 minutes is shown. At 20 hours (not shown), the average fluid uptake for the uncompressed substrate samples and the compressed substrate samples was about 1200%. The results show that the substrate initially rapidly absorbs the fluid, with the absorption leveling off at about 10 minutes. The average fluid uptake percentages for the uncompressed substrates and the compressed substrates were generally within the measurement error at a given measurement time.
[0336] Part B. Coated Substrate Processing and Testing.
[0337] The coated substrates were prepared by coating a dry blend solution of two hydrogel precursors onto a set of compressed samples of Substrate E. The substrate samples for coating were prepared by drying in an oven at a temperature of 35°C under ambient air for 18 hours or until the relative humidity of the oven was less than 5%. The thickness of each substrate sample after drying was approximately the same as the thickness before drying. For each coated substrate sample, the first hydrogel precursor was an eight-arm polyethylene glycol-based precursor having a molecular weight of 15,000 Da and succinimidyl glutarate (SG) functional end groups (8A15k PEG SG, Jenkemusa). The second hydrogel precursor was an eight-arm polyethylene glycol-based precursor having a molecular weight of 20,000 Da and HCl salt amine functional end groups (8A20k PEG amine-HCl, Jenkemusa). The first and second precursors were measured in powder form and then melt blended with trace amounts of FD&C Blue #1 in a heated roller system at a temperature above 45°C in a glove box. The molten precursor blend is delivered to a liquid distribution system (FOM Coater, FOM Technologies). Under inert gas conditions, a single layer coating of the melt blend is applied to each substrate sample. Precursors are applied by a heated slot die head, which is located at a gap of 4.5mm above the bottom surface of a substrate of about 5mm thickness. Through this process, the coating of the substrate involves injecting the melt blend into the substrate, because the slot die head compresses the substrate. The average thickness of the precursor impregnation region ("precursor / substrate network region") of each substrate is about 0.25mm, usually to extend at least about 0.05mm above the substrate surface. The mixed precursor coated substrate is solidified at room temperature under inert gas conditions. The thickness of each of the coated substrates obtained by measuring is about 5.25mm.
[0338] One of the coated substrates (Sample 1) was retained as the "uncompressed sample", while the remaining coated substrate samples (Samples 2-4) were subjected to post-coating compression using calendar rollers. Fig.16A -D show SEM images of representative portions of the surfaces of samples 1-4, respectively. For the uncompressed sample (sample 1), Fig.16A The coated samples have relatively non-uniform cracks on the surface, which is consistent with Fig. 16B -D, which includes some relatively large cracks. (Note that Fig.16A The magnification is lower than Fig. 16B -D. ) Fig.16A The large cracks seen in are a result of sample handling / shipping and indicate that the cured precursor is rigid and brittle after coating if strain relief is not provided. Fig.16AThe cured precursor in (Sample 1) was brittle, but the precursor was observed to adhere well to the substrate. For Samples 2-4, post-coating compression was performed using pasta rollers, which were set to correspond to the distance (i.e., gap) between the near surfaces of the calendering rollers. One coated sample (Sample 2, Fig. 16B ) was compressed at a setting corresponding to a gap of about 5 mm. Another coated sample (Sample 3, Fig. 16C ) was compressed at a setting corresponding to a gap of about 2 mm. Another coated sample (Sample 4, Fig.16D ) was compressed in two steps by first compressing at a gap of about 5 mm and then compressing at a gap of about 2 mm. Fig. 16B -D shows that compression of the coated substrate introduced surface cracks, where direct compression with a 2 mm gap (Sample 3, Fig. 16C ) introduces obvious surface cracks. SEM image of sample 4 ( Fig.16D ) suggests that two-step compression can provide more consistent fractures by releasing some strain using the first compression step and introducing additional cracks by the second compression step. SEM images of samples 2-4 ( Fig. 16B -D) qualitatively shows that the brittleness of compressed samples 2-4 is lower than that of uncompressed sample 1 ( Fig.16A ), because it does not exist Fig.16A Uneven / wide cracks shown. All samples showed good adhesion of the precursor to the substrate, including during handling / transport.
[0339] Fig.17A and 17B SEM images of cross sections of representative portions of Sample 1 and Sample 2 are shown. Uncompressed Sample 1 ( Fig.17A ) and compressed sample 2 ( Fig. 17B ) have an underlying substrate similar to the uncompressed substrate and compressed substrate described in Part A. In particular, the underlying substrate of Sample 1 ( Fig.17A ) shows relatively large pores surrounded by a thin gelatin scaffold. The lower substrate of sample 2 ( Fig. 17B ) shows a collapsed / broken pore structure. The precursor / substrate network region ("network") of Sample 1 was measured to be approximately 200-230 microns thick. The precursor / substrate network region of Sample 2 was measured to be approximately 170-320 microns thick. The wider range of network thicknesses for the compressed samples appears to be related to compression, which causes the precursor to be more broken and more integrated into the substrate, and thus results in an overall wider range of network cross-sectional footprints. Fig.17A and 17B It is also shown that the precursor infiltrates relatively uniformly across the substrate surface. The precursor does not completely penetrate the substrate.
[0340] In addition to the above tests, the effect of the coating on a compressed substrate versus an uncompressed substrate was also studied. Fig.18A and 18B A coated substrate prepared as described above is shown, except that the coating was applied to an uncompressed substrate E. Fig.18A and 18B The white areas in the graph are areas that are not fully covered by the precursor coating. Fig.18C A coated substrate is shown where the coating is applied to a compressed substrate E. There are no white areas and the blue coating is evenly distributed, even along the edge-to-edge exclusion boundary. (Note that Fig.18A -The image in C was taken through the glass of the glove box and therefore there are some reflections in the image. )
[0341] The result of the research of this part shows that compression coating patch is presented at more cracks in the network based on PEG than uncompressed patch.Compression coating patch also shows that precursor precursor is more penetrated into the basal layer, and this shows that stratification can reduce (i.e. the adhesion of precursor to substrate will improve).In addition, the result of this research shows that pre-coating compression can be used for removing depression and other inconsistencies in substrate before coating, and this can improve coating consistency visually.
[0342] Part C. Patch Testing.
[0343] Four coated substrate samples were prepared using the method described in Part B. Two of the samples (patch samples 1 and 2) were not compressed. Two of the samples (patch samples 3 and 4) were compressed using a calendering roller that was 5 mm in gap. For all patch samples, precursor was well adhered to substrate. There was no evidence to show that precursor peeled off from substrate during treatment.
[0344] The 8mm biopsy puncture device is used to cut each patch sample into 8mm disk test specimens after these preliminary observations, and test burst pressure.Table 16 shows the burst pressure results.Patch samples 1 and 2 (uncompressed) and patch samples 3 and 4 (compression) have similar average burst pressure results, but the standard deviation of the burst pressure results of compressed samples is lower.This result shows that compression can improve the consistency of patch performance.The consistency of improvement may be due to the more collapse of the pore structure of substrate, the reduction of substrate thickness variability, the consistency improvement of precursor / substrate network, the flexibility / conformity of hemostatic patch increase and / or the adhesion improvement of precursor and substrate.
[0345] Table 16
[0346]
[0347] The results of this study show that the compression of the cross-linked gelatin substrate during coating with the precursor melt blend produces a consistent and cohesive precursor / substrate network at the substrate top surface. The precursor adheres to the substrate and does not peel off from the substrate during processing / transportation. The results of this study further show that compression can be used to increase flexibility / conformity and improve the performance consistency of the hemostatic patch without causing measurable changes in fluid absorbency or burst pressure. The results show that compression of the hemostatic patch alleviates some variability associated with applying the patch to the target surface by manual compression, which helps to better adhere to the target surface and higher burst strength. The results also show that the shear force introduced by calendering compression can help improve flexibility and performance. The results also show that two-step or multi-step compression process will be advantageous. In particular, the results show that the initial compression of the exposed substrate is carried out to cause hole rupture / collapse, and then a second compression is carried out after coating to further rupture / collapse the holes of the substrate and also rupture the coating.
[0348] The above embodiments are intended to be illustrative and not restrictive. Additional embodiments are also within the scope of the claims. In addition, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes can be made in form and detail without departing from the spirit and scope of the present invention. Any incorporation of the above documents by reference is limited so that no subject matter contrary to the explicit disclosure herein is included. Within the scope of the specific structures, compositions and / or processes with components, elements, ingredients or other partitions described herein, it should be understood that the disclosure herein covers specific embodiments, including embodiments of specific components, elements, ingredients, other partitions or combinations thereof, and embodiments consisting essentially of such specific components, ingredients or other partitions or combinations thereof, which embodiments may include additional features that do not change the basic properties of the subject matter, as suggested in the discussion, unless otherwise explicitly stated. The term "about" used herein refers to the expected uncertainty of the associated value understood by a person of ordinary skill in the art in a specific context. For the range set presented by any parameter herein, these should be interpreted as also explicitly reciting the associated range, wherein the lower limit of one range is combined with the upper limit of another specific range.
Claims
1. A medical patch comprising a biocompatible substrate and a dried hydrogel precursor layer on the substrate, the dried hydrogel precursor layer comprising an electrophilic hydrogel precursor having a plurality of electrophilic functional groups and a nucleophilic hydrogel precursor having a plurality of protonated amine groups and no more than about 2 wt % of water, and wherein both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncrosslinked and are blended or in direct contact with each other. 2 . The medical patch of claim 1 , wherein the dried hydrogel precursor layer comprises a blend of the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor.
3. The medical patch according to claim 1 or claim 2, wherein the substrate persists in an in vitro physiological solution maintained at 37°C for less than 30 days.
4. The medical patch according to claim 1 or claim 2, wherein the substrate persists in an in vitro physiological solution maintained at 37°C for less than 2 weeks.
5. The medical patch according to any one of claims 1 to 4, wherein the substrate is capable of absorbing 300 wt% to 3000 wt% of water.
6. The medical patch according to any one of claims 1 to 5, wherein the substrate comprises gelatin.
7. The medical patch of claim 6, wherein the substrate is partially thermally cross-linked, and wherein the substrate is a foam, a nonwoven tufted material, or a nonwoven felt material.
8. The medical patch of any one of claims 1-7, wherein the dried hydrogel precursor layer comprises multiple layers of a blend of the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor.
9. The medical patch of claim 8, wherein the dried hydrogel precursor layer is formed from a neat melt blend of the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor.
10. The medical patch according to any one of claims 1 to 7, wherein the dried hydrogel precursor layer comprises a stack of one or more sublayers of the electrophilic hydrogel precursor and one or more sublayers of the nucleophilic hydrogel precursor, wherein adjacent sublayers are in direct contact with each other.
11. The medical patch of any one of claims 1-7, wherein the substrate consists essentially of gelatin and the dried hydrogel precursor layer consists of a single solid layer consisting essentially of the electrophilic hydrogel precursor, the nucleophilic hydrogel precursor, and an optional imaging agent, wherein the imaging agent is biocompatible.
12. The medical patch of any one of claims 1-11, wherein the electrophilic hydrogel precursor has a first hydrophilic core comprising a polymer having a molecular weight of at least about 5000 Da, and wherein the nucleophilic hydrogel precursor has a second hydrophilic core comprising a polymer having a molecular weight of at least about 2500 Da.
13. The medical patch of claim 12, wherein the first hydrophilic core and the second hydrophilic core independently have a molecular weight of about 10K Da to about 25K Da and 4 to 8 arms.
14. The medical patch according to claim 12, wherein the first hydrophilic core and / or the second hydrophilic core comprises polyethylene glycol, polyvinyl alcohol, polyoxazoline, copolymers thereof or mixtures thereof or other water-soluble medical polymers having functional groups that can be modified, wherein the first hydrophilic core and the second hydrophilic core comprise the same polymer.
15. The medical patch according to any one of claims 1-14, wherein the plurality of arms for the electrophilic hydrogel precursor and the plurality of arms for the nucleophilic hydrogel precursor are independently 3 to 8, and wherein the first hydrophilic core and the second hydrophilic core comprise polyethylene glycol.
16. The medical patch according to any one of claims 1 to 15, wherein the electrophilic hydrogel precursor has an electrophilic functional group comprising an ester.
17. The medical patch of claim 16, wherein the ester is a succinimidyl ester.
18. The medical patch of any one of claims 1-17, wherein the ratio of electrophilic functional groups to protonated amine groups is no more than about 1.
19. The medical patch of any one of claims 1-18, wherein the ratio of electrophilic functional groups to protonated amine groups is about 1.
20. The medical patch of any one of claims 1-18, wherein the ratio of electrophilic functional groups to protonated amine groups is from about 0.95 to about 1.
05.
21. The medical patch of any one of claims 1-20, wherein the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are each water soluble.
22. The medical patch of any one of claims 1-21, wherein the medical patch further comprises a therapeutic agent.
23. The medical patch of claim 22, wherein the therapeutic agent comprises an analgesic, an anesthetic, a steroid, an antibiotic, a steroid, an anti-infective agent, an anti-inflammatory agent, a nonsteroidal anti-inflammatory drug, an anti-proliferative agent, or a combination thereof.
24. The medical patch of any one of claims 1-23, wherein the dried hydrogel precursor layer further comprises an imaging agent.
25. The medical patch of claim 24, wherein the imaging agent is biocompatible and comprises a colorant, a fluorescent molecule, a contrast agent, or a combination thereof.
26. The medical patch of claim 24 or claim 25, wherein the medical patch has a first side comprising the substrate and a second side comprising the dried hydrogel precursor layer and the imaging agent, wherein the first side is substantially free of the imaging agent.
27. The medical patch of any one of claims 1-26, wherein the medical patch is flexible and conformable when dry.
28. The medical patch of claim 27, wherein the patch can be rolled up for laparoscopic delivery through a trocar.
29. The medical patch of any one of claims 1-28, wherein the medical patch has a thickness of about 0.5 mm to about 5 mm, and a width and length independently of about 1 cm to about 15 cm.
30. The medical patch of any one of claims 1-29, wherein the medical patch is free of blood components and human body components.
31. The medical patch of any one of claims 1-30, wherein contact with a relevant physiological fluid causes the dried hydrogel precursor layer to form a hydrogel.
32. The medical patch of any one of claims 1-31, wherein the substrate does not adhere to surgical gloves or gauze moistened with a non-buffered solution when dry or wet.
33. The medical patch of any one of claims 1-32, wherein the medical patch has a storage stability against significant gelling under refrigerated conditions for at least about 1 year.
34. The medical patch of any one of claims 1-33, wherein contact with physiological fluids results in complete absorption of the medical patch in no more than about 28 days.
35. The medical patch of any one of claims 1-33, wherein contact with physiological fluids results in complete absorption of the medical patch in no more than about 9 days.
36. The medical patch of any one of claims 1-35, wherein the medical patch has a three-dimensional contoured shape.
37. The medical patch of claim 36, wherein the three-dimensional shape is a perfect cone or a truncated cone.
38. A wound packing composition comprising an amount of minced material from a patch according to any one of claims 1 to 37.
39. A medical patch comprising a biocompatible substrate and a dried hydrogel precursor layer on the substrate, the dried hydrogel precursor layer comprising a PEG-electrophilic hydrogel precursor and a PEG-nucleophilic hydrogel precursor and no more than about 2 weight percent water, the PEG-electrophilic hydrogel precursor having a plurality of arms having terminal reactive electrophilic groups, the PEG-nucleophilic hydrogel precursor having a plurality of arms having terminal protonated amine groups, and wherein both the PEG-electrophilic hydrogel precursor and the PEG-nucleophilic hydrogel precursor are substantially uncross-linked, wherein the dried hydrogel precursor layer forms a cross-linked hydrogel within no more than 5 minutes after hydration with a physiological solution.
40. The medical patch of claim 39, wherein the substrate is biodegradable and comprises gelatin and is partially thermally cross-linked, wherein the substrate is a foam, a nonwoven tufted material or a nonwoven felt material and persists for less than 2 weeks in an in vitro physiological solution maintained at 37°C.
41. The medical patch of claim 39 or claim 40, wherein the dried hydrogel precursor layer comprises multiple layers of a blend of the PEG-electrophilic hydrogel precursor and the PEG-nucleophilic hydrogel precursor, or a stack of one or more sublayers of the PEG-electrophilic hydrogel precursor and one or more sublayers of the PEG-nucleophilic hydrogel precursor, wherein adjacent sublayers are in direct contact with each other, and wherein the width and length of the medical patch are independently about 1 cm to about 15 cm and the thickness is about 0.5 mm to about 5 mm.
42. The medical patch of any one of claims 39-41, wherein the PEG-electrophilic hydrogel precursor and the PEG-nucleophilic hydrogel precursor independently have a molecular weight of about 10K Da to about 25K Da and 4 to 8 arms, and wherein the reactive electrophilic group comprises an ester.
43. A wound packing composition comprising a quantity of minced material from a patch according to any one of claims 39 to 42.
44. A method for forming a medical patch, the method comprising: One or more layers of liquid are applied to a porous hydrophilic substrate in a dry atmosphere to form a hydrogel precursor layer on the porous hydrophilic substrate, wherein the hydrogel precursor layer comprises a blend of an electrophilic hydrogel precursor and a protected nucleophilic hydrogel precursor, or a stack of sublayers of each of the electrophilic hydrogel precursor and the protected nucleophilic hydrogel precursor, wherein adjacent sublayers are in direct contact with each other, wherein the protected nucleophilic hydrogel precursor comprises an acidified amine, wherein the liquid comprises the electrophilic hydrogel precursor and / or the protected nucleophilic hydrogel precursor, and wherein the liquid comprises a melt or non-aqueous solution of the electrophilic hydrogel precursor and / or the protected nucleophilic hydrogel precursor.
45. The method of claim 44, wherein the temperature of the liquid does not exceed about 95°C.
46. A method according to claim 44 or claim 45, further comprising drying the porous hydrophilic substrate prior to applying.
47. The method of claim 46, wherein the drying is performed until the porous hydrophilic substrate has a water content of no more than about 2% by weight water.
48. The method of any one of claims 44-47, wherein the applying comprises slot die coating, doctor blade, spraying or sprinkling.
49. The method of any one of claims 44-48, wherein the medical patch has a thickness of no more than about 5 mm.
50. The method of any one of claims 44-49, further comprising sterilizing the medical patch by radiation.
51. The method of any one of claims 44-50, further comprising forming the medical patch into a three-dimensional contoured shape after applying the one or more layers of the liquid.
52. A method for using a medical patch, the method comprising: One or more medical patches are placed on or in a bleeding defect associated with an organ, wherein the medical patch comprises a biocompatible substrate and an initially dried, substantially non-crosslinked hydrogel precursor layer on the substrate, wherein the layer comprises an electrophilic hydrogel precursor and a nucleophilic precursor as a blend or in the form of multiple stacked sublayers in direct contact with each other.
53. The method of claim 52, wherein the one or more medical patches are provided in a disposable pharmaceutical package having a high moisture barrier and / or a desiccant.
54. The method of claim 52 or claim 53, further comprising contouring the one or more medical patches to have a three-dimensional shape corresponding to the interior of the bleeding defect.
55. The method of any one of claims 52-54, wherein the organ is a bone, a gland, a digestive organ, a lung organ, a urinary organ, a reproductive organ, a blood vessel, an interface with a natural or synthetic implant, or a combination thereof.
56. The method of any one of claims 52-55, wherein the bleeding defect is a suture, a puncture wound, a gunshot wound, a cavity, an abrasion, a biopsy puncture hole, a graft interface, or a combination thereof.
57. The method of any one of claims 52-56, wherein the placing is performed without pre-wetting the one or more medical patches.
58. The method of any one of claims 52-57, further comprising wetting the one or more medical patches with non-buffered water or non-buffered saline prior to and / or after placement.
59. The method of any one of claims 52-58, wherein the placing comprises placing the one or more medical patches on the bleeding defect in a non-planar geometry.
60. The method of any one of claims 52-59, wherein the placing comprises wrapping one or more medical patches around the organ.
61. The method of claim 60, wherein the organ is an artery or a vein, and wherein the organ is native, transplanted, or a combination thereof.
62. The method of any one of claims 52-59, wherein the placing comprises directing the medical patch onto or into a bleeding defect with a tubular applicator, wherein the medical patch has a three-dimensional contoured shape.
63. The method of claim 62, wherein the tubular applicator has a shape that integrates with the three-dimensional shape of the medical patch.
64. The method of claim 62, wherein the tubular applicator has a tapered end and the three-dimensional shape of the medical patch is a cone, wherein placing comprises directing the medical patch transvaginally to the cervix using the tubular applicator.
65. The method of any one of claims 52-64, wherein the placing comprises placing one or more first medical patches on the bleeding defect and then placing one or more second medical patches, the one or more second medical patches overlapping at least a portion of the one or more first medical patches.
66. The method of any one of claims 52-65, wherein the placing further comprises applying manual pressure to the one or more medical patches for no longer than about 2 minutes.
67. The method of any one of claims 52-66, wherein the placing results in hemostasis within about 5 minutes.
68. The method of claim 67, wherein the bleeding defect has an Adam score of 1 to 4.
69. The method of any one of claims 52-68, wherein contact with a physiological fluid associated with the organ causes the layer to form a hydrogel in no more than about 2 minutes, wherein the hydrogel adheres to the organ.
70. The method of any one of claims 52-69, wherein the width and length of the one or more medical patches are independently about 1 cm to about 15 cm, wherein the edges of the one or more medical patches adhere to the organ within about 5 minutes of placement.
71. The method of any one of claims 52-70, wherein the bleeding defect comprises blood that has been anticoagulated.
72. The method of any one of claims 52-71, wherein the one or more medical patches are fully absorbed in no more than about 28 days.
73. The method of any one of claims 52-72, wherein the one or more medical patches remain at least partially adhered to the organ until the one or more medical patches are substantially completely absorbed.
74. The method of any one of claims 52-73, wherein the one or more medical patches have a gel time of no more than about 5 minutes at 37°C, wherein the gel time is measured in vitro using a texture analyzer immediately after activation of the patch with a buffer solution having a pH of 8 to generate a force versus time curve, wherein the gel time is the time corresponding to the lowest force on the curve.
75. The method of any one of claims 52-74, wherein the one or more patches have a burst pressure of at least about 50 mm Hg.
76. A particulate composition comprising a blend of a porous hydrophilic material and a hydrogel precursor, wherein the hydrogel precursor comprises an electrophilic hydrogel precursor having multiple electrophilic functional groups and a nucleophilic hydrogel precursor having multiple protonated amine groups and no more than about 2 weight percent of water, wherein both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncross-linked and are in the same particle, or in different particles, or a combination thereof.
77. A particle composition according to claim 76, wherein the porous hydrophilic material and the hydrogel precursor form a composite material within the particle.
78. The particle composition of claim 76, wherein the porous hydrophilic material forms an intra-particle composite with the electrophilic hydrogel precursor or the nucleophilic hydrogel precursor.
79. The particle composition of claim 76, wherein the composite material of the porous hydrophilic material and the hydrogel precursor are in different particles.
80. The particle composition of claim 76, wherein the porous hydrophilic material, the electrophilic hydrogel precursor, and the nucleophilic hydrogel precursor are in different particles.
81. The particle composition of claim 76, wherein the porous hydrophilic material, the electrophilic hydrogel precursor, the nucleophilic hydrogel precursor, or a blend of the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor at least partially coats the porous hydrophilic material.
82. The particle composition of any one of claims 76-81, comprising 10% to 75% by weight of the porous hydrophilic material, wherein the ratio of electrophilic functional groups to protonated amine groups is approximately 1.
83. A particle composition according to any one of claims 76-82, wherein the porous hydrophilic material comprises two or more materials.
84. The granular composition of any one of claims 76-83, comprising particles having an average diameter of about 0.001 mm to about 2 mm.
85. The granular composition of any one of claims 76-84, comprising a powder.
86. The particulate composition of any one of claims 76-85, further comprising an imaging agent and / or a therapeutic agent.
87. A method of using the granular composition according to any one of claims 76-86, the method comprising: The particulate composition is placed on or in a bleeding defect.
88. A medical patch comprising a biocompatible substrate and a hydrogel precursor presenting a surface along one side of the biocompatible substrate, the hydrogel precursor comprising an electrophilic hydrogel precursor having a plurality of electrophilic functional groups and a nucleophilic hydrogel precursor having a plurality of nucleophilic functional groups, wherein the biocompatible substrate comprises thermally cross-linked gelatin, wherein the hydrogel precursor at least partially extends into the surface of the biocompatible substrate to form an adhesive hydrogel precursor structure, wherein the adhesive hydrogel precursor structure comprises a blended layer and / or separate adjacent layers of the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor, and wherein the medical patch presents a fractured surface of the adhesive hydrogel precursor structure adhered to the biocompatible substrate.
89. The medical patch of claim 88, wherein the biocompatible substrate comprises a foamed gelatin material.
90. The medical patch of claim 89, wherein the foamed gelatin material comprises gelatin felt.
91. The medical patch of claim 88, wherein the biocompatible substrate consists essentially of foamed gelatin having a ruptured cell structure.
92. The medical patch of any one of claims 88-91, wherein the biocompatible substrate is capable of absorbing 100% to 2500% by weight of water relative to the weight of the dry patch.
93. The medical patch of any one of claims 88-92, wherein the biocompatible substrate does not adhere to surgical gloves or gauze moistened with a non-buffered solution when dry or wet.
94. The medical patch of any one of claims 88-93, wherein both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncrosslinked.
95. The medical patch of any one of claims 88-94, wherein the adhesive hydrogel precursor structure comprises the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor in a plurality of stacked layers in direct contact with each other.
96. The medical patch of any one of claims 88-94, wherein the adhesive hydrogel precursor structure comprises the blended layer.
97. The medical patch of any one of claims 88-96, wherein the adhesive hydrogel precursor structure is free of buffer and free of non-aqueous solvent.
98. The medical patch of any one of claims 88-97, wherein the medical patch has a thickness of about 0.25 mm to about 10 mm when dry, and a width and length independently of about 1 cm to about 15 cm.
99. The medical patch of any one of claims 88-98, wherein the adhesive hydrogel precursor structure has a surface that substantially conforms to a surface of the biocompatible substrate.
100. The medical patch of any one of claims 88-99, wherein the medical patch is sufficiently flexible when dry so that it can be wrapped around a 1 / 2 inch shank without breaking.
101. The medical patch of any one of claims 88-100, wherein the medical patch has an accordion-like folded shape.
102. The medical patch of any one of claims 88-101, wherein the medical patch can be rolled or folded without breaking for laparoscopic delivery through a trocar.
103. The medical patch of any one of claims 88-102, wherein the adhesive hydrogel precursor structure cross-links in less than about 30 seconds to form an adhesive hydrogel structure after exposure to physiological fluid or physiological buffered saline.
104. The medical patch of any one of claims 88-103, wherein the adhesive hydrogel precursor structure spontaneously cross-links to form an adhesive hydrogel structure when exposed to physiological fluids or physiological buffered saline.
105. The medical patch of any one of claims 88-104, wherein the fractured surface comprises a plurality of microcracks and / or fissures resulting from a compression manufacturing step.
106. The medical patch of any one of claims 88-105, wherein the nucleophilic hydrogel precursor comprises a plurality of protonated amine groups.
107. The medical patch of any one of claims 88-106, wherein the electrophilic hydrogel precursor has a first hydrophilic core comprising a polymer having a molecular weight of at least about 5000 Da, and wherein the nucleophilic hydrogel precursor has a second hydrophilic core comprising a polymer having a molecular weight of at least about 2500 Da, wherein the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are each water soluble.
108. The medical patch of claim 107, wherein the first hydrophilic core and the second hydrophilic core independently have a molecular weight of about 5K Da to about 35K Da and 4 to 8 arms, and wherein the first hydrophilic core and the second hydrophilic core comprise polyethylene glycol, polyoxazoline, or copolymers thereof.
109. The medical patch of any one of claims 88-108, wherein the electrophilic hydrogel precursor has an electrophilic functional group comprising a succinimidyl ester.
110. The medical patch of any one of claims 88-109, wherein the medical patch further comprises a therapeutic agent.
111. The medical patch of any one of claims 88-109, wherein the therapeutic agent comprises an analgesic, an anesthetic, a steroid, an antibiotic, a steroid, an anti-infective agent, an anti-inflammatory agent, a nonsteroidal anti-inflammatory drug, an anti-proliferative agent, or a combination thereof.
112. The medical patch of any one of claims 88-111, wherein the adhesive hydrogel precursor structure further comprises an imaging agent.
113. The medical patch of claim 112, wherein the imaging agent is biocompatible and comprises a colorant, a contrast agent, or a combination thereof.
114. The medical patch of any one of claims 88-113, wherein the medical patch has a storage stability against significant gelling for at least about 2 months under dry storage.
115. The medical patch of any one of claims 88-114, wherein the medical patch has a storage stability against significant gelling under refrigerated conditions for at least about 1 year.
116. The medical patch of any one of claims 88-115, wherein the medical patch is provided in a moisture-proof packaging.
117. The medical patch of any one of claims 88-116, wherein contact with physiological fluids results in complete absorption of the medical patch in no more than about 9 days.
118. The medical patch of any one of claims 88-117, wherein the medical patch has a burst pressure of at least about 150 mm Hg.
119. A method for using a flexible medical patch, the method comprising: One or more flexible medical patches are placed on or in a target bleeding site, wherein the flexible medical patch comprises a biocompatible substrate and a hydrogel precursor presenting a surface along one side of the biocompatible substrate, wherein the hydrogel precursor comprises an electrophilic hydrogel precursor and a nucleophilic hydrogel precursor as a blend and / or in a plurality of stacked regions in direct contact with each other, wherein the biocompatible substrate has a ruptured pore structure, wherein the hydrogel precursor is initially dried and substantially uncrosslinked and extends at least partially into the ruptured pore structure of the biocompatible substrate to form an adhesive hydrogel precursor structure, wherein the medical patch is hemostatically adhered to the target bleeding site.
120. The method of claim 119, wherein the biocompatible substrate comprises thermally cross-linked gelatin.
121. The method of claim 119 or claim 120, wherein the placing is performed without pre-wetting the one or more flexible medical patches.
122. The method of any one of claims 119-121, wherein the placing comprises placing the one or more flexible medical patches on the target bleeding site in a non-planar geometry.
123. The method of any one of claims 119-122, wherein the placing comprises wrapping one or more flexible medical patches around a body structure, wherein the body structure comprises the target bleeding site.
124. The method of any one of claims 119-123, wherein the target bleeding site is associated with an artery and / or a vein, and wherein the artery and / or the vein is natural, transplanted, or a combination thereof.
125. The method of any one of claims 119-124, wherein the method further comprises bending or folding the one or more flexible medical patches into a three-dimensional shape prior to placement.
126. The method of claim 125, wherein the three-dimensional shape comprises accordion folds.
127. The method of claim 125, wherein the bending or folding is performed without pre-wetting the one or more flexible medical patches.
128. The method of any one of claims 119-127, wherein placing comprises directing the one or more flexible medical patches through a tubular applicator onto or into the target bleeding site.
129. The method of claim 128, wherein the tubular applicator comprises a cannula.
130. The method of claim 128 or claim 129, wherein the target bleeding site is associated with a laparoscopic surgical site.
131. The method of any one of claims 119-130, wherein the placing further comprises applying manual pressure to the one or more flexible medical patches for no longer than about 30 seconds.
132. The method of any one of claims 119-131, wherein the placing results in hemostasis within about 3 minutes.
133. The method according to any one of claims 119-132, wherein the target bleeding site has an Adam score of 1 to 4 and / or a SPOT score of 1 to 4. Rating is 1 to 5.
134. The method of any one of claims 119-133, wherein contact with a physiological fluid associated with the target bleeding site causes the adhesive hydrogel precursor structure to form an adhesive hydrogel structure in no more than about 30 seconds, wherein the adhesive hydrogel structure adheres to the target bleeding site.
135. The method of any one of claims 119-134, wherein the target bleeding site exudes blood that has been anticoagulated.
136. The method of any one of claims 119-135, wherein the one or more flexible medical patches are completely absorbed in no more than about 28 days.
137. The method of any one of claims 119-136, wherein the one or more flexible medical patches are completely absorbed in less than about 7 days.
138. The method of any one of claims 119-137, wherein the one or more flexible medical patches remain at least partially adhered to the target bleeding site until the one or more flexible medical patches are substantially completely absorbed.
139. A medical patch comprising a biocompatible substrate and a hydrogel precursor, wherein the hydrogel precursor comprises a solid blend and / or a separate solid layer of an electrophilic hydrogel precursor having a plurality of electrophilic functional groups and a nucleophilic hydrogel precursor having a plurality of nucleophilic functional groups, wherein both the electrophilic hydrogel precursor and the nucleophilic hydrogel precursor are substantially uncross-linked, wherein the biocompatible substrate comprises thermally cross-linked gelatin having a ruptured pore structure, wherein the hydrogel precursor at least partially extends into the ruptured pore structure of the biocompatible substrate to form an adhesive hydrogel precursor structure.
140. The medical patch of claim 139, wherein the biocompatible substrate comprises a foamed gelatin material, a nonwoven felt gelatin material, or a nonwoven tufted gelatin material.
141. The medical patch of claim 139 or claim 140, wherein the biocompatible substrate comprises a gelatin sponge or gelatin felt capable of absorbing 100% to 2500% by weight of water relative to the dry weight of the patch.
142. The medical patch of claim 139, wherein the biocompatible substrate consists essentially of foamed gelatin and the hydrogel precursor.
143. The medical patch of any one of claims 139-142, wherein the biocompatible substrate has a thickness of about 0.2 mm to about 8 mm when the medical patch is dry.
144. The medical patch of any one of claims 139-143, wherein the medical patch further comprises a therapeutic agent.
145. The medical patch of claim 144, wherein the therapeutic agent comprises an analgesic, an anesthetic, a steroid, an antibiotic, a steroid, an anti-infective agent, an anti-inflammatory agent, a nonsteroidal anti-inflammatory drug, an anti-proliferative agent, or a combination thereof.
146. The medical patch of any one of claims 139-145, wherein the medical patch further comprises an imaging agent.
147. The medical patch of any one of claims 139-146, wherein the adhesive hydrogel precursor structure has a surface that substantially conforms to a surface of the biocompatible substrate.
148. The medical patch of any one of claims 139-147, wherein the hydrogel precursor presents a surface on one side of the biocompatible substrate and is absent on the other side of the biocompatible substrate.
149. The medical patch of any one of claims 139-148, wherein the medical patch is sufficiently flexible when dry that it can be wrapped around a 1 / 2 inch mandrel without breaking.
150. The medical patch of any one of claims 139-149, wherein the medical patch has a three-dimensional folded shape.
151. The medical patch of any one of claims 139-150, wherein the medical patch has an accordion-like folded shape.
152. The medical patch of any one of claims 139-151, wherein the medical patch can be rolled or folded without breaking for laparoscopic delivery through a trocar.
153. The medical patch of any one of claims 139-152, wherein the adhesive hydrogel precursor structure cross-links in less than about 30 seconds after exposure to physiological fluids or physiological buffered saline.
154. The medical patch of any one of claims 139-153, wherein the adhesive hydrogel precursor structure spontaneously cross-links when exposed to physiological fluids or physiological buffered saline.
155. The medical patch of any one of claims 139-154, wherein the medical patch, when dry, exhibits a fractured surface of the adhesive hydrogel precursor structure adhered to the biocompatible substrate, wherein the fractured surface comprises a plurality of microcracks and / or cracks.
156. The medical patch of any one of claims 139-155, wherein the nucleophilic hydrogel precursor comprises a plurality of protonated amine groups.
157. A medical patch according to any one of claims 139-156, wherein the electrophilic hydrogel precursor comprises polyethylene glycol, polyoxazoline or a copolymer thereof having a molecular weight of about 10K Da to about 35K Da and having 3 to 8 arms terminated with succinimidyl ester functional groups, wherein the nucleophilic hydrogel precursor comprises polyethylene glycol, polyoxazoline or a copolymer thereof having a molecular weight of about 10K Da to about 35K Da and having 3 to 8 arms terminated with protonated amine functional groups.
158. The medical patch of claim 157, wherein the succinimidyl ester functional group comprises N-hydroxysuccinimidyl succinate (SS), N-hydroxysulfosuccinimidyl succinate, N-hydroxysulfosuccinimidyl glutarate, succinimidyl glutarate (SG), succinimidyl adipate (SAP), succinimidyl azelate (SAZ), or a mixture thereof.
159. A method for forming a medical patch, the method comprising: A structure comprising a biocompatible substrate and one or more hydrogel precursor layers is compressed to form the medical patch, wherein the one or more hydrogel precursor layers are melt-coated onto the substrate to present a surface along one side of the biocompatible substrate, wherein the biocompatible substrate comprises foamed gelatin having a broken pore structure, wherein the one or more hydrogel precursor layers at least partially extend into the broken pore structure of the biocompatible substrate to form a cohesive hydrogel precursor structure, wherein upon wetting with a physiological fluid or a physiological buffered saline, the cohesive hydrogel precursor structure cross-links to form a cohesive hydrogel structure.
160. The method of claim 159, wherein the compressing comprises calendering the structure.
161. The method of claim 160, wherein calendering is performed using calendering rolls having a gap of about 5% to about 70% of the thickness of the structure.
162. The method of any one of claims 159-161, wherein the one or more hydrogel precursor layers are at room temperature during the compressing.
163. The method of any one of claims 159-162, wherein the compressing breaks up the surface to form a fractured surface of the adhesive hydrogel precursor structure adhered to the biocompatible substrate.
164. The method of any one of claims 159-163, wherein the medical patch is more flexible and hydrates more rapidly than its pre-compression structure.
165. The method of any one of claims 159-164, wherein the medical patch is sufficiently flexible when dry so that it can be wrapped around a 1 / 2 inch shank without breaking.
166. The method according to any one of claims 159-165, further comprising coating the biocompatible substrate with one or more hydrogel precursor layers prior to compression to form one or more hydrogel precursor layers coated on the substrate, wherein the coating comprises melt coating a dry blend of an electrophilic hydrogel precursor having multiple electrophilic functional groups and a nucleophilic hydrogel precursor having multiple nucleophilic functional groups.
167. The method of claim 166, wherein the biocompatible substrate prior to coating is sufficiently flexible so that it can be wrapped around 1 / 2 inch shank without breaking.
168. The method of claim 166, further comprising initially compressing the biocompatible substrate prior to coating.
169. The method of claim 168, wherein the initial compression comprises calendering the biocompatible substrate.
170. The method of claim 169, wherein calendering is performed using calendering rolls having a gap of about 5% to about 65% of the thickness of the biocompatible substrate.
171. The method of claim 168, wherein compressing the biocompatible substrate causes the pore structure of the foamed gelatin to rupture.
172. A method according to any one of claims 159-171, wherein the foamed gelatin is thermally cross-linked.
173. The method of any one of claims 168-171, further comprising thermally cross-linking the biocompatible substrate prior to initial compression.
174. A method for forming a medical patch, the method comprising: applying a liquid hydrogel precursor to a porous hydrophilic substrate in a dry atmosphere, wherein the applying is performed by compressing the substrate at a printing position using a print head to inject the liquid hydrogel precursor into the compressed substrate, The liquid hydrogel precursor comprises an electrophilic hydrogel precursor and a protected nucleophilic hydrogel precursor, wherein the protected nucleophilic hydrogel precursor comprises an acidified amine, wherein the liquid hydrogel precursor comprises a melt or non-aqueous solution of the electrophilic hydrogel precursor and / or the protected nucleophilic hydrogel precursor.
175. The method of claim 174, wherein the porous hydrophilic substrate comprises thermally cross-linked gelatin.
176. A method according to claim 174 or claim 175, wherein application is performed using a print head that compresses the substrate to a selected depth.
177. The method of claim 176, wherein the selected depth is from about 5% to about 30% of the thickness of the porous hydrophilic substrate prior to application.
178. The method of any one of claims 174-177, wherein the liquid hydrogel precursor comprises a blend of the electrophilic hydrogel precursor and the protected nucleophilic hydrogel precursor.
179. A method according to any one of claims 174-178, wherein the liquid hydrogel precursor comprises a first melt of the electrophilic hydrogel precursor and a second melt of the nucleophilic hydrogel precursor, wherein applying comprises applying the first melt and then applying the second melt, or applying the second melt and then applying the first melt.
180. The method of any one of claims 174-179, further comprising calendering the porous hydrophilic substrate prior to applying.
181. The method of any one of claims 174-180, further comprising calendering the medical patch after applying.
182. A method according to claim 181, wherein calendering includes a first calendering and a second calendering, wherein the first calendering is performed using a calendering roller having a first gap, and the second calendering is performed using a calendering roller having a second gap, wherein the second gap is smaller than the first gap.